In-Situ engineering of hierarchical ZIF@HOF heterostructures for efficient antibiotic degradation: Mechanistic insights from experimental and DFT studies - Ali Ahmad; Naeem Akram; Muhammad Khurram Tufail; Bing Yu; Hailin Cong (Water Research, 2027)

Historical cold biases exaggerate future elevation-dependent warming over the Tibetan Plateau - Yu Deng; Qinglong You; Fangying Wu; Wenyu Zhou; Zhiyuan Cong; Zhiyan Zuo; Haijun Deng; Nick Pepin; Hans W. Chen; Deliang Chen; Renhe Zhang (Atmospheric Research, 2027)

Region-specific gut microbiota and metabolite crosstalk underlie feed efficiency variation in Strongylocentrotus intermedius - Lin Cong; Yuehan Yan; Yu Guan; Jialiang Dong; Ziling Qin; Yi Zheng; Zhe Song; Tianqi Wang; Xiaotong Wang; Wenchao Yu (Aquaculture, 2027)

GNSS-R simulation of oil-covered sea surface: Coupling effects of oil film thickness and kinematic viscosity under different wind speeds - Bin Wang; Jianqing Li; Dongmei Song; Weimin Chen; Honglei Zheng; Cong Yin; Jintao Yu (Marine Pollution Bulletin, 2026)

Unveiling microscale aerosol formation pathways in combustion systems: in situ evidence from cigarette burning cones - Jiaying Li; Huapeng Cui; Meijuan Fan; Li Chen; Yaqiong Qin; Ruihong Liu; Mantang Chen; Yu Liu; Jizhao Guo; Shaofeng Liu; Xiaobing Zhang; Fuwei Xie; et al. (Biomass and Bioenergy, 2026)

Time-of-day-dependent effects of exercise on the hepatic clock and proteome in high-fat diet-fed mice - Chunxiu Huang; Xiaodan Wang; Huanghao Zhou; JingFang Zhu; Yue Hu; Huijuan Wu; Xinru Yu; Cong Chen (Journal of Physiology and Biochemistry, 2026)

The role and mechanism of TNFRSF21 in promoting necroptosis of vascular endothelial cells and inducing vascular leakage in sepsis - Juntao Wang; Bindan Zhang; Yujia Wu; Weichao Li; Yuxi Zhang; Daiqin Bao; Haoyu Pei; Caifeng Shi; Han She; Xiaoyan Wang; Qingxiang Mao; Cong Yu (Journal of Molecular Medicine, 2026)

Migration and transformation patterns of pesticides and their transformation products across the groundwater-surface water continuum - Jun Liu; Mengwen Liu; Guiyao Xiong; Yi Cheng; Cong Han; Hao Geng; Xuebing Wang; Si Wei; Nanyang Yu; Xiaobin Zhu; Jianfeng Wu; Xiankui Zeng; et al. (Water Research, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

A novel scattering model for tight-rock reservoirs based on fractal cracks - Rupeng Ma; Jing Ba; José M. Carcione; Cong Luo; Bo Yu; Xiaobin Li; Liwei Song (International Journal of Rock Mechanics and Mining Sciences, 2026)

Over-expression of the solute carrier gene SLC23A1 as a novel mechanism contributing to imidacloprid resistance in Nilaparvata lugens - Fan Zhang; Zhi-Tao Yu; Yan-Chao Zhang; Yu-Qiu Xie; Li-Xiang Wang; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2026)

A natural Nlscarlet insertion underlies the orange-eye phenotype and facilitates efficient multiple-sgRNA genome editing in Nilaparvata lugens - Wen-Nan Ye; Rong-Yu Chen; Qi Xing; Yan-Chao Zhang; Shun-Fan Wu; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2026)

Oxidation patterns and stability mechanisms of marine oils revealed by oxidized triglyceride and phospholipid analysis using RPLC–Q-TOF - Nan Meng; Yaru Li; Peixu Cong; Yu Song; Yanjun Liu; Jie Xu; Changhu Xue (Food Research International, 2026)

Bovine-LTID: A vision-based spatio-temporal identity system for multi-camera cattle tracking and long-term behavior monitoring - Boyang Zhao; Bo Xiao; Cong Liu; Xiao Jin; JunMing Ye; Mingjie Yu; Zhenhua Yu (Computers and Electronics in Agriculture, 2026)

Numerical investigation on hysteretic behavior and damage accumulation mechanism of segmental joints under cyclic loading conditions - Weiling Gao; Linchong Huang; Cong Tian; Yu Liang; Zuxian Wang (Tunnelling and Underground Space Technology, 2026)

Flexural behavior and progressive interfacial debonding mechanism of BFRP-PCM composite-strengthened tunnel segments - Cong Tian; Linchong Huang; Yu Liang; Weiling Gao; Chenghao Li (Tunnelling and Underground Space Technology, 2026)

Experimental study on the hydrodynamic response of a liquid-filled cylinder inclined into water - Jiahui Li; Cong Wang; Jian Bao; Wenpeng Li; Yu Liu; Wenzhi Yan; Yanyi Ding (Ocean Engineering, 2026)

Engineering MOF-on-MOF heterostructure for enhanced adsorption-assisted photocatalytic decontamination of carbamazepine: Kinetics, thermodynamic and pathway study - Muhammad Fayaz; Raza Ullah; Muzamil Ahmad; Ikram Ullah; Muhammad Rafiq; Ali Ahmad; Nasim Ullah; Faizan Jamil; Latif Ur Rehman; Hammad Ali; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2026)

Overcoming curcumin's limitations via amorphous solid dispersion: Mechanistic insights, bioavailability enhancement, and shelf-life evaluation - Minghui Hao; Chenchen Yu; Chungang Zhang; Fantong Yu; Ti Wang; Cong Zhang (Journal of Food Engineering, 2026)

Self-synergistic viologen-based ionic conjugated polymers for external cocatalyst-free CO2 fixation - Fei Yu; Wenting Fang; Hang Cong; Song Yang; Xi-Sheng Wang; Wenfeng Zhao (Journal of Environmental Chemical Engineering, 2026)

Interfacial construction of Co-MOF/NiCu-MOF for enhanced visible-light-driven peroxymonosulfate activation and ciprofloxacin degradation: Mechanistic insights, kinetics and stability study - Raza Ullah; Nasim Ullah; Abdul Qadir; Muzamil Ahmad; Alamgir; Muhammad Fayaz; Muhammad Rafiq; Adeel Ahmed; Muhammad Adnan; Fangqing Wang; Bing Yu; Hailin Cong (Journal of Environmental Chemical Engineering, 2026)

Design of dual-function soil amendment via co-roasting K-feldspar with soda residue and oyster shell for acidity amelioration and potassium supply - Ernest Uwiringiyimana; Ren-Yong Shi; Jiu-Yu Li; Jia-Ning Gao; Yong-Ming Fu; Md. Romel Biswash; Cong-Ming Wu; Ren-Kou Xu (Journal of Environmental Chemical Engineering, 2026)

Elemental sulfur-enhanced hydrothermal stabilization of arsenic in arsenic sulfide sludges: Mechanism of sulfur-induced structure transformation and practical application - Hui Xu; Wanlan Wu; Qiujing Xu; Yong Ke; Yun Li; Cong Peng; Lin Yu; Zhumei Sun; Yunyan Wang; Xiaobo Min (Journal of Environmental Chemical Engineering, 2026)

Heterovalent Al/Mn bimetallic MIL-53(Al) with engineered defects for effective removal of nanoplastic from water - Jumeng Di; Xiaohua Li; Songyu Guan; Wenwen Ma; Wen Li; Jie Gao; Yuzhi Xu; Bing Yu; Hailin Cong (Journal of Environmental Chemical Engineering, 2026)

Enhanced aluminum removal via K+–NH4+ composite alum precipitation from beryllium leachates: Mechanism validation and application - Lin Yu; Xiaobo Min; Yunyan Wang; Yulin Zhou; Zhou Liao; Yun Li; Cong Peng; Hui Xu; Zhiyan Zeng; Yong Ke (Hydrometallurgy, 2026)

Disrupting the cardiolipin oxidation-apoptosis axis: low-temperature, high-salinity depuration extends anhydrous storage in Pacific oysters - Nan Meng; Xinyu Cao; Yu Song; Peixu Cong; Yanjun Liu; Yi Liu; Changhu Xue; Jie Xu (Food Research International, 2026)

Advancements in the research of antioxidant peptides: A comprehensive overview - Xuelin Bai; Wei Pan; Mengyuan Xu; Muhammad Rafiq; Bing Yu; Hailin Cong (Food Research International, 2026)

Skin temperature as input to behavioral thermal adaptation for energy-efficient HVAC control - Yu Dong; Yuan Shi; Yanfeng Liu; Cong Song; Bintian Lin; Jørn Toftum (Energy and Buildings, 2026)

Morphological engineering and valence state strategy enable stable nitrate-to-ammonia electroconversion at copper surface in the wide pH range - Yue-Han Qin; Xiao-Hui Wang; Ze-Nong Zhang; Shi-Bin Yin; Cong-Cong Han; Xuan Ai; Shu-Ni Li; Xin Wang; Yu Chen (Chemical Engineering Journal, 2026)

Multifunctional theranostic probe for trimodal detection and chemodynamic therapy of methicillin-resistant bacterial infections - Mohammed Y. Suleiman; Hao Jiang; Qianyu Guo; Hongzhan Liu; Shuang Song; Cunqi Wu; Saman Hosseinkhani; Cong Yu; Guobao Xu (Chemical Engineering Journal, 2026)

Distribution and fate of microplastics in river sediment downstream of a reservoir: the interplay of a storm event and aquatic plants - Jingzhe Zhou; Feixi Zhao; Cong Liu; Wei Li; Yu Cao (Hydrobiologia, 2026)

Extreme drought converts grassland carbon sinks to sources in Inner Mongolia, but strong recovery follows: Insights from a 9-year study - Shaoling Li; Rongle Zhang; Juejie Yang; Tai Yang; Cong Wang; Frank Hagedorn; Arthur Gessler; Marcus Schaub; Fei Li; Shikui Dong; Qiang Yu (Agricultural and Forest Meteorology, 2026)

A Comparative Numerical Study of Hydrodynamic and Acoustic Performance Between Contracted and Loaded Tip Pump-Jet and Conventional Pump-Jet - Yu Zhao; Chao Wang; Cong Sun; Yi-Ming Hu; Hao-Yu Liu; Min Liu (Journal of Marine Science and Engineering, 2026)
This study employs a Contracted and Loaded Tip (CLT) propeller to replace the conventional pump-jet rotor, and a comparative analysis is conducted using the Detached Eddy Simulation (DES) method. The reliability of the numerical method is first validated through open-water tests. The CLT pump-jet propulsors are systematically investigated in two series: the varying endplate width (CW) and varying endplate length (CL). The results indicate that varying the endplate width has a significant impact on the hydrodynamic performance. A smaller width leads to a more pronounced decrease in the thrust coefficient, torque coefficient, and efficiency. In contrast, varying the endplate length primarily affects the efficiency at high advance coefficients. Regarding the vortical characteristics, the gap region is dominated by the tip leakage vortex (TLV) and tip separation vortex (TSV), whose intensity and evolution are influenced by the endplate structure. A reduced endplate width expands the low-velocity region within the gap, while an increased length contributes to a more stable vortex development. In terms of the noise performance, the varying-width designs effectively suppress pressure fluctuations and achieve noise reduction. Specifically, the CW3 model exhibits maximum reductions in the overall sound source level of 5.7 dB and 4.0 dB at distances of 1 m and 20 m, respectively. Conversely, the varying-length designs intensify the pressure fluctuations and show no significant noise reduction effect.

Cascade-amplified oxidative stress coupled with tryptophan metabolic blockade for synergistic cancer immunotherapy - Xiaoya Wu; Yu Guo; Jianxin Rong; Jiahui Cong; Chunyong Liang; Zhigang Xie; Xiuli Hu (Chemical Engineering Journal, 2026)

Spatial heterogeneity and prioritization of chemical mixtures along the Yarlung Tsangpo River - Cong Wang; Xiaoping Wang; Wenyuan Su; Bao Zhu; Jie Fu; Kai Huang; Huimin Yu; Shuping Yang; Suona Zhuoga; Jianjie Fu (Water Research, 2026)

Large-strain self-weight consolidation model under double-drained conditions: A unified framework incorporating water weight effects - Cong Mou; Jiaxing Weng; Feng Ji; Jianhua Wang; Junjun Ni; Dechang Ren; Jin Yu (Transportation Geotechnics, 2026)

Field resistance monitoring and nAChR α6 target validation support spinetoram as a candidate insecticide for rotation in Nilaparvata lugens resistance management - Wen-Nan Ye; Qi Xing; Rong-Yu Chen; Yan-Chao Zhang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Targeted isolation of previously undescribed fortunefuroic acid-type triterpenoids from Keteleeria pubescens using 1H NMR/LC-PDA-MS and assessment of ACL Inhibition - Chun-Jing Chi; Ze-Yu Zhao; Yi Zang; Cong Li; Jia Li; Dong Huang; Peng Sun; Juan Xiong; Yeun-Mun Choo; Jin-Feng Hu (Phytochemistry, 2026)

Ginsenoside Rh3 induces barrier-associated injury in an in vitro blood-brain barrier model with involvement of MMP2/9 - Yuheng Wang; Cong Hu; Yu Liu; Xiaojing Wang; Geng Chang; Jianwen Chen (NeuroToxicology, 2026)

Photo-assisted catalytic oxidation using PBA-derived ZnCo oxides in a H₂O₂ system for organic pollutant removal - Jia-Yin Lin; Yun-Ju Lai; Ying-hua Lai; Ta Cong Khiem; Nai-Wen Tsao; Yu-Chih Tsai (Journal of Water Process Engineering, 2026)

Enhanced degradation of sunscreen additive through oxone activated by cobalt sulfide: Tailoring the nanostructure for boosting catalytic performance - Xin-Yu Jiang; Shaoping Tong; Ta Cong Khiem; Nguyen Nhat Huy; Wei-Jie Liu; Wei-Hsin Chen; Chechia Hu; Kun-Yi Andrew Lin (Journal of Water Process Engineering, 2026)

The role of transcription factor MdGeBP3 in Modulating cold stress tolerance and anthocyanin biosynthesis in apple - Ming-Kun Wang; Ran-Xin Liu; Cong-Yu Xu; Yue-Ning Wang; Xiao-Han Qin; Shan-Shan Li; Ying-Xue Lv; Du Liu; Jie Lu; Xiao-Fei Wang (Journal of Plant Physiology, 2026)

New insight into the role of lipids in the formation and retention of key aroma compounds in micro-pressure stewed beef based on lipidomics and lipid-derived free radical analysis - Huan Liu; Yu Liu; Xinhe Zhang; Bo Xiao; Pi Li; Peng Gao; Jiangtao Xing; Weiting Wang; Pengfei Du; Jingxian Cong; Chengyu Zeng; Cheng Li; et al. (Food Research International, 2026)

Revisiting the formation and differentiation of Neoproterozoic continental arc crust in the western Yangtze Block, South China - Yu Zhu; Xiao-ping Xia; Feng Guo; Yan-jie Tang; Xin Zhu; Chang-xin Yin; M.P. Manu Prasanth; Ren-zhi Zhu; Min Liu; Zhuang Guo; Jiang-feng Qin; Fang-yi Zhang; et al. (Chemical Geology, 2026)

Water-mass structuring of metazoan communities inferred from environmental DNA in the Chukchi Borderland during the summer sea-ice retreat period - Zhiyi Su; Wei Luo; Yong Yu; Kun Liu; Zihan Wang; Zheying Lin; Ling Cao; Cong Zeng (Polar Biology, 2026)

Periphyton plays a dual role in the bioavailability of organic phosphorus in aquatic environments - Cong-min Wu; Ren-yong Shi; Yuan-chun Yu; Xin-yu Hu; Ernest Uwiringiyimana; Jiu-yu Li; Ren-kou Xu (Applied Geochemistry, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Mechanisms of aerobic simultaneous nitrogen removal under low COD/N conditions: Diffusion–reaction coupling and particle size effects via self-recirculating microgranular system - Lifang Liu; Cong Wang; Wei-Kang Qi; Shu-Jun Zhang; Yu-You Li; Yongzhen Peng (Water Research, 2026)

Primary amine-functionalized HTO/CMC/PVA composite films: Highly selective lithium adsorption and applications in complex lithium-containing systems - Shengkai Liu; Ruimeng Liu; Wenxuan Wang; Dandan Hu; Yu Han; Cong Li; Huiling Li; Chang Wan; Tai Peng; Wei Wang; Daxin Liang (Process Safety and Environmental Protection, 2026)

Three New Arnebin-type metabolites extracted from Arnebia euchroma: Structural analysis and antitumor activity evaluation - Guang-Jie Pan; Yu Sun; De-Gang Qing; Cong-Zhao Fan; Guo-Xu Ma; Zhong-Hao Sun; Lei-Ling Shi; Jing Zhang (Phytochemistry Letters, 2026)

Load-transfer evolution and redistribution in instrumented large-diameter bored piles in coastal sand–clay–rock strata: Roles of post-grouting and pile geometry - Jichao Yin; Xiaoyu Bai; Yamei Zhang; Nan Yan; Yu Cong; Mingyi Zhang; Songkui Sang (Ocean Engineering, 2026)

Installation-induced spatial degradation of strength and cyclic stiffness evolution in pile-surrounding mudstone - Jichao Yin; Xiaoyu Bai; Yamei Zhang; Nan Yan; Yu Cong; Mingyi Zhang; Songkui Sang (Ocean Engineering, 2026)

Elastic preloading-enhanced parallel-column brace for vibration suppression of deep-sea mining towers - Shubin Ji; Li Zou; Qianxi Zhang; Cong Wang; Yingjie Wei; Zongbing Yu (Ocean Engineering, 2026)

A study on the hydrodynamic performance and wake modulation effect of a twisted pre-swirl stator in a rim-driven thruster - Yi-Ming Hu; Cong Sun; Min Liu; Chun-Yu Guo; Pei-Rui Tang; Yu Zhao; Chao Wang (Ocean Engineering, 2026)

Origin and migration of ore-forming fluids in the Dafulou tin deposit, Dachang district, South China: Constraints from cassiterite UPb geochronology, trace elements, fluid inclusions and oxygen isotopes - Cong Xu; Kui-Dong Zhao; Jia-Sheng Hu; Qian Li; Yu-Song Guo; Shao-Yong Jiang (Journal of Geochemical Exploration, 2026)

Unveiling the dynamic electron transfer at asymmetric Fe-O-Co sites for sustained PMS activation via in-situ synchrotron spectroscopy - Xian-Chuan Chen; Fu-Sheng Sun; Cong-Qiang Liu; Guang-Hui Yu (Journal of Environmental Sciences, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

Elucidating the oxidation mechanism of phospholipid-based marine oils during storage: A new insight based on the analysis of oxidized phospholipids - Nan Meng; Peixu Cong; Xincen Wang; Yu Song; Yanjun Liu; Yaru Li; Jie Xu; Changhu Xue (Food Research International, 2026)

Investigating the molecular mechanism of plasmalogen and quality changes in Pacific oyster (Crassostrea gigas) depurated under salinity stress - Yu Song; Lili Hao; Xincen Wang; Peixu Cong; Yanjun Liu; Xiaoxu Wang; Zhaojie Li; Changhu Xue; Jie Xu (Food Research International, 2026)

Surface functionalized treatment of Co3O4 by modifying phosphate group to boost peroxymonosulfate activation for effective degradation of antibiotic - Wei Wang; Ziyi Guo; Menglan Xu; Shengran Yu; Lvjun Jin; Hao Fang; Yanqing Cong; Shi-Wen Lv (Environmental Research, 2026)

Predictors, sources, and health risks of environmental antibiotic exposure in Chinese pregnant women - Lu Qian; Yi Wang; Sumiao Hong; Yuanping Wang; Haiping Lin; Yuanyuan Chen; Baochang Sun; Yu Liu; Mingxue Wang; Xinyi Zhu; Haozhe Gu; Jiaqi Liu; et al. (Environmental Pollution, 2026)

MgI2 immobilized nitrogen and phosphorus co-doped hollow carbon cubes as a multifunctional host for high-performance lithium‑sulfur batteries - Sheng Liang; Cong Li; Zi-Hao Chen; Lei Hu; Xin Liang; Ling-Li Liu; Li-Li Wang; Ning-Ning Zhou; Bin Chen; Wen-Yu Gu; San-E Zhu (Chemical Engineering Journal, 2026)

Distinct extraction methods alter physicochemical properties and bioactivities of polysaccharides extracted from Pycnoporus sanguineus - Cong Xia; Di Huang; Lu Yu; Yang Liu; Xuemei He; Xinhong Dong; Xia Li; Hock Eng Khoo (Biocatalysis and Agricultural Biotechnology, 2026)

Regional flooding enhances N2O and CH4 emissions from agricultural fields: Evidence from a single extreme event across the North China Plain - Zhengkui Ge; Zhifeng Yan; Mike Peacock; Si-Liang Li; Xiaotang Ju; Pete Smith; Guirui Yu; Cong-Qiang Liu (Agricultural and Forest Meteorology, 2026)

Corrigendum to “Assessing environmental pressure efficiency in Chinese bivalve aquaculture: Spatio-temporal dynamics and policy implications (2008–2023)” Aquaculture, Volume 622, 15 July 2026, 744071 - Cong Yu; Xu Chen; ShuaiShuai Jia; Runsheng Pei; Qun Liu; Suman Barua (Aquaculture, 2026)

Characterizing brain structural and functional abnormalities in borderline personality disorder by seed-based d mapping approach - Wanru Qiu; Sen Li; Aoxue Zhang; Hao Yu; Jian Cui; Yinghong Xu; Liangliang Ping; Hao Zheng; Chunyu Dong; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2026)

PD-1/PD-L1 inhibitor induces systemic inflammation and alters cardiac lipid metabolism in C57BL/6 J mice - Cong Ye; Zhi-Ting Jiang; Chen Yan; Xin-Ran Li; Yu-Hua Zhu; Ling-Yu Zeng; Lan Luo (Human Cell, 2026)

Assessing environmental pressure efficiency in Chinese bivalve aquaculture: Spatio-temporal dynamics and policy implications (2008–2023) - Cong Yu; Xu Chen; Shuaishuai Jia; Runsheng Pei; Qun Liu; Suman Barua (Aquaculture, 2026)

IL-8-expressing recombinant Bacillus subtilis: A novel immunostimulant for improving production efficiency and disease resilience in Sebastes schlegelii aquaculture - Qing Yang; Hong-Yu Jiang; Ming-Tao Li; Bin-Tong Yang; Shu Li; Wei Cong; Yuan-Huan Kang (Aquaculture, 2026)

NPY-Y2R driven neuroimmune signaling as a potential therapeutic target for trigeminal neuralgia: clinical and experimental evidence - Zi-Le He; Chao Xu; Qi-Fan Yang; Cong-Zhou Han; Ting Wu; Yu-Qing Xu; Yun-Ze Liu; Liang-Yu Ni; Si-Qi Jia; Tang-Yu Zhang; Yun Wang; Yi Feng (Science Bulletin, 2026)

Effects of circumferential and streamwise micro-groove arrangements on the hydrodynamic and acoustic performance of a pump-jet propulsor - Chao Wang; Yu Zhao; Cong Sun; Lian-Zhou Wang; Yu-Long Feng (Ocean Engineering, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Comparative analysis of the structure and content of N-glycans in bovine, goat, and yak milk during lactation - Cong Li; Qiuqi Peng; Hongjuan Li; Hongbo Li; Jinghua Yu (International Dairy Journal, 2026)

Nutritional composition and processing technologies of liquid infant formula: A systematic review with reference to breast milk - Cong Li; Hongbo Li; Hongjuan Li; Jinghua Yu (International Dairy Journal, 2026)

Climate change rather than grazing dominates the declined resilience of Chinese grassland - Huanhuan Liu; Yangjian Zhang; Zhoutao Zheng; Guang Zhao; Yu Zhang; Li Liu; Nan Cong; Xiaoqing Duan; Yihan Sun (Global and Planetary Change, 2026)

Molecular fractionation of dissolved organic matter: A governing mechanism for the coupled fate of phosphorus and chromium at iron mineral interfaces - Cong Fan; Zhoumei Hu; Qian Yao; Limiao Cai; Bing Zhang; Xiaohu Jin; Yu Liu; Chuling Guo; Guining Lu; Xiaofei Li; Zhi Dang (Chemical Engineering Journal, 2026)

Characterizing tissue-specific accumulation dynamics and assessing healthy risk of organic insecticides in sea cucumbers based on a multicompartmental toxicokinetic model - Xiao Cong; Tongtong Jiang; Lei Wang; Kang Dong; Zhenglin Yu; Shoufeng Chi; Xiutang Yuan (Aquatic Toxicology, 2026)

Evaluation and comparison of TCR repertoire differences between patients with cervical cancer and healthy individuals - Wenwen Gao; Cong Wang; Jiawen Jia; Yiqian Li; Ting Li; Ling Liu; Yi Zhang; Haibin Yu; Cuiping Yang; Xiaoli Fu; Yongbin Chen; Yan Cheng (Science China Life Sciences, 2026)

Autotetraploid induction and one-step regeneration, and transcriptomic analysis in Dendrobium officinale - Cong-Dan Zheng; Jun-Yu Su; Shang-Yan Fu; Jie-Mei Deng; Zi-Ting Zhu; Heng-Yu Huang; Yuan-Zhong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Evaluating the quality and reliability of DILI in Chinese videos on TikTok (Douyin) and BiliBili: cross-sectional content analysis study - Ruogu Nie; Bing Yu; Han Wang; Shengying Qin; Cong Huai; Zhiling Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Probiotic Effects of Marichromatium gracile DH-1 on Growth, Stress Resistance, and Water Quality in Juvenile Seahorses: A Potential Strategy for Sustainable Aquaculture - Kai-Hua Geng; Shuai Liang; Yi Zhang; Ya-Juan Wang; Tian-Yu Lu; Yunfeng Liu; Tian Lan; Ya-Nan Lu; Yu-Ting Cong; Yuan Wang; Li Wang; Lian-Shun Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Influence of ground pressure on grounding performance of deep-sea mining vehicle tracks - Junlin Zhao; Manhong Li; Hao Zheng; Yangrui Cheng; Zhou Li; Cong Ding; Andi Yu; Gen Li (Ocean Engineering, 2026)

NaOH regulation of steel slag carbonation: Interfacial activation and kinetic enhancement - Wenjing Tang; Jiale Tian; XinYu Zhu; Yu Cong Ge; Tao Wang; Zhenwei Yi; Mengxiang Fang; Kun Luo; Xiang Gao (Journal of Environmental Chemical Engineering, 2026)

Beyond performance-cost trade-off: Engineered Geopolymer Composites (EGC) incorporating ultra-high-volume coal gangue wastes - Zhi-Liang Zhang; Ze-Ming Yang; Ling-Yu Xu; Jian-Cong Lao; Hui Zhang; Yu-Jie Huang; Linghua Shen; Dan-Dan Shi; Bo-Tao Huang (Journal of Cleaner Production, 2026)

Enhanced antifriction and antiwear performances of steel achieved by porous boron nitride/grease composite triggered self-adaptive confined lubrication - Heng He; Fengli Zhou; He Huang; Songyan Cong; Beiyi Zhang; Weiben Chen; Yibing Lin; Li Qiang; Yuanlie Yu (Journal of Environmental Chemical Engineering, 2026)

Intelligent technology-enabled comprehensive research on microplastics: Detection, fate, and ecological effects - Yuzhi Liu; Shibo Cong; Yu Gao (Journal of Environmental Chemical Engineering, 2026)

Heterogeneous slab components impart diverse oxygen isotope of arc magmas in northwestern circum-Rodinia subduction system - Yu Zhu; Xiao-ping Xia; Xin Zhu; Chang-xin Yin; Zhuang Guo; Ren-zhi Zhu; Min Liu; Fang-yi Zhang; Hang Yang; Shao-cong Lai (Geochimica et Cosmochimica Acta, 2026)

Self-consolidation mechanism of lead‑zinc secondary oxide materials pellets without additional binder - Maixin Yu; Yunyan Wang; Yun Li; Liyuan Chai; Xin Wang; Changhao He; Pingsheng Zeng; Cong Peng; Yong Ke; Zongliang Zhang; Xiaobo Min (Chemical Engineering Journal, 2026)

Vegetation and human-activity signals from pollen over the last millennium: Implications for organic carbon sources in the Pearl River estuary - Shaohua Yu; Fang Chen; Qing Zhu; Kangyou Huang; Yang Zhou; Cong Wu; Chang Zhuang; Xia Jing; Kaijun Cao; Dehao Tang (CATENA, 2026)

Rapid and sensitive detection of feline herpesvirus-1 using fluorescent microspheres as labels for immunochromatographic test strips - Peipei Shao; Yuexiao Lian; Xiangnan Liu; Huizhen Liu; Jiantao Yu; Yongping Tang; Feng Cong; Ye Ge (Veterinary Research Communications, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Distribution patterns of potential soil phytopathogenic fungi and their association with plant communities in natural broadleaved forests - Jin Li; Wei Cong; Haimang Yu; Jing Cong; Yuan Yang; Zhen Li; Ye Deng; Kai Feng; Yuguang Zhang (Plant and Soil, 2026)

Root morphological strategies enhance growth of Cunninghamia lanceolata and Schima superba under nitrogen stress in intercropping systems - Xiao-Li Yan; Cong Cheng; Yunhao Xu; Jiaxiang Yu; Zhaozhao Wang; Yanru Wang; Xinghao Tang; Pengfei Wu; Xiangqing Ma; Lu-Ping Qu (Plant and Soil, 2026)

The long non-coding RNA PVT1 promotes keratinocyte proliferation and inflammation in psoriasis by targeting miR-485-5p - Wanwan Yu; Boling Qi; Can Cong; Yining Ma; Qingtao Kong; Hong Sang (Journal of Molecular Histology, 2026)

A framework for analyzing the spatiotemporal evolution of seismic functionality loss for irregular buildings considering the interdependencies of components - Gang Li; Yong Guo; Ding-Hao Yu; Yang Cong (Bulletin of Earthquake Engineering, 2026)

Axillary bud-driven propagation combined with ex vitro rooting: establishment of an efficient rapid propagation system for parthenocarpic Solanum muricatum - Cong-Dan Zheng; Qing Yang; Heng-Yu Huang; Jia-Jia Liu (In Vitro Cellular & Developmental Biology - Plant, 2026)

Engineering phosphoribosylpyrophosphate synthetase in Methylobacterium radiotolerans for lettuce growth and quality enhancement - Long-Yu Zhang; Dan-Dan Tian; Zhe Liu; Ming-Ming Zhang; Jing Wu; Shuai-Jie Wang; Song Yang; Cong Zhang; Lu Yao; Ling-Ling Tan (Archives of Microbiology, 2026)

New cutting tool wear testing method for evaluating the influence of foam additive on plowing effect during shield TBM tunnelling in dense sandy gravel ground - Shao-Hui Tang; Xiao-Ping Zhang; Quan-Sheng Liu; Yu-Cong Pan; Wei-Qiang Xie; Xin-Fang Li; Hao-Jie Wang (Tunnelling and Underground Space Technology, 2026)

Nonlinear drivers of canopy and surface urban heat islands across China’s climate zones: marginal and interaction effects from explainable machine learning - Cong Wen; Ali Mamtimin; Haitao Wang; Yu Wang; Haotong Liu; Hajigul Sayit; Meiqi Song; Jiacheng Gao; Ailiyaer Aihaiti; Yisilamu Wulayin; Fan Yang; Chenglong Zhou; et al. (Sustainable Cities and Society, 2026)

Exploring sustainable pathways and strategies for China’s “Shan-Shui” ecological restoration initiatives - Tao Liu; Le Yu; Xin Chen; Yanshu Liu; Cong Ou; Zhengrong Du; Zhouyuan Li; Dailiang Peng (Science Bulletin, 2026)

2-Nonanol enhances the resistance against Penicillium expansum in postharvest ‘Huangguan’ pear via coordinated phenylpropanoid and antioxidant pathways - Cong Song; Yang Zhang; Qian Zhao; Yu Zhang; Dan Li; Zhenhua Jia; Shuishan Song; Junfeng Guan (Postharvest Biology and Technology, 2026)

RlTTG1 isolated from Rosa laevigata Michx. regulates trichome development and stress response in transgenic Arabidopsis - Sinian Wu; Lisha Song; Yixi Chen; Cong Luo; Lingyun Wan; Guojian Liao; Wenjing Liang; Shugen Wei; Cuihong Yang; Yujian Huang; Ying Wei; Shixin Feng; et al. (Plant Science, 2026)

Numerical investigation of cavitation and vortex evolution characteristics in a hull-propeller-rudder coupled system - Chao Wang; Yi-Ming Hu; Cong Sun; Yu Zhao; Yang Han; Lian-Zhou Wang; Jia-Xiu Cao (Ocean Engineering, 2026)

Selenylation enhances anti-melanogenic activity of polysaccharide from Cinnamomum cassia Presl. by regulating the CREB/MITF/tyrosinase pathway - Qi-Cong Chen; Ya-Li Wang; Yu Luo; Yan-Ling Zhang; Wen-Xin Li; Wei-Feng Cai; Qian Ni; Cui-Ping Jiang; Qiang Liu; Chun-Yan Shen (Food Research International, 2026)

EGCG–selenocysteine nanoparticles inducing ferroptosis and apoptosis in tumor cells - Ziqi Cao; Wendong Qi; Yue Li; Xin Cong; Dejian Huang; Song Zhu; Shangwei Chen; Ruipeng Yu (Food Bioscience, 2026)

Experimental investigation on dynamics and flow resistance of granular-fluid flows - Cong-jiang Li; Yu-xiang Hu; Hong-yu Luo; Jie-yuan Zhang; Hai-Bo Li; Jia-wen Zhou (Engineering Geology, 2026)

Unlocking iron-chromium flow batteries: Conquering kinetics and crossover for affordable grid storage - Jiaxin Meng; Guozhen Zhang; Weizhai Bao; He Liu; Cong Guo; Jingfa Li; Feng Yu; Linlin Yang; Aishui Yu (Chemical Engineering Journal, 2026)

Observed and modeled interactions between atmospheric pollutants and urban thermal environment in an arid city: Urumqi as a case study - Cong Wen; Yu Wang; Ali Mamtimin; Jian Peng; Hajigul Sayit; Jiali Feng; Meiqi Song; Jiacheng Gao; Ailiyaer Aihaiti; Junjian Liu; Yisilamu Wulayin; Chenglong Zhou; et al. (Atmospheric Environment, 2026)

Biogeochemical cycling of carbon and nitrogen in terrestrial-aquatic interfaces: Mechanisms, driving factors, and eco-environmental significance - Wei Guo; Weiping Tang; Liyuan Sang; Xu Zhang; Wenhong Wang; Anji Li; Yunchao Lang; Xinchu Wang; Hu Ding; Guang-Hui Yu; Cong-Qiang Liu (Science China Earth Sciences, 2026)

From copper transport to cuproptosis: emerging therapeutic targets in cardiovascular disease - Xiaobing Zhang; Jiawen Liu; Cong He; Yu Wang; Qianyue Ni; Yabin Zhou; Jing Sun (Molecular and Cellular Biochemistry, 2026)

Suspect screening strategy reveals that illegal addition of drugs to fishery inputs is the main cause of drug residue problems in quality and safety of aquatic products in China - Hongyu Li; Haiyan Zhang; Zhongquan Jiang; Guangxin Yang; Cong Kong; Yu Li; Xiaosheng Shen (Aquaculture, 2026)

The transcriptional regulatory module MdERF2-MdSCR11 promotes ABA-mediated apple fruit ripening through synergistic repression of MdABA4-2 - Miaomiao Wang; Qizhe Li; Hao Wang; Nan Jiang; Jiale Wang; Xiaotong Hu; Yu Liu; Tuanhui Bai; Jian Jiao; JiangLi Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

A novel salt-tolerant purple photosynthetic bacterium Afifella marina TC201-1 for sustainable treatment of saline aquaculture wastewater - Shuai Liang; Kai-Hua Geng; Ding-xian Xu; Ya-Juan Wang; Wei-Yu Du; Yun-Feng Liu; Ya-Nan Lu; Li Wang; Yuan Wang; Jing Gu; Yu-Ting Cong; Lian-Shun Wang; et al. (Journal of Water Process Engineering, 2026)

Accelerated degradation of antibiotics via UV irradiation in the presence of chlorite: roles of reactive species, degradation pathways, and toxicity - Yu-qiong Gao; Xue-ting Ren; Yang-yang Liu; Ju-xiang Chen; Fu-xiang Tian; Nai-yun Gao; Cong Li (Journal of Water Process Engineering, 2026)

Methane production enhancement from anaerobic digestion of waste activated sludge with corn straw-derived biochar: Insights into the roles of tubular and lamellar structures - Shi-Yu Gao; Wen Hu; Lijuan Gao; Cong-Cong Tang; Xiao-Yan Chen; Ai-Juan Zhou; Wentao Li; Wenzong Liu; Zhang-Wei He (Journal of Water Process Engineering, 2026)

Built-in electric field promoted self-sufficient piezo-photo-Fenton tandem catalysis with in-situ H2O2 production for degradation and disinfection - Zhenyue Yu; Luhui Li; Jiaxing Xie; Gaolei Dong; Min Gao; Cong Lin; Yi Lin; Yong Wu; Xiaojing Huang; Xinan Chen (Journal of Environmental Chemical Engineering, 2026)

Combined effect of soda residue and dyeing sludge on mechanical properties and microstructural characterization of low-alkali activated GGBS - Dongyang Tian; Hua Jiang; Zedong Qiu; Xinyu Cong; Weixuan Zhao; Hesong Jin; Jing Yu; Shuang Lu (Journal of Environmental Management, 2026)

Nd-doped MgO-based adsorbent performance for CO2 capture - Xuehua Zhang; Zexin Zhao; Yan Zhu; Zhenfeng Wang; Chenliang Zhou; Gewen Yu; Yanming Wang; Cong Wang; Jian Ding; Xiaohui Guo; Yuqing Wang (Journal of Environmental Chemical Engineering, 2026)

The alleviating effects of vitamin B6 and choline on β-lactoglobulin Maillard reaction: Insight into the mechanisms via mass spectrometry and interaction analysis - Mengqi Wang; Sihui Wang; Cong Li; Hongjuan Li; Hongbo Li; Jinghua Yu (Food Research International, 2026)

The interactive effects of roasting degree and lipid content on the gas retention capacity in fermented oat dough - Fan Yang; Wenhua Ma; Ruige Yu; Binghua Sun; Xiaojie Qian; Cong Sun; Chong Liu; Sen Ma; Xiaoxi Wang (Food Research International, 2026)

Modulation of cobalt spin state to enhance enzyme-like activity of cobaltous oxide for colorimetric sensing analysis of phenolic compound - Zihan Xu; Ziyi Guo; Shengran Yu; Xinyi Shen; Yanqing Cong; Tong Wei; Wenming Pei; Shi-Wen Lv (Food Chemistry, 2026)

Development of a lipid bioactive-loaded bigel food system for elderly individuals with dysphagia - Lihua Jin; Shengnan Zhang; Lu Gao; Yu Shu; Cong Li; Bang Chen; Yehua Shen (Food Chemistry, 2026)

Insight into the mechanism of natural preservatives (rosmarinic acid and phytic acid) against quality deterioration of Pacific white shrimp through interactions with hemocyanin - Junpeng Zeng; Xiaowei Fan; Junyi Song; Yu Song; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2026)

Neuroprotective effects and transport characteristics of selenium-enriched protein digestion products with different selenium species - Yue Zhang; Wendong Qi; Yue Li; Song Zhu; Xin Cong; Dejian Huang; Ruipeng Yu; Shangwei Chen (Food Bioscience, 2026)

Runoff–sediment coupling in low vegetation coverage scenario: Insights from plot scale experiment in the loess environment - Yingxi Zeng; Yu Liu; Cong Wang (CATENA, 2026)

Functional reorganization of microbial ecological clusters is associated with citrus soil health enhancement under greenhouse cultivation - Chenhong Liu; Qi Zhao; Lin Zhang; Fuzhi Ke; Xuebin Xu; Senxiang Yu; Jiaping Lang; Tida Ge; Cong Wang; Haoqing Zhang (Plant and Soil, 2026)

The characterization of RUNX1-mediated macrophage polarization requires a multidimensional perspective beyond the M1/M2 binary - Lei Chen; Cong Hong; Yu Xie (Inflammation Research, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Molecular Mechanisms of Mangiferin on Neuroinflammation for Treating Major Depressive Disorder Based on Network Pharmacology and Bioinformatics Analysis - Cong-Ya Chen; Lan Lei; Xuan Yang; Yu-Fei Wang; Yi Zhang (Journal of Neuroimmune Pharmacology, 2026)

Experimental and Mechanistic Investigation on Time-Delayed Initiation of Hydraulic Fractures in Shale Under Constant Pressure Injection - Cong Huang; Yu Zhao; Yongfa Zhang; Dongping Zhou (Rock Mechanics and Rock Engineering, 2026)

Application of ENU-mediated efficient mutagenesis in breeding of the big belly seahorse (Hippocampus abdominalis) - Xiao-lei Su; Chun-yu Hou; Lin Shi; Shi-chang Zhang; Cheng-de Fan; Jie-zhou Wang; Yi-cong Ma; Wu-hong Lv; Cong Liu; Guo-dong Zheng; Kai Wang (Aquaculture, 2026)

Emerging contaminants disrupt the nitrogen cycle in coastal hydrological systems: Insights from synergistic effects of weakly-correlated emerging contaminants - Guiyao Xiong; Mengwen Liu; Xiaobin Zhu; Hao Geng; Cong Han; Yi Cheng; Yun Yang; Guangquan Chen; Xingyong Xu; Jianfeng Wu; Jinguo Wang; Nanyang Yu; et al. (Water Research, 2026)

Toughening mechanism of shield tunnel segments strengthened with BFRP-PCM composite: A numerical perspective considering interface failure - Cong Tian; Linchong Huang; Yu Liang; Weiling Gao (Tunnelling and Underground Space Technology, 2026)

Effects of urban canopy on kinematic and boundary layer structures of the landfalling Typhoon Lekima (2019) - Xiangyu Ao; Robert F. Rogers; Huan-Cong Liu; Hui Yu; Wei Huang (Urban Climate, 2026)

MdHMGB15 enhances zinc tolerance by activating multiple metal homeostasis genes in apple - Ran-Xin Liu; Ming-kun Wang; Yue-Ning Wang; Xiao-Han Qin; Ying-Xue Lv; Shan-Shan Li; Du Liu; Cong-Yu Xu; Xiao-Fei Wang (Journal of Hazardous Materials, 2026)

Seasonal dynamics and environmental regulation of pathogenic bacteria in the Weihe River Basin - Min Wang; Guofeng Yu; Yutong Zhang; Jiehui Ren; Wen Chen; Qiang Li; Peiyao Cong (Journal of Hazardous Materials, 2026)

Gold-modified hierarchical ZnO Cellulose flower-like multifunctional membrane for enhanced wastewater treatment: Multifunctional oil/water separation, solar-powered catalytic dye degradation, and antibacterial applications - Min Xu; Xun Wang; Hefeng Xu; Xinyi Zhang; Yuqing Yao; Zesheng Song; Yin Qiao; Cong Yu; Feng Liu (Journal of Environmental Sciences, 2026)

A general framework for designing and assessing sustainable and diversified cropping systems: Bridging knowledge-driven, model-aided, and participatory approaches - Zhengyuan Liang; Bowen Ma; Rui-Peng Yu; Yuewen Huo; Shingirai Mudare; Feiyu Ying; Long Li; Fusuo Zhang; Wen-Feng Cong (Field Crops Research, 2026)

Flexural behavior investigation of RC beams with FRP-reinforced 3D-printed ECC permanent formwork - Long-yu Cong; Fang Zhang; Yong-jiu Qian (Engineering Structures, 2026)

Multivariate Gaussian process regression for characterization of geo-data spatial variability from limited and non-co-located measurements - Cong Miao; Yu Wang (Engineering Geology, 2026)

From local to national networks: Evolution and drivers of interprovincial linkages of construction land use efficiency in China - Penglai Ran; Xun Jin; Amy E. Frazier; De Yu; Cong Xia; Zongnan Hu; Hongwei Hu (Environmental Impact Assessment Review, 2026)

Hetero-folded hBN/graphene with ultrahigh thermal conduction and electrical insulation for reliable thermal management - Han Zhao; Pengyu Zhang; Jingran Guo; Dizhou Liu; Shixuan Dang; Duola Wang; Hongxuan Yu; Jiali Chen; Chuanyun Song; Yuanpeng Deng; Yingde Zhao; Cong Li; et al. (Chemical Engineering Journal, 2026)

Wide pH range electrocatalytic nitrate reduction to ammonia over high-performance hollow Cu3P nanocubes - Yong-Qi Zhang; Xiao-Hui Wang; Ying Li; Cong-Cong Han; Xuan Ai; Shu-Ni Li; Yu Chen (Chemical Engineering Journal, 2026)

In-situ cultivation and process dynamics of algal-bacterial granular sludge in a continuous-flow self-circulation reactor - Wei-Kang Qi; Yu-Ge Sun; Ming-Ming Zhang; Rui Hu; Yong-Zhen Peng; Cong Wang (Bioresource Technology, 2026)

Plant and microbial interactions under different planting patterns regulate nitrogen removal in constructed wetlands - Feng-Cong Jia; Yue Zhang; Yu Han; Xing-Peng Wang; Yu-Hui Yang; Wei-Jie Wang (Bioresource Technology, 2026)

Differential cellular and humoral immune responses of the Asian citrus psyllid Diaphorina citri to its ecto- and endoparasitoids - Zhuo Yu; Liwen Feng; Mohao Xiong; Wenfeng Hu; Jun Zhong; Cong Zhang; Marylène Poirié; Jean-Luc Gatti; Bin Xia; Bin Wan (Journal of Pest Science, 2026)

Effects of adding Afifella marina on growth performance, intestinal health, and microbial community of juvenile Hippocampus abdominalis - Shuai Liang; Kai-Hua Geng; Yi Zhang; Ya-Juan Wang; Tian-Yu Lu; Tian Lan; Ya-Nan Lu; Yuan Wang; Jing Gu; Yu-Ting Cong; Li Wang; Lian-Shun Wang; et al. (Aquaculture International, 2026)

Reinforcement-Learning-Based Adaptive PID Depth Control for Underwater Vehicles Against Buoyancy Variations - Jian Wang; Shuxue Yan; Honghao Bao; Cong Chen; Deyong Yu; Jixu Li; Xi Chen; Rui Dou; Yuangui Tang; Shuo Li (Journal of Marine Science and Engineering, 2026)
Underwater vehicles performing sampling tasks often encounter significant buoyancy variations due to payload adjustments and environmental changes, which severely challenge the stability and accuracy of controllers. To address this issue, this paper proposes a hybrid control framework that integrates Proximal Policy Optimization (PPO) with adaptive PID tuning. The framework employs PPO to dynamically adjust PID parameters online while incorporating output saturation, stepwise quantization, and dead zone filtering to ensure control safety and actuator longevity. A dual-error state representation—combining instantaneous error and its derivative—along with actuator command buffering is introduced to compensate for system lag and inertia. Comparative simulations and experimental tests demonstrate that the proposed method achieves faster convergence, lower steady-state error, and smoother control signals compared to both conventional PID and pure PPO-based control. The framework is validated through pool tests and field trials, confirming its robustness under realistic hydrodynamic disturbances. This work provides a practical and safe solution for adaptive depth control of sampling-capable AUVs operating in dynamic underwater environments.

Residual load capacity of longitudinally-cracked reinforced-concrete pipe and its recovery by CIPP versus spray-mortar liners - Xue-Feng Yan; Yu-Yong Jiao; Cong Zeng; Samuel T. Ariaratnam; Zhe-Yao Zhao (Tunnelling and Underground Space Technology, 2026)

From agricultural waste to water treatment functional materials: Performance study of nano zero-valent iron loaded on ramie biochar for persulfate-activated carbamazepine degradation - Weiwei Yu; Lu Lv; Yang Liu; Cong Liu; Chuandong Tang; Yuanxin Liu; Xinyan Li; Dan Liu; Yan Luo; Ji Li (Journal of Environmental Chemical Engineering, 2026)

Research on identification, functional characteristics, and applications of milk fat globule membrane proteins - Xiaoyu Ma; Yu Wan; Xingyu Bao; Jian He; Sufang Duan; Gang Feng; Haixia Wu; Shuzhen Cheng; Cong Wang (International Dairy Journal, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Unraveling the flavor evolution mechanism in liquid-smoked rainbow trout through integrated lipidomics and flavoromics - Junpeng Zeng; Nan Meng; Xiaowei Fan; Yu Song; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2026)

Integrated multi-omics profiling of wooden breast reveals energy metabolism dysfunction and RHOA/ROCK pathway activation - Cong Ding; Meijuan Ren; Zhixuan Li; Shiqi Liu; Haoming Sun; Sijia Yu; Yiwei Chen; Xingyu Li; Qiang Niu; Bing Li; Li Li; Xiaojun Yang; et al. (Food Chemistry, 2026)

Research on the impact of resident behavior on energy consumption during the heating period of ultra-low energy buildings - Ru-Xi Ding; Jia-Ze Dai; Ying-Nan Zhang; Xiao-Ping Wu; Cong-Han Yu; Zhenfa Fan (Energy and Buildings, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Catalytic hairpin assembly-assisted dual-enhanced SERS satellite nanocomplex for ultrasensitive detection of lipopolysaccharides in injection samples - Chan Huang; Xiuying Li; Xuan Zeng; Lingzhi Chen; Huabin Zhang; Xinjie Guo; Yiqun Chang; Wenshi Huang; Yichu Nie; Tianen Zhou; Jiaqi Yu; Jun Xu; et al. (Chemical Engineering Journal, 2026)

Covalent triazine framework with synergetic multiple redox-active cores for high-performance sodium-ion batteries - Yufan Ren; Qianqian Jin; Yanbiao Ren; Hailin Cong; Yanxin Yu (Chemical Engineering Journal, 2026)

Function and mechanisms of polyethylene glycol-modified sodium acrylate-acrylamide hydrogel for microalgal biomass enrichment and purification - Cong-Cong Tang; Qiao Zhong; Yi Liu; Yong-Qi Cheng; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2026)

Advances in the preparation, cross-linking, activation and biomedical use of agarose microspheres - Wen Li; Junying Weng; Dayang Wang; Wenxue Zhao; Wenwen Ma; Hailin Cong; Bing Yu (Carbohydrate Polymers, 2026)

Revealing the overlooking role of polysulfides in sulfide-based denitrification biofilms through mathematical modeling - Yan Yang; Yu Liu; Cong Fan; Huimin Fu; Mohamed S. Mahmoud; Kang Dan; Hongxiang Chai (Bioresource Technology, 2026)

From bioprocess to market: Optimizing medium-chain carboxylate extraction for application readiness - Yiran Zhang; Aijie Wang; Yilu Sun; Xuening Zhang; Jianfeng Liu; Wen Wang; Cong Huang; Shaoping Fu; Honggang Deng; Yongping Shan; Jiadong Yu; Xufeng Yuan; et al. (Bioresource Technology, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

Iterative Downward Continuation and Modeling of the Earth’s Global Gravity Field in Ellipsoidal Harmonics - Cong Liu; Zhengtao Wang; Yu Gao; Yang Xiao (Surveys in Geophysics, 2026)

Effect of statistical uncertainty on kriging interpolation of 2D geospatial data from sparse measurements - Cong Miao; Yu Wang (Stochastic Environmental Research and Risk Assessment, 2026)
Geospatial data are often spatially varying but measured sparsely in a two-dimensional (2D) plane. Therefore, spatial interpolation methods, such as Kriging, are frequently used to estimate values at locations without measurement and quantify the associated uncertainty. However, Kriging generally requires extensive measurements to effectively divide non-stationary geospatial data into a deterministic trend and stationary residuals (i.e., detrending) and to estimate semi-variogram parameters from the detrended residuals (i.e., semi-variogram fitting). When measurements are limited, a scenario often encountered in practice, detrending might be challenging, and the estimated semi-variogram parameters inevitably contain statistical uncertainty. The statistical uncertainty may significantly affect the subsequent Kriging interpolation, but it is often ignored in practical applications of Kriging. This study develops a 2D Kriging method (SR-Kriging) that is featured by a sparse representation of covariance function from a Bayesian perspective and explicitly models both spatial variability and statistical uncertainty for interpolation of 2D geospatial data directly from sparse measurements. The proposed method requires neither detrending nor semi-variogram fitting. Both simulated and real data are used to illustrate and validate the proposed method. Results demonstrate that the proposed method directly interpolates 2D geospatial data from limited measurements, with quantified interpolation uncertainty, and explicitly accounts for statistical uncertainty. Ignorance of statistical uncertainty may lead to an underestimation of Kriging interpolation uncertainty.

Carbon emissions and population migration preferences: the impact of China’s carbon emissions and low-carbon policies on regional population migration - Pan Jiang; Ziwang Yu; Shuaiyi Lu; Lianghan Cong (Climatic Change, 2026)

Simultaneous Quantification of Coenzyme Q10 and Vitamin E in Softgel Capsules Using Validated 1H NMR Spectroscopy - Yixuan Wang; Mingming Yu; Cong Wang (Journal of Ocean University of China, 2026)

Identification of DIO2 as a Molecular Therapeutic Target for Depression in Chronic Rhinosinusitis: A Comprehensive Bioinformatics and Experimental Study - Hao Lv; Peiqiang Liu; Yunfei Wang; Jingyu Huang; Yulie Xie; Mengting Guan; Jianchao Cong; Yang Jiang; Yu Xu (Biochemical Genetics, 2026)

Amino Acid Metabolism-Related Gene Kynureninase (KYNU) as a Prognostic Predictor and Regulator of Diffuse Large B-Cell Lymphoma - Yu Zhang; Shi Feng; Liemei Lv; Cong Wang; Ran Kong; Guangcai Zhong; Na Wang; Peipei Li; Xiangxiang Zhou (Biochemical Genetics, 2026)

Fertilization and Aridity Legacies Determine Soil Microbial Necromass Persistence Across Climates - Li‐Xin Xu; Guang‐Hui Yu; Cong‐Qiang Liu; Georg Guggenberger (Global Change Biology, 2026)
Microbial necromass‐mineral interactions are vital for soil organic carbon (C) persistence, but their response to concurrent climate and fertilization legacies in croplands remains unclear. Using six long‐term field sites (27–38 years) across a pronounced aridity gradient, we show that stabilization of microbial necromass is coupled with short‐range ordered (SRO) minerals in humid zones (aridity index, AI 1.3), this correlation strongly weakens, challenging the universality of SRO‐associated C paradigms. While aridity controls mineral weathering and SRO abundance, we showed that long‐term fertilization can supersede aridity‐driven constraints on necromass C accrual. Spatial mapping of 6060 in situ μ‐FTIR spectra revealed reduced organic C transformation in outer aggregate rims under aridity, aligning with diminished microbial processing and a consequent weakening of necromass‐SRO associations. Our findings establish soil moisture as a critical regulator of fertilization‐induced ecological memory in mineral‐necromass interactions, urging climate‐tailored practices to sustain soil C resilience in water‐limited ecosystems under global aridification.

Nutrient comparisons among the three varieties Mercenaria mercenaria with different shell colors - Mei-Jie Yang; Pu Shi; Peng-Peng Hu; Shuang Liang; Yan Zou; Zhi Hu; Cong Zhou; Fan-Yu Meng; Kai Xiao; Tao Zhang; Hao Song (Aquaculture, 2026)

Mechanical and microstructural degradation of pile-surrounding mudstone induced by dynamic pile driving: A multi-scale experimental study - Jichao Yin; Xiaoyu Bai; Nan Yan; Yamei Zhang; Lin Cui; Yu Cong; Mingyi Zhang (Soil Dynamics and Earthquake Engineering, 2026)

Nanofibrous core/nanoporous sheath structured ultra–flexible ceramic aerogels for thermal superinsulation - Dizhou Liu; Cong Li; Han Zhao; Hongxuan Yu; Jingran Guo; Shixuan Dang; Duola Wang; Chuanyun Song; Yingde Zhao; Zhengli Yan; Yuanpeng Deng; Jiali Chen; et al. (Science Bulletin, 2026)

Integrated transcriptomic and physiological analysis highlights the candidate genes regulating enzymatic browning, antioxidant capacity, and lipid metabolism in pomegranate aril browning - Yawen Shen; Sen Wang; Ran Wan; Jian Jiao; Yujie Zhao; Liu Cong; Kunxi Zhang; Pengbo Hao; Yu Liu; Wanyu Xu; Miaomiao Wang; Jiangli Shi; et al. (Postharvest Biology and Technology, 2026)

Distributed penetration strategy for multi-USV based on scalable deep reinforcement learning - Zhao Zhang; Xiao Liang; Cong Chen; Dianyong Liu; Changdong Yu; Yankong Song; Wei Li (Ocean Engineering, 2026)

Dynamics of a towed cable crossing the air–water interface: Modeling and experimental validation - Yu Liu; Cong Wang; Wenzhi Yan; Yingyong Shen; Jian Bao; Lei Hou (Ocean Engineering, 2026)

Transformation of dissolved organic matter at molecular level during UV222/chlorine process - Chen-Yan Hu; Jia-Nan Chen; Ling-Mei Gao; Xiao-Cong Ma; Ming Zheng; Xi-Wei Yang; Jia-Qi Yang; Tian-Hong Qiu; Hai-Qing Ding; Zheng-Yu Dong (Journal of Water Process Engineering, 2026)

Flow separation and effective roughness height in vegetated flow - Feng-Cong Jia; Yu Han; Wei-Jie Wang (Journal of Hydrology, 2026)

A fluorescent probe based solid-state fluorophore for the detection of N2H4 and its application in environmental samples - Cong-Ping Cao; Qian Song; Chu-Yu-Hui Peng; Shuang-Xian Li; Guo-Jiang Mao; Juan Ouyang; Liufang Hu; Yongfei Li; Chun-Yan Li (Journal of Hazardous Materials, 2026)

Occurrence of beryllium and its microscale interactions with coexisting phases in beryllium-containing sludge - Xiaobo Min; Lin Yu; Yong Ke; Yunyan Wang; Wenming Zeng; Hui Xu; Yun Li; Cong Peng; Zhumei Sun (Journal of Environmental Sciences, 2026)

Bundle adjustment-based co-registration with high geolocation accuracy for UAV photogrammetry - Nan Jiang; Hai-bo Li; Cong-jiang Li; Yu-xiang Hu; Jia-wen Zhou (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Green extraction of undenatured type II collagen from goat cartilage by deep eutectic solvents: An integrated in silico and experimental study - Wei Wu; Yuhao Zhou; Jingjie Tan; Cong Wang; Mohammed Gagaoua; Rotimi E. Aluko; Zhongquan Zhao; Yongju Zhao; Yu Fu (Innovative Food Science & Emerging Technologies, 2026)

Effect of pre-oxidation with ozone and thermal dissolution on the structural features of Xiaojihan subbituminous coal: A comparative study of raw coal and derived residues - Yong Gao; Miao-Miao Jia; Qi-Yang Zhu; Ming-Wu Chen; Yu-Xing Cong; Jia-Ju Wu; Guang-Hui Liu; Yu-Hong Kang; Jin-Jun Bai; Chen Shi; Zhang-Feng Zhou; Xian-Yong Wei (Fuel, 2026)

A self-adaptive interfacial adhesive strategy for enduring flame retardancy and aging resistance of anti-aging agent-free polyurethane foam - Yan Wang; Lei He; Heng-Fei Liang; Chen Ye; Ze-Yong Zhao; Ming-Jun Chen; Yu-Zhong Wang; Hai-Bo Zhao; Cong Deng (Chemical Engineering Journal, 2026)

Mechanistic insight into N-doping-enhanced CO2 adsorption, activation and selectivity regulation in 0D 2D NT@ZIS S-scheme heterostructures - Hanwen Xu; Yu Wei; Shengjie Hao; Meiyu Cong; Zhenze Han; Taolue Liu; Mingxia Guo; Jialuo Li; Jinxuan Liu; Xin Ding; Yan Gao (Chemical Engineering Journal, 2026)

Size, change, and trajectory of the topsoil organic carbon stock in Chinese grasslands - Jinchao Kong; Cong Yu; Li Xu; Ying Li (CATENA, 2026)

Positive and negative responses of AMF community and diazotrophic community to peanut genetic diversity - Yanyan Yu; Miaomiao Li; Cong Wang; Zhongjie Sun; Xiongde Dong; Shijie Han; Junqiang Zheng (Applied Soil Ecology, 2026)

Biodiversity gains importance in sustaining ecosystem multifunctionality when beyond aridity thresholds in temperate grasslands - Yu Yang; Changchao Zhang; Mingxing Tian; Binwei Ci; Cong Liu; Yunxiang Cheng; Pujin Zhang; Hongtao Luo; Liqing Zhao; Yonghui Wang; Wenhong Ma (Agriculture, Ecosystems & Environment, 2026)

Sparse Spectrum Representation of Gaussian Process Regression for Modeling Nonstationary Geo-Data from Limited Measurements - Cong Miao; Yu Wang (Mathematical Geosciences, 2025)
Although geo-data are spatially variable, they are often measured sparsely at a limited number of locations owing to constraints in resources, time, or technology in various geoscience disciplines. Modeling of spatially varying geo-data from limited measurements is therefore necessary using methods such as Gaussian process regression (GPR). Since geo-data often exhibit nonstationary characteristics, such as complex spatial trends, GPR may require a composite kernel or covariance function that combines a nonstationary dot-product kernel and a stationary kernel to effectively model the complex spatial structure of geo-data. In geoengineering practice, however, the spatial structure of spatially varying geo-data is often unknown, posing a significant challenge in the development of a suitable composite kernel function, especially when measurement data points are limited. Additionally, estimating the hyperparameters of a composite kernel from limited measurements—particularly the length scale of the stationary kernel—is challenging. To address these challenges, this study develops a sparse spectrum representation of GPR that requires neither the construction of a composite kernel nor estimation of associated hyperparameters, enabling direct modeling of spatially varying geo-data from limited measurements. The proposed method is illustrated and validated using both simulated and real-world data. The results show that the proposed GPR improves prediction accuracy and reduces prediction uncertainty when predicting nonstationary geo-data from limited measurements.

Biofilm formation by Gallibacterium anatis depends on TolC-mediated initial attachment of cells - Zi-cong Shi; Jin-li Zhai; Jing-yue Yu; Zeng Wang; Hong-ying Liu; Xia Yang; Xin-wei Wang (The Veterinary Journal, 2025)

The topographic features and sedimentary environment potentially influenced the vegetation reconstruction in southwestern China since the MIS3 - Xiao Zhang; Yuanfu Yue; Ziyan Zhang; Liuying He; Xinmeng Yuan; Xintian Yu; Qiuchi Wan; Cong Chen; Yongjie Tang; Zhuo Zheng; Kangyou Huang (Quaternary Science Reviews, 2025)

Highly efficient degradation of sulfamethoxazole by peroxydisulfate activated with phosphoric acid-modified biochar-supported copper sulfide: Performance, mechanisms, and potential applications - Weiwei Yu; Xiyin Zheng; Xi Chen; Cong Liu; Bolin Li; Lu Lv; Yuanxin Liu; Ji Li; Xinyan Li; Yan Luo; Dan Liu; Shiling Chen (Journal of Environmental Chemical Engineering, 2025)

Comparing the effects of pre-deposited and pre-mixed anion exchange resin on algal fouling during ultrafiltration - Cong Ma; Miao Yu; Jun Xu; Xiangji Kong (Journal of Environmental Chemical Engineering, 2025)

Comparison of UV320/nitrate and UV222/nitrate processes in sulfadiazine degradation: Mechanism and radical roles - Chen-Yan Hu; Ling-Mei Gao; Jia-Nan Chen; Xiao-Cong Ma; Ming Zheng; Xi-Wei Yang; Guo-Hong Chen; Tian-Hong Qiu; Zheng-Yu Dong (Journal of Environmental Chemical Engineering, 2025)

Multi-quality attributes prediction and process parameter optimization of liquid-smoked rainbow trout by different machine learning models combined with genetic algorithm - Junpeng Zeng; Jingyi Luo; Yu Song; Xiaoming Jiang; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Research International, 2025)

A facile and stable single-system fluorescent sensor array for the quantification and discrimination of nitrofuran antibiotics - Yi-Fan Xia; Xiao-Shan Yu; Si-Tong Wen; Hou-Qun Yuan; Cong-Cong Xu; Lan Yang; Yao-Hong Wang; Hua Yu; Ling-Yi Guo; Guang-Ming Bao (Food Chemistry, 2025)

Preparation and characterization of Ag@MOF-Amomum tsaoko essential oil/waterborne polyurethane composite films for strawberry preservation - Yuyue Qin; Hongda Yu; Haiyan Chen; Yongliang Zhuang; Qiuming Liu; Rui Cui; Cong Zhang; Charles Brennan; Yuanxiang Huang (Food Control, 2025)

Energy efficiency, renewables, and electrification contribute to decarbonising the operation of residential building stock in Hong Kong - Yumin Liang; Cong Yu; Wei Pan (Energy and Buildings, 2025)

Harnessing enhanced rock weathering for carbon neutrality: potential and challenges in China - Lianghan Cong; Shuaiyi Lu; Pan Jiang; Tianqi Zheng; Yanjun Zhang; Xiaoshu Lü; Ziwang Yu; Tianfu Xu (Earth-Science Reviews, 2025)

Atomic-scale regulation of Bi2Te3 nanopores via in-situ electron beam irradiation for nanofabrication - Yuting Shen; Yu Tao; Tao Xu; Yuwei Xiong; Kuibo Yin; Yilong Zhou; Shan Cong; Litao Sun (Chemical Engineering Journal, 2025)

Enhanced Carrier Collection by Controlling Element Distribution in Kesterite Solar Cells through Se&SnS2 Co-annealing process - Yali Sun; Zihang Liu; Jiahui Ma; Xiao Liu; Ridong Cong; Qing Zhou; Wanlei Dai; Xiaoyun Teng; Chao Gao; Wei Yu; Dongliang Ding (Chemical Engineering Journal, 2025)

Designing light-guiding carriers in microalgal-bacterial systems: From optimization to integration and development perspectives - Cong-Cong Tang; Jin-Qiao Liu; Yong-Qi Cheng; Ya-Ru Hu; Zhang-Wei He; Wen-Qiong Wang; Zhi-Hua Li; Xiaochang C. Wang; Yu Tian (Chemical Engineering Journal, 2025)

A binary-medium-based multiscale constitutive model for stabilized expansive soil considering the influence of freeze-thaw cycles - Cong Chen; Yunyong He; Bo Xiang; Enlong Liu; Yanyang Yu (Cold Regions Science and Technology, 2025)

Green approaches for modifying lignocellulosic features: Recent advances in reducing recalcitrance for sustainable bioethanol production - Muhammad Adnan; Adeel Ahmed; Muhammad Rafiq; Nasim Ullah; Ali Ahmad; Muhammad Sarfraz; Raza Ullah; Muzamil Ahmad; Bing Yu; Hailin Cong (Biomass and Bioenergy, 2025)

Recent progress in the microbial production of Xylanase - Shoufeng Wang; Mingming Zhao; Yu Zheng; Hualan Zhou; Wenjie Cong; Jianguo Zhang (World Journal of Microbiology and Biotechnology, 2025)

Comparative analysis of sexual dimorphism in ultrastructure of sensilla on antennae, frons, and compound eyes of Azpeytia shirakii Hurkmans (Diptera: Syrphidae) - Bin Mao; Yu-Hui Cong; Ming-Hui Wang; Han-Rui Ren; Yun-Li Xiao (Zoomorphology, 2025)

Effects of Multi-Step-Ahead Prediction Strategies on LSTM-Based Runoff Prediction - Jingchao Jiang; Yang Gao; Jiaqi Chen; Jingzhou Huang; Juan Yu; Cong Jiang; Junzhi Liu; Anke Xue (Water Resources Management, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Temporal and spatial dynamics of drought in the Amur River Basin under climate change: observed trends, future projections, and driving mechanisms - Yanhui Zhang; Lei Wang; Ming Li; Wen J. Wang; Jinyuan Ren; Shanfeng Xing; Yu Cong (Climate Dynamics, 2025)

Competent expression of effective and long-acting human α-Gal A-Fc fusion protein in the milk of transgenic mice - Mengke Yuan; Lan Yang; Chunyang Li; Zhiqiang Wu; Zhipeng Liu; Tianfei Du; Xinzong Rong; Cong Cong; Yongxia Zhang; Xiaoping Yu; Yali Gao; Zhengli Chen; et al. (Transgenic Research, 2025)

Dual-branch Fusion Network Integrating Multispectral Time Series and Hyperspectral Data for Precise Mapping of Liaohe River Delta Wetland, China - Haoyang Yu; Kaizhen Zhou; Lianru Gao; Jiaxin Wang; Pifu Cong; Jiaochan Hu (Chinese Geographical Science, 2025)

Wetland Loss Offsets Climate Change Benefits on Ecological Security Network in Songnen Plain, Northeast China - Jinyuan Ren; Wenjuan Wang; Lei Wang; Long Fei; Guanghui Shao; Yuhong Li; Shanfeng Xing; Yu Cong (Chinese Geographical Science, 2025)

Permeability properties in water-saturated sandstone under graded cyclic loading and unloading - Abi Erdi; Zeng Qifu; Yuan Hechuan; Cong Yu; Liu Mingwei; Zhang Jie; Jiang Mingjing (Arabian Journal of Geosciences, 2025)

Promising mass spectrometry imaging: exploring microscale insights in food - Xinyu Cao; Peixu Cong; Yu Song; Yanjun Liu; Changhu Xue; Jie Xu (Critical Reviews in Food Science and Nutrition, 2025)

Neonatal personality is linked to trappability in a large mammal - Cong Yu; Bawan Amin; Anna David; Simone Ciuti (Animal Behaviour, 2025)

Corrigendum to “Susceptibility, resistance risk and sublethal effect to fenmezoditiaz, a novel mesoionic insecticide, in the brown planthopper, Nilaparvata lugens” [ Pesticide Biochemistry and Physiology 213 (2025) 106540] - Yan-Chao Zhang; Xiao-Yan Song; Yu Li; Zi-Xin Zhuang; Wen-Nan Ye; Zhao-Yu Liu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2025)

Cooperative game method of heterogeneous unmanned surface vehicles based on distributed decision-making framework - Cong Chen; Xiao Liang; Zhao Zhang; Dianyong Liu; Changdong Yu; Wei Li (Ocean Engineering, 2025)

Late Triassic ultrahigh-temperature mafic granulite from the North Dabie terrane, Central China - Heng-Cong Lei; Hai-Jin Xu; Hui Zhang; Fei Xia; Cong-Jun Yu; Wang-Chao Li; Liang-Peng Deng; Ling Wang; Jian-Bing Duan (Lithos, 2025)

pH-responsive polymers: classification, response mode, properties and biomedical applications - Dayang Wang; Huanchen Yao; Jiashuo Ye; Ziyan Wang; Hailin Cong; Bing Yu (Chemical Engineering Journal, 2025)

Sensitive colorimetric assay for the detection of aflatoxin B1 via target-induced generation of multivalent DNA nanowires accelerates the catalytic hairpin assembly reaction - Shihong Zhang; Yingying Sun; Xingyu Liu; Cong Chen; Yuhan Ma; Dian Yu; Wenjie Liu; Jianna Yu; Guoxing Jing; Wen Liu; Wenshan Li (Analytica Chimica Acta, 2025)

Comparative analysis of feed efficiency in Pacific abalone and its hybrid under varied environmental conditions - Wenchao Yu; Ziheng Yin; Yuehan Yan; Lin Cong; Miaoqin Huang; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture International, 2025)

Overlooked influence of phosphate on the performance of a dual membrane process with coagulation pretreatment - Cong Ma; Zixiang Zhang; Lei Xu; Sajid Rashid; Guibai Li; Nigel Graham; Wenzheng Yu (Water Research, 2025)

Synergistic charge separation and magnetic recovery in a noble-metal-free Fe3O4/TiO2/Bi photocatalyst for bromate reduction - Ying Xu; Shuili Yu; Zhiqiang Fan; Xingli Ji; Cong Huang; Zheng Xu; Rui Liu; Chao Jiang (Journal of Water Process Engineering, 2025)

Flow structure and spectral characteristics in regions with highly flexible vegetation - Feng-Cong Jia; Yu Han; Wei-Jie Wang; Jin-Jin Li; Zhen Zhao; Jia-Yu Du (Journal of Hydrology, 2025)

Bismuth nanospheres enabling sacrificial-agent-free bromate photoreduction and total bromine mitigation for safer water treatment - Ying Xu; Shuili Yu; Zhiqiang Fan; Cong Huang; Lei Li; Rui Liu; Zheng Xu (Journal of Hazardous Materials, 2025)

Process and mechanism of low-temperature molten salt roasting conversion of beryl ore: Towards low-energy-consumption beryllium smelting - Lin Yu; Xiaobo Min; Hui Xu; Yunyan Wang; Yulin Zhou; Zhou Liao; Yun Li; Zhiyan Zeng; Yibin Xie; Cong Peng; Yong Ke (Journal of Environmental Chemical Engineering, 2025)

Regulating ROS for highly efficient conversion of furfural to valuable organic acids in CoZnO catalyst - Yifan Yang; Qixin Zhang; Lijian Wang; Junjie Bian; Cong Yu; Xinbo Wang (Journal of Environmental Chemical Engineering, 2025)

Biochar-activated peracetic acid for the degradation of emerging contaminants - Shi-Yu Gao; Cong-Cong Tang; Ai-Juan Zhou; Zhaobo Chen; Wenzong Liu; Yong-Xiang Ren; Zhi-Hua Li; Zhang-Wei He (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Enhanced moisture tolerance and toluene oxidation activity of δ-MnO2 catalysts by Sn doping: Phase transition and surface protection - Yiming Li; Mengxia Xu; Rui Liu; Shuibo Wang; Taotao Sun; Zijun Yan; Cong Wan; Hongbo Yu; Haocheng Li; Haotian Li; Xudong Zhao; Kaijie Li; et al. (Fuel, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Flavor controlled release behavior from novel high internal phase Pickering emulsion gels stabilized by zein-chitin nanocrystals complex coacervates: The models on phase equilibria and mass transfer - Lei Lei; Can-hua Xu; Cai-hong Zhu; Yu-cong Zou; Yu-xi Guo; Mahoudjro David Bodjrenou; Bin Zhang; Yang Yuan (Food Hydrocolloids, 2025)

Screening of an antibacterial peptide with high antibacterial activity against superbugs and its application in the treatment of skin wound infections - Shengjie Zhang; Yayun Zhu; Jiaxin Zou; Min Zhang; Xiaohua Li; Yumei Wang; Xuezhen Ma; Hailin Cong; Bing Yu (Chemical Engineering Journal, 2025)

Hydrogen plasma-induced uniform grain boundary engineering in Cu(In, Ga)Se2 thin films for high efficiency large area solar panels - Zeran Gao; Jiaxin Guo; Zihan Guo; Shanshan Tian; Wanlei Dai; Ridong Cong; Yali Sun; Chao Gao; Xinzhan Wang; Wei Yu (Chemical Engineering Journal, 2025)

Quantum effect modulates the Bi-Ov active sites of S-scheme heterojunction for efficient CO2 photoreduction to CH4 - Hanwen Xu; Shengjie Hao; Meiyu Cong; Zhenze Han; Taolue Liu; Jialuo Li; Yu Wei; Mingxia Guo; Xin Ding; Jinxuan Liu; Yan Gao (Chemical Engineering Journal, 2025)

Mesenchymal Stem Cells Derived from Different Adipose Tissue Depots Ameliorate Severe Acute Pancreatitis by Inhibiting NF-κB/NLRP3/Caspase-1 Pathways - Ao Wang; Yu An; Xuefei Wang; Wenfeng Gou; Feifei Xu; Yanli Li; Cong Wang; Zhengwei Tu; Wenbin Hou; Yunfeng Cui (Stem Cell Reviews and Reports, 2025)

Microglia in the Rostral Ventromedial Medulla Mediate Synaptic Pruning via the C1q/C3-CR3 Signaling Pathway—A Mechanism for the Chronic Orofacial Pain - Xilu Huang; Jie Zeng; Zhanwei Hu; Yujia Wu; Guangyan Zhang; Chao Zhang; Cong Yu; Min Song (Molecular Neurobiology, 2025)

Geochronology, Geochemical and Sr-Nd-Pb Isotope of Syenites in the North Daba Mountains, South Qinling Belt: Constraints on Petrogenetic Evolution and Tectonic Implication - Hang Yang; Shao-Cong Lai; Jiang-Feng Qin; Fang-Yi Zhang; Ren-Zhi Zhu; Yu Zhu; Min Liu; Shao-Wei Zhao; Zhen Yang (Journal of Earth Science, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Subduction-induced crustal growth in the Neoproterozoic continental magmatic arc: Evidence from arc-type high-Mg# diorites and adakitic granitoids in the western Yangtze Block, South China - Rui-Yang Liu; Shao-cong Lai; Yu Zhu; Ren-Zhi Zhu; Min Liu; Jiang-Feng Qin; Fang-yi Zhang; Hang Yang (Precambrian Research, 2025)

Susceptibility, resistance risk and sublethal effect to fenmezoditiaz, a novel mesoionic insecticide, in the brown planthopper, Nilaparvata lugens - Yan-Chao Zhang; Xiao-Yan Song; Yu Li; Zi-Xin Zhuang; Wen-Nan Ye; Zhao-Yu Liu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2025)

Saleucanes A-J, structurally diverse neo-clerodane diterpenoids from Salvia leucantha with anti-neuroinflammatory activity via TLR4/MYD88/NF-κB pathway - Fen-Cong Pan; Han-Fei Liu; Xiao-Die Shu; Xiao-Qiao Yang; Hua-Yong Lou; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2025)

Optimizing strip clear-cutting regimes for carbon sequestration and maintaining ecosystem health in Cryptomeria japonica plantations - Siyu Song; Zhangming Wu; Cong Li; Yu Zhou; Yamei Chen; Junxi Hu; Xinglei Cui; Lihua Tu; Asma Atta; Pleasure Chisom Ajayo; Youyou Huang; Xinhua He; et al. (Journal of Environmental Management, 2025)

Sulfide-driven denitrification process for low C/N ratio wastewater treatment - Chao Wang; Cong Yu; Sen Qiao (Journal of Environmental Management, 2025)

Effect of pulsation frequencies on the fracture characteristics of CO2 foam fractured coal: An experimental study - Yangfeng Zheng; Cheng Zhai; Aikun Chen; Hexiang Xu; Xinyu Zhu; Shuxun Sang; Meng Wang; Shiqi Liu; Xu Yu; Jizhao Xu; Yong Sun; Yuzhou Cong; et al. (Gas Science and Engineering, 2025)

Salting-induced lipid hydrolysis and oxidation in dried squid fillets: A mechanistic link to formaldehyde formation, color browning, and flavor alteration - Junpeng Zeng; Xiaowei Fan; Nan Meng; Yanjun Liu; Yu Song; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Corrigendum to “Auricularia polytricha and Flammulina velutipes ameliorate inflammation and modulate the gut microbiota via regulation of NF-κB and Keap1/Nrf2 signaling pathways on DSS-induced inflammatory bowel diseases” [Food Bioscience 47 (2022) 101426] - Ivan St'eve Nguepi Tsopmejio; Miao Ding; Jiali Wei; Cong Zhao; Yu Jiang; Yuting Li; Hui Song (Food Bioscience, 2025)

Dielectric elastomer with covalently charged interpenetrated polyacrylate network for large actuation strain under low driving electric field - Yingying Zhang; Zhiyuan Song; Wei Yu; Cong Wang; Changshuai Dong; Jindan Wu; Liangru Shi; Pengchao Yao; Wenjing Yuan; Chuizhou Meng; Shijie Guo (Chemical Engineering Journal, 2025)

Novel degradable piezoelectric-induced PHBV/CS/HA scaffolds to achieve dual effects of endogenous osteogenesis and antibacterial properties by piezoelectric stimulation and ultrasonic action - Cong Yang; Meilin Zhao; Ning Yu; Sen Wang; Yuanqiang Li; Hang Chen; Yan Xiong; Xiaonan Zhang; Ping Ji (Chemical Engineering Journal, 2025)

Patterns and drivers of soil organic carbon fractions and persistence in coastal wetlands of China - Lele Wu; Zhaoliang Song; Xinyu Zhang; Yuan Guo; Yidong Wang; Changxun Yu; Yunying Fang; Iain P. Hartley; Ji Chen; Shaopan Xia; Xiaoguang Ouyang; Wenhai Mi; et al. (CATENA, 2025)

Speciation distribution and phase partition laws of rare alkali metals in geothermal sinter deposits in southern Tibet: Implications for the cesium mineralisation in the geothermal system - Zhiwei Shi; Hongbing Tan; Peixin Cong; Fei Xue; Hongkai Zhu; Yu Zhang (Chemical Geology, 2025)

Aurantibrevibacter litoralis gen. nov. sp. nov. a Novel Member in the Family Flavobacteriaceae Isolated from Sediment of Tidal Flat Located in Ningbo, China - Yun-Fei Cao; Dong-Yan He; Yu-Ruo Wang; Ke Cao; Yang Li; Jia-Wei Gao; Xing-Cheng Wang; Lin Xu; Cong Sun; Xiao-Yun Yu (Current Microbiology, 2025)

Microplastics Induce Structural Color Deterioration in Fish Poecilia reticulata Mediated by Oxidative Stress - Hong-Yu Ren; Huan-Chao Ma; Rui-Peng He; Cong-Cong Gao; Bin Wen; Jian-Zhong Gao; Zai-Zhong Chen (Fishes, 2025)
Microplastics (MPs) can affect fish health by inducing oxidative stress, but their impact on structural coloration remains poorly understood. This study investigated the effects of environmentally relevant concentrations (16 and 160 μg/L) of MPs and nanoplastics (NPs) exposure on growth, oxidative stress and structural coloration in blue strain guppy fish (Poecilia reticulata). Results showed exposure to 160 μg/L MPs significantly reduced specific growth rate of fish compared to controls. Plastic accumulation followed a dose-dependent pattern, especially within gut concentrations. Oxidative stress responses differed between MPs and NPs: 160 μg/L MPs decreased SOD activity in skin and reduced GSH levels, while 160 μg/L NPs increased MDA levels in gut tissues, indicating severe lipid peroxidation. Structural coloration analysis revealed exposure to 160 μg/L MPs decreased lightness and increased yellowness, demonstrating reduced blue coloration. This was accompanied by an increase in skin uric acid content, suggesting that guanine conversion might occur to combat oxidative stress. These findings demonstrate that MPs, particularly at high concentrations, impair growth and induce oxidative stress in guppies. To counteract stress, guanine in iridophores may be converted into uric acid, leading to a decline in structural coloration. This study is the first to reveal that MPs disrupt structural coloration of fish, providing new insights into the ecological risks of plastic pollution on aquatic organisms.

Evaluating the green development level of marine molluscan shellfish aquaculture industry and analyzing obstacle factors that hinder its improvement: The case of China - Runsheng Pei; Hongzhi Zhang; Zifei Liu; Cong Yu; Yingxue Zhang; Yongtong Mu (Aquaculture, 2025)

Deciphering the synergistic effects and mechanisms of biochar and magnetite contained in magnetic biochar for enhancing methane production in anaerobic digestion of waste activated sludge - Hong-Yu Jin; Yong-Xiang Ren; Cong-Cong Tang; Shuai Zhang; Jiabin Wang; Ai-Juan Zhou; Bin Liang; Wenzong Liu; Aijie Wang; Zhang-Wei He (Water Research, 2025)

Settlement-based triple factor framework for long-term safety assessment of immersed tunnel - Shu-Yu He; Cong Tang; Mi Pan; Wan-Huan Zhou (Tunnelling and Underground Space Technology, 2025)

Break-off and stagnation of the subducting Nazca slab in the mantle transition zone beneath West-Central South America - Kailun Ba; Jianping Huang; Youqiang Yu; Jianguo Song; Sanzhong Li; Cong Shen; Lin Liu (Tectonophysics, 2025)

Protocatechualdehyde improves cyclophosphamide-induced premature ovarian insufficiency by inhibiting granulosa cell apoptosis and senescence through the SIRT1/p53 axis - Cong Feng; Yue Jiang; Yi Wang; Yuehui Zhang; Yu Liu; Jia Li (Reproductive Toxicology, 2025)

Research on vector layout of ducted propellers for remotely operated vehicle - Cong Xue; Yu Dai; Jize Jiang; Guanghao Ren; Defa Wu (Ocean Engineering, 2025)

Hollow cavity engineering of MOF-derived hierarchical nitrogen-doped In2O3@carbon for efficient photocatalytic degradation of tetracycline hydrochloride - Raza Ullah; Muhammad Rafiq; Alamgir; Abdul Qadir; Adeel Ahmed; Muhammad Fayaz; Muhammad Adnan; Nasim Ullah; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2025)

Energy-saving low-frequency vibration-assisted riveting process for joining high-strength metallic structures with enhanced performance - Cong Shao; Jun Lin; Congxiao Yu; Yanjin Guan; Liang Chen; Xiangshan Kong; Cunsheng Zhang; Guoqun Zhao (Journal of Cleaner Production, 2025)

The driving effect of marine industries on marine pollution: Empirical evidence from coastal China - Cong Yu; Zifei Liu; Xianghui Kong; Runsheng Pei; Wanchanok Umprasoet; Yongtong Mu; Jun Xu (Journal of Cleaner Production, 2025)

Interaction effects and threshold analysis of enterprise digital service innovation on environmental performance: Evidence from interpretable machine learning models - Pan Jiang; Ziwang Yu; Shuaiyi Lu; Lianghan Cong (Journal of Cleaner Production, 2025)

Mowing mitigates the enhancement of nitrogen enrichment on grassland insect herbivory - Yuan-Xiu Wu; Cong Ding; Bing-Chuan Zhang; Xiao-Sa Liang; Yu Ning; Jiang-Xia Yin; Xiao-Tao Lü (Journal of Environmental Management, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

Exploring the impact of short-term weak static magnetic field stimulation on the metabolite profiles and metabolic pathways of fresh-cut young ginger based on HS-GC-IMS and UHPLC-MS/MS - Cong-cong Xu; De-kun Liu; Yun-ying Lv; Chun-Yu Ni (Food Chemistry, 2025)

Impacts of sex and gestation on bioaccumulation and transfer of per-and polyfluoroalkyl substances in loaches - Cong Wang; Yonglong Lu; Bin Sun; Ruoyu Mao; Meng Zhang; Shuai Song; Mingzhao Yu; Jixin Zhao (Environmental Research, 2025)

Accelerating enrichment of ARGs and MGEs with increasing ammonium removal during partial nitrification treating high-strength ammonia wastewater - Heng Yu; Weiyi Jia; Yuqiu Luo; Rong Zhang; Junkai Zhao; Cong Lu; Yue Dong; Shuo han; Bing Li; Chengtun Qu (Environmental Research, 2025)

Damage evolution and toughening mechanism of shield tunnel segments strengthened by epoxy-bonded thin plates considering interface effects - Cong Tian; Linchong Huang; Yu Liang; Weiling Gao (Computers and Geotechnics, 2025)

Genomic insights into the brooding reproduction and climate-driven dynamics of Pocillopora damicornis in the Anthropocene - Jie Li; Yali Liu; Zhixin Zhang; Yu Chen; Jian Zhang; Haiyan Yu; Yingyi Zhang; Cong Liu; Zhuang Shao; David G. Bourne; Meng Qu; Si Zhang; et al. (Science China Life Sciences, 2025)

Structural characteristics and immunomodulatory activity of an exopolysaccharide from Antarctic Pseudoalteromonas sp. LP6-12-2 - Dezhi Wang; Han Li; Yu Zhao; Bailin Cong; Pengying Zhang (Extremophiles, 2025)

Prolonged mantle metasomatism in the Neoproterozoic continental arc: Insights from mafic magmatism in the western Yangtze Block, South China - Zhe-hao Zhong; Shao-cong Lai; Yu Zhu; Jiang-feng Qin; Ren-zhi Zhu; Min Liu; Yu-hong Xia (Acta Geochimica, 2025)

Energy consumption and quality improvement of frozen pork using NaCl refrigerant with three amino acids in contact immersion freezing - Yu Zhou; Qiong Pan; Wen Li; Lifang Zou; Qing-fei Du; Wu Wang; Cong-gui Chen (Meat Science, 2025)

Diquat exposure causes brainstem demyelination by upregulating the mitochondrial calcium uniporter - Jie Zhou; Yingli Yang; Jiacheng Tian; Cong Liu; Jiafei Chen; Mei Yang; Mengran Zhang; Yu Duan; Tian Zhang; Yapei Sun; Qin Yu; Zhiqin Xia; et al. (Journal of Hazardous Materials, 2025)

Preparation, identification and application of lipid-Maillard reaction products during the drying process of squid fillets - Junpeng Zeng; Xiaowei Fan; Yanjun Liu; Yu Song; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Contriving molecular configuration to realize a bidirectionally stable quasi-solid polymer electrolyte for high-voltage Li metal batteries - Silin Chen; Shunchao Ma; Yu Zhang; Yanan Li; Yutong Yang; Shuainan Wang; Jianli Cao; Siqi Fan; Liqun Sun; Yulong Liu; Lina Cong; Haiming Xie (Chemical Engineering Journal, 2025)

RNA sequencing reveals circular RNA expression patterns in chronic intermittent hypoxia - Cong Li; Tiantian Su; Yuqin Chen; Lei Yue; Yu Zhang; Song Shi; Wenjia Wei (Sleep and Biological Rhythms, 2025)

Spatiotemporal variations in potential evapotranspiration in the Yellow River and Yangtze River Basins under changing environments: impacts on runoff and their causes - Lu Jia; Kunxia Yu; Zhanbin Li; Peng Li; Peijuan Cong; Binbin Li; Guoce Xu; Yuxiao Wang; Yuanguo Ding (Irrigation Science, 2025)

Bacteria in the Phylum Bacillota Degrade Nicotine Through the Variant of Pyridine and Pyrrolidine Pathway - Xiu-Ming Liu; Xuan Hai; Cong-Jian Li; Yu-Fan Han; Xing Chen; Yu-Jin Fan; Jian Wu; En-Min Zhou; Yuan-Dong Li; Ling-Ling Yang; Yan-Qing Duan; Xiao-Yang Zhi (Current Microbiology, 2025)

Disruptions of white matter in adolescents with internet game disorder: evidence from seed-based d mapping - Hao Zheng; Chunyu Dong; Yu Wan; Hailong Shen; Sen Li; Shanling Ji; Jian Cui; Kun Li; Hao Yu; Chuanxin Liu; Cong Zhou (Brain Imaging and Behavior, 2025)

Collaborative Scheduling of Yard Cranes, External Trucks, and Rail-Mounted Gantry Cranes for Sea–Rail Intermodal Containers Under Port–Railway Separation Mode - Xuhui Yu; Cong He (Journal of Marine Science and Engineering, 2025)
The spatial separation of port yards and railway hubs, which relies on external truck drayage as a necessary link, hampers the seamless transshipment of sea–rail intermodal containers between ports and railway hubs. This creates challenges in synchronizing yard cranes (YCs) at the port terminal, external trucks (ETs) on the road, and rail-mounted gantry cranes (RMGs) at the railway hub. However, most existing studies focus on equipment scheduling or container transshipment organization under the port–railway integration mode, often overlooking critical time window constraints, such as train schedules and export container delivery deadlines. Therefore, this study investigates the collaborative scheduling of YCs, ETs, and RMGs for synchronized loading and unloading under the port–railway separation mode. A mixed-integer programming (MIP) model is developed to minimize the maximum makespan of all tasks and the empty-load time of ETs, considering practical time window constraints. Given the NP-hard complexity of this problem, an improved genetic algorithm (GA) integrated with a “First Accessible Machinery” rule is designed. Extensive numerical experiments are conducted to validate the correctness of the proposed model and the performance of the solution algorithm. The improved GA demonstrates a 6.08% better solution quality and a 97.94% reduction in computation time compared to Gurobi for small-scale instances. For medium to large-scale instances, it outperforms the adaptive large neighborhood search (ALNS) algorithm by 1.51% in solution quality and reduces computation time by 45.71%. Furthermore, the impacts of objective weights, equipment configuration schemes, port–railway distance, and time window width are analyzed to provide valuable managerial insights for decision-making to improve the overall efficiency of sea–rail intermodal systems.

A new β-caryophyllene type sesquiterpenoid pentoside with nine known compounds from the aerial parts of Biebersteinia heterostemon as a α-glucosidase inhibitor in vitro - Yu-hao Zhang; Deng-yi Du; Ruo-fei Bai; Cong-wei Zhou; Zi-jian Zhao; Shan-shan Yang (Phytochemistry Letters, 2025)

Simulations on the trajectory and attitude of supercavitating vehicles with a general three-dimensional algorithm - Yiguo Li; Cong Wang; Wei Cao; Haiyu Xu; Qian Yang; Delei Yu (Ocean Engineering, 2025)

Hetero-atom-doped biochar as a sustainable catalyst for value-added upgrading of lignin derivatives: Optimizing dopant for enhancing conversion - Vo Thi Thanh Thuy; Hua-Chen Wu; Yu-chih Tsai; Ta Cong Khiem; Yi-Feng Lin; Ha Manh Bui; Yiu Fai Tsang; Kun-Yi Andrew Lin (Journal of Environmental Chemical Engineering, 2025)

Basalt mineralization with soda saline soil for enhanced CO₂ sequestration: An experimental study - Lianghan Cong; Ziwang Yu; Jianguo Kang; Shuaiyi Lu; Pan Jiang; Tianqi Zheng; Xiaoshu Lü (Journal of Environmental Chemical Engineering, 2025)

Protective effect of selenium-enriched protein from Cardamine violifolia digestion products on PC12 cells injury induced by Aβ1-42 - Wendong Qi; Yue Zhang; Xin Cong; Dejian Huang; Ruipeng Yu; Shangwei Chen; Song Zhu (Food Bioscience, 2025)

Corrigendum to “A chitosan derivative-crosslinked hydrogel with controllable release of polydeoxyribonucleotides for wound treatment” [Carbohydrate Polymers 300 (2023) 120298] - Yanzhen Sun; Xiaodong Jing; Yang Liu; Bing Yu; Hao Hu; Hailin Cong; Youqing Shen (Carbohydrate Polymers, 2025)

Effects of thinning on soil water content and water use characteristics of artificial forest in the Loess Plateau of China - Yu Liu; Yue Li; Guangyao Gao; Lei Jiao; Zongshan Li; Zhaolin Li; Cong Wang; Di Wang; Lide Tian; Bojie Fu (CATENA, 2025)

Long-term characteristics of formaldehyde concentrations in four Chinese residences and estimation of annual average - Jin Ye; Zhiyuan Wang; Tao Yu; Wenbin Zhuang; Wenqing Lai; Lei Tian; Wenjun Leng; Ying Song; Shaodan Huang; Yinping Zhang; Cong Liu; Bencheng Lin (Building and Environment, 2025)

An EXPAR-CRISPR/Cas12a Assay for Rapid Detection of Salmonella - Wensen Lin; Mintao Huang; Hongjian Fu; Luxin Yu; Ying Chen; Lingwei Chen; Yanzhen Lin; Ting Wen; Xiaomin Luo; Yanguang Cong (Current Microbiology, 2025)

Cortical thickness alternation in obsessive-compulsive disorder patients compared with healthy controls - Chunyu Dong; Hao Zheng; Hailong Shen; Yu Wan; Yinghong Xu; Ying Li; Liangliang Ping; Hao Yu; Chuanxin Liu; Jian Cui; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2025)

Impacts of cascade dam construction on riparian vegetation in an alpine region - Yihang Wang; Nan Cong; Yu Zhong; Yongshuo Fu; Nan Wang; Lijian Ouyang; Weiwei Yao (Journal of Hydrology, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Highly efficient multifunctional 3D polyurethane sponge with photothermal responsiveness for efficient oil-water separation and microplastic extraction - Ritong Wang; Zuozhu Yin; Guoyan Yang; Qidong Zha; Cong Xiong; Yu Xie; Jilin Xu; Yidan Luo; Zhen Hong; Chan Xie; Mingshan Xue (Desalination, 2025)

Knitted forming material with a lock-ring structure for individual puncture protection - Xuliang Yu; Ting Su; Xinhua Liang; Honglian Cong; Haijun He; Gaoming Jiang; Pibo Ma (Chemical Engineering Journal, 2025)

A near-infrared responsive hydrogel loaded with Prussian blue-based nanocarriers for CO gas therapy of infected wounds - Yao Li; Zhixue Zhang; Haoran Jiang; Zheng Zhuang; Hailin Cong; Bing Yu; Kai Wang; Hao Hu (Chemical Engineering Journal, 2025)

Dual-channels engineering of carbon tube/NiCo-LDH composites for enhanced ion diffusion and electron transfer - Qiuhong Bai; Xiaoyan Wang; Yu Zhang; Yan Wang; Cong Li; Yang Wang; Xiaoheng He; Yehua Shen; Hiroshi Uyama (Chemical Engineering Journal, 2025)

Reprocessable bio-based rubber with hierarchical hydrogen bonding: A sustainable solution for high strength, superior extensibility, and recyclability - Wei-Chen Zhou; Xue-Qin Gao; Jia-Hao Li; Gui-Lin Hu; Yu-Zhong Wang; Cong Deng (Chemical Engineering Journal, 2025)

Anti-ferroptosis effects of undescribed abietane diterpenoids from Prunella vulgaris subsp . hispida (Benth.) Hultén - Heng-Li Yan; Xiao-Qiao Yang; Han-Fei Liu; Fen-Cong Pan; Jin-Yu Li; Wei-Dong Pan; Ni Zhang; Hua-Yong Lou; Chao Sun (Natural Product Research, 2025)

Identification of circRNA-Based Biomarkers and ceRNA Mechanism in Non-Small Cell Lung Cancer - Zhengjia Liu; Xiyu Liu; Cong Yin; Zihao Liu; Haixiang Yu (Cell Biochemistry and Biophysics, 2025)

A novel index for mapping crop residue covered cropland using remote sensing data - Wenqian Zhang; Wenjuan Li; Cong Wang; Qiangyi Yu; Huajun Tang; Wenbin Wu (Computers and Electronics in Agriculture, 2025)

Provincial resilience differences of water cycle in China over the past two decades - Bin Liu; Wei Pan; Cong Yu; Pankaj Kumar; Yifan Chen; Jingjing Li (Resources, Conservation and Recycling, 2025)

Collaborative chasing strategy of unmanned surface vehicles in complex obstacle environments - Cong Chen; Xiao Liang; Zhao Zhang; Dianyong Liu; Changdong Yu; Wei Li (Ocean Engineering, 2025)

Effects of triclosan on microalgal-bacterial symbiosis system operating in stable phase: Performances and mechanisms - Qiang Chao; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian (Journal of Water Process Engineering, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Dual-functionally N-doped porous carbon synthesized from Liquidambaris fructus and melamine-formaldehyde resin for high-performance CO2 adsorption and supercapacitors - Jialong Geng; Yu Shu; Jiage Ma; Ziyi Pang; Renbo Yao; Qidong Wang; Cong Li; Bang Chen; Yehua Shen (Chemical Engineering Journal, 2025)

Regulating the growth mechanism of kesterite thin films with single-target selenium-free annealing by introducing a suitable buried buffer layer at the bottom - Qing Zhou; Yijia Cong; Tingchun Wu; Hao Li; Junhui Hei; Xinzhan Wang; Xiaobing Yan; Yali Sun; Chao Gao; Wei Yu (Chemical Engineering Journal, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

Global Soil Methane Uptake Estimated by Scaling Up Local Measurements - Jiawei Jiang; Zhifeng Yan; Jinshi Jian; Shushi Peng; Hanqin Tian; Kendalynn A. Morris; Robert M. Ellam; Jesper Riis Christiansen; Huai Chen; Jianzhi Dong; Si‐Liang Li; Pingqing Fu; et al. (Global Change Biology, 2025)
Aerobic soils remove methane from the atmosphere, but global soil methane uptake (SMU) estimates remain highly uncertain due to challenges in scaling local data. We develop a data‐driven approach to refine this global estimate by incorporating local data of 79,800 flux measurements from 198 sites. This novel approach links the global SMU budget to local SMU fluxes by varying its parameters with soil properties. Our 2003–2018 global SMU estimate is ~39.0 Tg CH 4 year −1 —about 30% higher than existing bottom‐up estimates and consistent with top‐down assessments. Cold grasslands and deserts were found to contribute nearly 30% of the total SMU, while disturbed agricultural biomes have the lowest SMU. The projected future global SMU is shaped by temperature and atmospheric methane, though local SMU is primarily influenced by changes in soil moisture. This study emphasizes the potential of soils in climate regulation and highlights the need to focus on key biomes for a better understanding of the soil‐atmosphere methane feedback and optimizing methane management strategies.

Regional abnormalities of white and gray matter in youths with conduct problems - Man Dong; Xiaodong Cheng; Yage Li; Shanling Ji; Hao Yu; Liangliang Ping; Chuanxin Liu; Cong Zhou (Brain Imaging and Behavior, 2025)

Polysaccharide metabolic pattern of Cytophagales and Flavobacteriales: a comprehensive genomics approach - Kuo-Jian Ma; Yong-Lian Ye; Yu-Kang Li; Ge-Yi Fu; Yue-Hong Wu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2025)
The complete metabolism of carbohydrates, as the most abundant and structurally diverse organic matter on earth, requires the involvement of different carbohydrate-active enzymes (CAZymes). Flavobacteriales and Cytophagales are two groups whose members specialize in polysaccharide metabolism, but research on their polysaccharide metabolic patterns based on the overall CAZymes is scarce. In this study, we analyzed 702 filtered genomes of Flavobacteriales and Cytophagales and obtained 100,445 CAZymes. According to their taxonomic status and living environment, we explored the impact of taxonomic status, isolation source, and environmental condition on their potential polysaccharide metabolic patterns. The results indicated significant differences in the CAZyme composition among different taxonomic statuses or environments. Compared with the Flavobacteriales genomes, the genomes of Cytophagales possess more abundant and diverse CAZymes, but have fewer unique CAZyme families. Genomes from different families vary greatly in terms of CAZyme family diversity and composition, but relatively small divergences were found from families in the same order. Furthermore, our findings indicated that genomes from the marine and tidal flat environments share more similarities in CAZyme family composition and diversity compared with the terrestrial genomes. Extreme environments greatly constrain the types of CAZyme families present, and certain CAZyme families are significantly lower than those in normal environments. Although significant differences were found among genomes from both different taxonomic statuses and environments, the dimensionality reduction and the clustering analysis based on CAZyme composition indicated that evolutionary status is the main factor influencing the polysaccharide metabolic patterns of these strains. The correlations among CAZyme families indicated that the majority of these families are synergistically involved in polysaccharide metabolism. This study provides a comprehensive profile of the CAZymes in Flavobacteriales and Cytophagales, highlighting the role of evolutionary status in shaping the polysaccharide metabolic patterns and the prevalence of synergism among CAZyme families. These findings have implications for understanding microbial carbohydrate metabolism in different environments.

Sus scrofa RNase L inhibits PRRSV replication by activation of type I IFN signaling pathway and apoptosis - Xiangju Wu; Xiaoyan Cong; Ping Jiang; Mingming Zhou; Ying Yu; Dandan Jiang; Yue Hu; Juntong Li; Jinxia Zhang; Ying Cao; Haowen Zhang; Yijun Du; et al. (Veterinary Microbiology, 2025)

Longitudinal deformation mechanism of shield tunnels caused by erosion voids in the underlying soil - Cong Tian; Linchong Huang; Yu Liang (Tunnelling and Underground Space Technology, 2025)

A flexible framework for built-up height mapping using ICESat-2 photons and multisource satellite observations - Xiayu Tang; Guojiang Yu; Xuecao Li; Hannes Taubenböck; Guohua Hu; Yuyu Zhou; Cong Peng; Donglie Liu; Jianxi Huang; Xiaoping Liu; Peng Gong (Remote Sensing of Environment, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Numerical investigation of shear effects between seafloor sediment and grousers of deep-sea mining vehicles: a comparison of bionic buffalo hoof grousers and straight grousers - Gen Li; Junlin Zhao; Manhong Li; Xuguang Chen; Zhou Li; Andi Yu; Cong Ding; Zhongtao Wang; Long Yu (Ocean Engineering, 2025)

The vegetation response to MIS5 and MIS1 as revealed by pollen data from the Pearl River estuary, China - Shaohua Yu; Fang Chen; Kangyou Huang; Yang Zhou; Qing Zhu; Cong Wu; Chang Zhuang; Kaijun Cao; Lu Yamin; Jinpeng Zhang; Zhuo Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Highly efficient degradation of norfloxacin by using Co3O4-CeO2 as a heterogeneous catalyst through peroxymonosulfate activation: Characterization, catalytic performance and mechanism - Muhammad Rafiq; Raza Ullah; Adeel Ahmed; Xin Liu; Muhammad Usman; Qinghua Cao; Muhammad Adnan; Muhammad Fayaz; Waqas Haider; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2025)

Harmless treatment of cyanide tailings by functional bacteria: Degradation of cyanide and the secondary pollutant ammonia nitrogen - Chongzhe Chi; Ye Zheng; Yujia Shi; Cong Lyu; Xiangzheng Jiang; Yu Zhang; Chunhui Wang (Journal of Hazardous Materials, 2025)

Developing a Ni-grafted magnetic nanoparticle for direct CotA capture in rapid detoxification of aflatoxin B1 - Chengyu Zhang; Danni Wang; Cong Wang; Huijuan Yu; Peng Zhong; Weifan Dang; Yufan Yang; Yuefei Wang; Xiaohui Yan (Journal of Hazardous Materials, 2025)

Green and low-carbon matrices for Engineered/Strain-Hardening Cementitious Composites (ECC/SHCC): Toward sustainable and resilient infrastructure - Ling-Yu Xu; Jing Yu; Bo-Tao Huang; Jian-Cong Lao; Hao-Liang Wu; Xi Jiang; Tian-Yu Xie; Jian-Guo Dai (Journal of Cleaner Production, 2025)

Digestive characteristics of Se-enriched proteins with different Se species and its effects on gut microbiota during in vitro APP/PS1 mice colonic fermentation - Yue Zhang; Wendong Qi; Xin Cong; Dejian Huang; Ruipeng Yu; Shangwei Chen; Song Zhu (Food Research International, 2025)

Insight into the mechanism of Maillard reaction and lipids mutually contribute to the flavor release of squid fillets during the drying process - Junpeng Zeng; Nan Meng; Yu Song; Xiaowei Fan; Xiaoming Jiang; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2025)

Reliability analysis of soil slope stability considering spatial variability of desiccation cracks - Qian-Feng Gao; Xin-Yang Wu; Ling Zeng; Hui-Cong Yu; Xue-Ke Shi (Computers and Geotechnics, 2025)

Defective Zn1-xCuxS nanosheet as efficient and durable cathode catalyst for photo-assisted Li-O2 batteries - Cong-Cong Dang; Yi-Ping Liu; Yu-Xin Huang; Xin-Yi Zhang; Zhen-Yi Gu; Jun-Ming Cao; Jin-Zhi Guo; Li-Ming Gao; Xing-Long Wu; Yi-Chun Liu (Chemical Engineering Journal, 2025)

Synergistic induction of immunogenic cell death by icaritin, JQ1, and doxorubicin to enhance immunotherapy in hepatocellular carcinoma - Wei Pan; Fengyuan Gao; Huinan Wang; Yuanyuan Guo; Muhammad Rafiq; Hailin Cong; Youqing Shen; Bing Yu (Chemical Engineering Journal, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Nim(Mo3S11)n derived from Ni2+ ions complexing [Mo3S13]2− loading on nickel foam to realize synergy of adsorption and PMS activation - Yue Li; Tingting Song; Conghui Wang; Lele Qiu; Cong Li; Xiang Yu; Gang Qin; Longlu Wang (Chemical Engineering Journal, 2025)

Aridity‐Driven Non‐Linear Shift of Plant Sodium Allocation Strategy at Regional and Global Scales - Hongbo Guo; Jiahui Zhang; Xiaoyan Kang; Cong Yu; Nianpeng He (Global Ecology and Biogeography, 2025)
Aim Plants allocate sodium (Na) to leaves and roots as an adaptation to salinity and drought, potentially modulating herbivory and ecosystem carbon cycling. However, large‐scale spatial patterns and environmental drivers of plant Na allocation remain unclear. Location China and the world. Time Period Field data were collected between 2013 and 2019. Literature data were collected between 1970 and 2024. Major Taxa Studied Vascular plants. Methods We compiled a global database of paired leaf Na (Na Leaf ) and root Na (Na Root ) content, combining field observations from 2183 species across 72 Chinese ecosystems with globally synthesised literature records. Results The spatial pattern of plant Na allocation between leaves and roots is primarily regulated by aridity. Generally, plants allocate more Na to roots in humid zones but more to leaves in arid zones. Furthermore, aridification leads to abrupt and non‐linear increases in the Na Leaf to Na Root ratio (Na Leaf:Root ) when aridity exceeds the critical threshold (0.814 for the Chinese plant species and 0.774 for the Chinese plant community). Importantly, the threshold response is consistently observed from species to community levels and from China to global biomes. Main Conclusions Our findings demonstrate the flexible allocation of plant Na in response to salinity and drought on a large scale. Projected aridification could amplify leaf Na allocation in threshold‐exceeding regions, possibly enhancing the activity of herbivores and decomposers and triggering cascading impacts on plant community structure and carbon cycling rate.

Increased miRNA-375 causes oxidative damage but promotes apoptosis resistance and cell migration in the clam Ruditapes philippinarum - Ming Cong; Zhaoshun Li; Wenwen Tian; Yixian Yu; Yu Che; Jiasen Lv (Frontiers in Marine Science, 2025)
MicroRNA is an important regulatory factor at the post-transcriptional level. Previous miRNAomics analysis found that miRNA-375 was steadily upregulated in the clam Ruditapes philippinarum upon ammonia nitrogen exposure. However, we have no knowledge about its regulatory mechanism yet. In this study, the clams were challenged by the injection of miRNA-375 mimics/inhibitor in vivo . Then, a combined approach of qRT-PCR, enzyme assay, and ultrastructure observation was applied to investigate its regulatory effects on the related genes, cellular parameters, and histological structures, respectively. Results showed that increased expression of miRNA-375 interfered with the expression levels of both its target genes and ammonia toxicity-related genes, which would probably lead to oxidative stress, migration of damaged cells, apoptosis resistance, and increased possibility of tumor formation. In addition, miRNA-375 increased MDA content but decreased glutamate content and caused serious structure damage to the clam gills. Thus, increased miRNA-375 probably brings a disastrous fate to the clam R. philippinarum by inducing oxidative damage but promoting apoptosis resistance and cell migration. Overall, this study revealed for the first time the regulatory effects of miRNA-375 in the clams and gave valuable clues to understand the toxicological mechanisms of ammonia nitrogen on the marine bivalve.

A novel microfluidic colorimetric biosensor for rapid and automatic detection Escherichia coli O157:H7 in aquaponics water - Zhuangzhuang Bai; Bingxiong Wang; Tingyao Gao; Xianbao Xu; Zhuangzhuang Du; Jie Han; Yang Hu; Yu Bai; Liu Wang; Cong Wang; Daoliang Li (Computers and Electronics in Agriculture, 2025)

PbSO4 reaction mechanism in oxygen and reduction atmospheres during co-smelting process with primary lead material - Yunyan Wang; Maixin Yu; Yu Liu; Xiaobo Min; Zelong Huang; Cong Peng; Yong Ke; Pingsheng Zeng; Xingwu Lu; Yun Li (Waste Management, 2025)

Assessment of CO2 fluxes in the hinterland of the Gurbantunggut Desert and its response to climate change - Ali Mamtimin; Gulnur Amar; Yu Wang; Jian Peng; Hajigul Sayit; Jiacheng Gao; Kun Zhang; Meiqi Song; Ailiyaer Aihaiti; Cong Wen; Fan Yang; Wen Huo; et al. (Journal of Environmental Management, 2025)

The growth and nutrient removal properties of heterotrophic microalgae using volatile fatty acids under different nitrogen forms and its application in actual acid-producing wastewater - Cong Jia; Na Liu; Lei Chen; Wenbao Yan; Qi Zhao; Jie Li; Ze Yu; Mingming Song; Chongqing Xu; Xiaozhe Song (Journal of Environmental Chemical Engineering, 2025)

Photocatalytic hydroxylation of benzene by platanus acerifolia fruit-derived KOH-activated porous biocarbon loaded with iron-based MOFs - Xuetong Xu; Xu Jia; Jiaolong Qiao; Cong Liu; Liuxue Zhang; Ziyu Duan; Guomin Yu; Xiulian Wang (Journal of Environmental Chemical Engineering, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Lipid-involved browning mechanism during the drying process of squid - Junpeng Zeng; Yu Song; Xiaowei Fan; Yanjun Liu; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Experimental analysis on breaching mechanism of earth-rock dam induced by landslide generated waves - Zhen-han Du; Jia-Wen Zhou; Shi-Chen Zhang; Qi-Ming Zhong; Hai-Bo Li; Yu-Xiang Hu; Cong-Jiang Li; Jie-Yuan Zhang (Engineering Geology, 2025)

Electronic configuration of carbon regulated by Mo2C clusters encapsulated in nitrogen self-doped biochar for efficient hydrogen evolution reaction - Chengyu Zhang; Fabrice Ndayisenga; Cong Wang; Zhisheng Yu (Chemical Engineering Journal, 2025)

Design and biomedical application of Cr3+-doped gallate near-infrared persistent luminescence nanoprobes - Jie Gao; Lin Yuan; Yu Min; Mengyu Cao; Hetong Zhu; Jiaqi Hong; Bing Yu; Hailin Cong (Chemical Engineering Journal, 2025)

Temperature-sensitive ionic hydrogels for dual electric and thermal responsive smart window - Li-Li Zhao; Xiao-Lei Shi; Cong-Huan Huang; Meng-Ling Zou; Ming-Yu Liang; Jie Liang; Shi-Min Kang; Lei Miao; Zhi-Gang Chen (Chemical Engineering Journal, 2025)

Dynamics of microbial communities and organic carbon pools in karst wetland soils - Yutian Xiao; Congyu Cheng; Aoqi Cheng; Weihua Kang; Taiming Shen; Qingrong Yang; Cong Peng; Longjiang Yu; Wei Li (CATENA, 2025)

Efficient Solutions for Forward Modeling of the Earth's Topographic Potential in Spheroidal Harmonics - Cong Liu; Zhengtao Wang; Fupeng Li; Yu Gao; Yang Xiao (Surveys in Geophysics, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Contribution of fungal biomass to persistent soil carbon across natural ecosystems - Xiang Wang; Guang-Hui Yu; Yakov Kuzyakov; Bo-Hao Yin; Andreas Kappler; Cong-Qiang Liu (Science China Earth Sciences, 2025)

Voriconazole Steady-State Trough Concentrations and Clinical Outcomes in Patients with Talaromycosis - Zhiwen Jiang; Cong Song; Bingkun Li; Xiuying Li; Xiaoshu Yu; Siru Zhou; Tiantian Li; Qihua Huang; Nanfang Mo; Xiaojuan He; Qian Pang; Zhijian Yao; et al. (Mycopathologia, 2025)

Iron-modified biochar for enhanced removal of ciprofloxacin and amoxicillin in wastewater - Sumita; Yong Wang; Jianping Yu; Cong Li (Environmental Chemistry Letters, 2025)

Petrogenesis of late Cretaceous high Ba–Sr granodiorites, SE Lhasa block, China: implications for the reworking of juvenile crust and continental growth - Li-Hang Lin; Ren-Zhi Zhu; Shao-Cong Lai; Jiang-Feng Qin; Yu Zhu; Shao-Wei Zhao; Min Liu (Acta Geochimica, 2025)

A Systematic Review on Atmospheric Ozone Pollution in a Typical Peninsula Region of North China: Formation Mechanism, Spatiotemporal Distribution, Source Apportionment, and Health and Ecological Effects - Miao Zhang; Yu Liu; Xiaojuan Xu; Jun He; Dongsheng Ji; Kai Qu; Yang Xu; Chunhua Cong; Yuesi Wang (Current Pollution Reports, 2025)

Genomic determinants of biological age estimated by deep learning applied to retinal images - Yu Huang; Mohammad Ghouse Syed; Ruiye Chen; Cong Li; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Shulin Tang; Jing Liu; Shunming Liu; Sundar Srinivasan; et al. (GeroScience, 2025)
With the development of deep learning (DL) techniques, there has been a successful application of this approach to determine biological age from latent information contained in retinal images. Retinal age gap (RAG) defined as the difference between chronological age and predicted retinal age has been established previously to predict the age-related disease. In this study, we performed discovery genome-wide association analysis (GWAS) on the RAG using the 31,271 UK Biobank participants and replicated our findings in 8034 GoDARTS participants. The genetic correlation between RAGs predicted from the two cohorts was 0.67 ( P = 0.021). After meta-analysis, we found 13 RAG loci which might be related to retinal vessel density and other aging processes. The SNP-wide heritability ( h 2 ) of RAG was 0.15. Meanwhile, by performing Mendelian randomization analysis, we found that glycated hemoglobin, inflammation hemocytes, and anemia might be associated with accelerated retinal aging. Our study explored the biological implications and molecular-level mechanism of RAG, which might enable causal inference of the aging process as well as provide potential pharmaceutical intervention targets for further treatment. Graphical Abstract

Assessing vegetation dynamics and human impacts in natural and urban areas of China: Insights from remote sensing data - Yuan Zou; Wei Chen; Siliang Li; Tiejun Wang; Le Yu; Xiao Zhang; Min Xu; Bohan Jiang; Chunying Wu; Ramesh P. Singh; Alfredo Huete; Cong-Qiang Liu (Journal of Environmental Management, 2025)

Generation of Neoproterozoic granites of the Huangling batholith in the northern Yangtze Block, South China: Implications for the evolution of the Precambrian continental crust - Wen-Bin Xue; Shao-Cong Lai; Yu Zhu; Jiang-Feng Qin; Ren-Zhi Zhu; Min Liu; Hang Yang (Journal of Asian Earth Sciences, 2025)

Synthesis of piceid lipoate and the effect and micro-mechanism of alpha-lipoic acid moiety on its antioxidant activity - Hai-Xia Xu; Na-Na Zheng; Yu-Cong Zou; Qing-Feng Zhang (Food Research International, 2025)

Evaluation of physicochemical quality, specific aromatic characteristic, and volatile organic compound profile of fresh-cut coriander leaves under different super-atmospheric oxygen modified atmosphere packaging conditions - Chun-yu Ni; Xing-lu Sun; Hui-na Dong; Cong-cong Xu (Food Packaging and Shelf Life, 2025)

Advances in the discovery, mechanism of action, optimization of activity and potential for clinical application of antimicrobial peptides - Yumei Wang; Hailin Cong; Youqing Shen; Bing Yu (Chemical Engineering Journal, 2025)

Synthesis and screening of polytetrahydropyrimidine polymers with synergistic antibacterial and anti-inflammatory effects - Xiaohua Li; Taimin Xu; Chunxiao Li; Bing Yu; Hailin Cong (Chemical Engineering Journal, 2025)

Maackiain: A comprehensive review of its pharmacology, synthesis, pharmacokinetics and toxicity - Waqas Haider; Wei Pan; Dayang Wang; Waqas Niaz; Muhammad Kashif Zaman; Raza Ullah; Shakir Ullah; Muhammad Rafiq; Bing Yu; Hailin Cong (Chemico-Biological Interactions, 2025)

Feedstock optimization with low carbon to nitrogen ratio during algal sludge aerobic composting: Quality and gaseous emissions - Hainan Wu; Chengkai Wang; Jiahui Zhou; Haibing Cong; Yu Gao; Wei Cai; Shaoyuan Feng; Chi Zhang (Bioresource Technology, 2025)

Pollution Characteristics and Risk Assessment of Heavy Metals in Rural Road Dust for Preschool Children in Baiyin, a Long-Term Polluted Area of NW China - Huilin Gu; Ziyi Wang; Jinglei Zhang; Shun Chen; Yue Du; Ting Yu; Cong Yuan; Shiwei Ai (Water, Air, & Soil Pollution, 2025)

Identification of genetic loci and candidate genes underlying Fusarium crown rot resistance in wheat - Yuqing Su; Xiangru Xu; Yunqiao Wang; Tongzhu Wang; Jiazheng Yu; Jiatian Yang; Jinlong Li; Yutian Gao; Yixin Wang; Wei Sang; Cong Li; Xingyi Wang; et al. (Theoretical and Applied Genetics, 2025)

Initiation Pressure and Fracture Path of Near-Field Symmetric Pre-cut Hydraulic Fracturing - Qian Yu; Yuemao Zhao; Xingdong Zhao; Shuyuan Liu; Yu Cong; Huaibin Li; Hongmo Zhu; Tianqi Jiang; Juncai Cao; Song Zhang (Rock Mechanics and Rock Engineering, 2025)

Experimental study on regular wave breakage and nonlinear characteristics on the terrain of steep coral islands and reefs - Wei Li; Tingqiu Li; Min Yu; Xuyi Fang; Cong Liu; Wenjun Zhou (Natural Hazards, 2025)

Bone marrow mesenchymal stem cell transplantation protects rats from myocardial infarction by regulating TXNIP/NLRP3 pathway-mediated inflammation and fibrosis - JianNan Bai; Cong Wang; HongQiang Yu; QingChao Wang; JinFeng Zhang; DanDan Shao; ZhiQiang Yu; Bo Meng; You Li (Molecular & Cellular Toxicology, 2025)

Causal relationship between dyslipidemia and diabetic neuropathy: a mendelian randomization study - Cong Li; Yu Feng; Lina Feng; Mingquan Li (Metabolic Brain Disease, 2024)

Habitat changes of a small endemic euryhaline fish species in the northern margin of the South China Sea under the background of global warming - Jian Liao; Hao Chen; Jia-Yu Li; Gao-Cong Li; Xian Guan; Cai-Feng Liang; Yu-Song Guo; Zhong-Dian Dong; Zhong-Duo Wang (Frontiers in Marine Science, 2024)
Hainan medaka ( Oryzias curvinotus ) is a small euryhaline fish species native to the northern margin of the South China Sea. Our long-term field observations indicate a concerning decline in its wild resources. Climate change, an uncontrollable factor, has altered the species’ distribution pattern. In this study, we simulated the shifts in the species range of O. curvinotus during the Last Glacial Maximum (LGM), current, and the next one hundred year, and analyzed its habitat attributes. The results demonstrate that bio2 (mean diurnal range of temperature) is a crucial factor in shaping the species range of O. curvinotus . The simulation results reveal that the current habitats are located in the coastal areas of northern Vietnam, the northeastern Hainan Province, the coastal areas of Guangdong Province and Guangxi Zhuang Autonomous Region, and a few areas in Taiwan Province of China, covering a total area of 17.82×10 4 km 2 . Highly suitable habitats are mainly concentrated in the coastal areas of Hai Phong, Nam Dinh, and Thanh Hoa in northern Vietnam, the central part of Leizhou Peninsula, and the west coast of the Pearl River Estuary. For the tropical species Hainan medaka, the impact of the LGM was relatively minor, and there were extensive suitable habitats during historical times, including three refugia. Currently, only Refugium 2 near Guanghai Town, Taishan County, Jiangmen City, Guangdong Province in China remains, while the other two refugia have submerged below sea level. Future climate warming under different carbon emission levels is projected to cause a short-term expansion, followed by a relief in expansion. By 2100, the potential habitat area of O. curvinotus is slightly larger than the current scenario. It is noteworthy that under future climate warming scenarios, the highly suitable habitats will not migrate northward but will expand near the 21°N latitude. Overall, Hainan medaka is not expected to be threatened in the future. Our study provides long-term dynamic distribution data, which provides a theoretical basis for the long-term development and conservation management of Hainan medaka.

Optimization of vegetation carbon content parameters and their application in carbon storage estimation in China - Cong Yu; Li Xu; Nianpeng He; Mingxu Li; Xiaoyan Kang (Science of The Total Environment, 2024)

Experimental and numerical simulation study on the dissipation mechanism of landslide-generated waves through multiple barrier structures - Yu-xiang Hu; Cong-jiang Li; Hai-bo Li; Da-rui Liu; Jia-wen Zhou (Ocean Engineering, 2024)

Research on layout optimization for propellers of a submarine operation vehicle - Long Xiao; Yu Dai; Cong Xue; Wei-Bin Ma; Cheng-Long Liu (Ocean Engineering, 2024)

Biogeochemical process governing cadmium availability in sediments of typical coastal wetlands driven by drying-wetting alternation - Cheng-Cheng Jiang; Guang-Hui Yu; Xiao-Jie Zhou; Fu-Sheng Sun; Cong-Qiang Liu (Journal of Hazardous Materials, 2024)

CeO2 enhanced performance of NiFe2O4-CaO for carbon capture and in-situ hydrogenation conversion to CO - Yu Fan; Bowen Lu; Xinyu Zhi; Cong Luo; Liqi Zhang (Journal of Environmental Chemical Engineering, 2024)

Topography alters the optimum timing of peatland initiation across Northeast China during the Holocene - Yakun Chen; Zicheng Yu; Lei Xu; Guoping Wang; Jinxin Cong; Dongxue Han; Chuanyu Gao (Global and Planetary Change, 2024)

Revealing assembly mechanisms of algal communities in aquatic microniches: Shifts in diversity patterns, microbial interactions and stability along nutrient gradients - Xiaoxu Zheng; Maoting Wang; Xiaoxuan Liu; Shengjun Xu; Shuanglong Ma; Jinglin Wang; Cong Wang; Aibin Zhan; Pingfeng Yu; Dongsheng Wang; Yi He; Cancan Jiang; et al. (Environmental Research, 2024)

Ultra-capacity and low-cost P3-type K0.5Mn0.96Fe0.04O2 cathode materials for K-ion batteries - Jun Cong; Shao-hua Luo; Yi-cheng Lin; Peng-yu Li; Li-xiong Qian; Sheng-xue Yan; Xin Liu; Xue-fei Lei (Chemical Engineering Journal, 2024)

A novel variant (p.A524P) in Spastin is responsible for a Chinese family with hereditary spastic paraplegia - Yu-Han Jin; Yang-Ziyu Xiang; Mei-Fang Zhao; Yi-Hui Liu; Liang-Liang Fan; Xiao-Cong Li (Molecular Biology Reports, 2024)

Tripartite-motif 3 represses ovarian cancer progression by downregulating lactate dehydrogenase A and inhibiting AKT signaling - Yu Cong; Xin Cui; Yaqian Shi; Xinxing Pan; Ke Huang; Zhe Geng; Pengfei Xu; Lili Ge; Jin Zhu; Juan Xu; Xuemei Jia (Molecular and Cellular Biochemistry, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Identification and culture of functional salivary gland ductal epithelial cells - Han-Shu Zhang; You-Wei Zhao; Xin-Yi Tao; Xin Cong; Li-Ling Wu; Guang-Yan Yu; Yan Zhang (Histochemistry and Cell Biology, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

Towards ecological civilization: Spatiotemporal heterogeneity and drivers of ecological quality transitions in China (2001–2020) - Jiaxing Xin; Jun Yang; Huisheng Yu; Jiayi Ren; Wenbo Yu; Nan Cong; Xiangming Xiao; Jianhong (Cecilia) Xia; Xueming Li; Zhi Qiao (Applied Geography, 2024)

Biogenic silica dynamics in coastal wetland sediments: A key driver of silicon and carbon biogeochemical cycling - Xiangwei Zhao; Zhaoliang Song; Yuntao Wu; Lukas Van Zwieten; Laodong Guo; Changxun Yu; Zimin Li; Lele Wu; Xiaomin Yang; Xiangbin Ran; Jun Sun; Yuqiu Wei; et al. (Limnology and Oceanography, 2024)
Biogenic silica (biogenic Si) is a bioactive component crucial for the biogeochemical cycling of Si in terrestrial and aquatic ecosystems. Its formation and dissolution dynamics are intricately linked to carbon (C) cycling. However, knowledge about the source, composition, and factors controlling the distribution of biogenic Si in coastal wetland sedimentary environments is still limited. To address this lack of knowledge, we introduced a suite of geometric models for biogenic Si biovolume calculation and investigated biogenic Si assemblages, along with biogenic Si and biogenic Si‐occluded C contents, in sediments from representative coastal wetlands along the west coast of Bohai Bay. Our analysis showed that sedimentary biogenic Si predominantly derived from phytoliths (78.1% ± 5.8%), diatoms (18.2% ± 4.8%), and sponge spicules (3.7% ± 2.9%). Notably, phytolith assemblages were primarily composed of forms derived from the Poaceae family. The biogenic Si‐occluded C content (0.035–1.870 g kg −1 ) within these wetland sediments was consistent across both sites, accounting for 0.97–5.71% of the total organic C pool. Structural equation modeling indicated that total organic C, pH, and amorphous aluminum oxides either directly or indirectly influenced the biogenic Si content in coastal wetlands sediments. These results demonstrate the critical role that biogenic Si plays in the Si biogeochemical cycle and provide valuable information that advances our understanding of the biogeochemical interactions between Si and C in coastal wetland ecosystems.

Integrated colon microbiome and metabolomics to elucidate the antidepressant mechanisms of the Radix Bupleuri-Radix Paeoniae Alba herb pair - Jia-le Lv; Yu Bai; Yu-e Lv; Cong-cong Chen; Xue-mei Qin; Guan-hua Du; Yu-zhi Zhou (Metabolic Brain Disease, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

The normalized difference yellow vegetation index (NDYVI): A new index for crop identification by using GaoFen-6 WFV data - Yanbing Wei; Miao Lu; Qiangyi Yu; Wenjuan Li; Cong Wang; Huajun Tang; Wenbin Wu (Computers and Electronics in Agriculture, 2024)

PbSO4 decomposition kinetic and phase transformation mechanism during lead waste recycling - Yun Li; Yu Liu; Liyuan Chai; Xin Wang; Dezhou Zhang; Yongming Chen; Yunyan Wang; Shenghai Yang; Yong Ke; Cong Peng; Pingsheng Zeng; Xingwu Lu; et al. (Process Safety and Environmental Protection, 2024)

Area-wide survey and monitoring of insecticide resistance in the brown planthopper, Nilaparvata lugens (Stål), from 2020 to 2023 in China - Wen-Nan Ye; Yu Li; Yan-Chao Zhang; Zhao-Yu Liu; Xin-Yu Song; Xin-Guo Pei; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2024)

A frequency domain analysis method for the dynamic response of a submerged floating tunnel under wave action - Mei Yu; Longfei Cong; Bin Teng (Ocean Engineering, 2024)

Enhanced activation of peroxymonosulfate by nanomagnetic CoFe2O4-CeO2/g-C3N4 composites as a heterogeneous catalyst for metronidazole degradation - Adeel Ahmed; Muhammad Usman; Muhammad Rafiq; Muhammad Adnan; Raza Ullah; Hailin Cong; Bing Yu (Journal of Water Process Engineering, 2024)

Unveiling the pathogenic and multidrug-resistant profiles of Vibrio alfacsensis: A potential identified threat in turbot (Scophthalmus maximus) aquaculture - Ren-Ge Hu; Lei Yang; Li-Yan Wang; Yu-Lin Yang; Hong-Jin Li; Bin-Tong Yang; Yuan-Huan Kang; Zhen-Lin Liang; Wei Cong (Journal of Hazardous Materials, 2024)

Contributions of the bacterial communities to the microcystin degradation and nutrient transformations during aerobic composting of algal sludge - Hainan Wu; Jiahui Zhou; Sen Zhang; Yu Gao; Chengkai Wang; Haibing Cong; Shaoyuan Feng (Journal of Environmental Management, 2024)

Additive patterns in near-infrared diffuse reflectance spectra: Implications for product formulation and analysis - Le Zhao; Youyan Liang; Nuohan Zhang; Yanbin Chang; Meijuan Fan; Cong Wang; Beibei Li; Hongbo Wang; Yu Liu; Hongxiao Yu; Song Yang; Fuwei Xie; et al. (Food Control, 2024)

Associations of multiple blood metals with cardiac structure and function: A cross-sectional study in a CAD population - Yapei Sun; Qi Mao; Denglu Zhou; Jiacheng Tian; Hang Du; Qin Yu; Jianhua Zhao; Weixia Duan; Cong Liu; Yu Duan; Jie Zhou; Tian Zhang; et al. (Environmental Pollution, 2024)

Interface-Confined nanocatalysts at hollow porous nanofibers for High-Performance cascaded remediation of radioactive wastewater - Qi-Hui Ye; Hao Ye; Yu-Cong Yu; Xiao-Lin Wang; Qiao Luo; Ming-Bang Wu; Juming Yao (Chemical Engineering Journal, 2024)

A novel antidepressant homogeneous polysaccharide YLP-1 from Millettia pulchra ameliorates tryptophan metabolism and SCFAs through modulating gut microbiota - Meng Yu; Cong-Cong Cai; Yun-Feng Huang; Yin-Di Zhu; Xin-Yao Luo; Xin-Yu Kong; Wen-Ting Zhang; Hui-Jun Li; Jing-Xian Fang; Zhong-Mei Zou (Carbohydrate Polymers, 2024)

Trichoderma gamsii, a new pathogen causing disease on cultivated mushroom Cordyceps militaris in China - Huanhuan Peng; Yunlong Cong; Yitong Zhao; Zhenghui Liu; Yu Li (Crop Protection, 2024)

Multi-output prediction for TBM operation parameters based on stacking ensemble algorithm - Yu Tang; Junsheng Yang; Yuyang You; Jinyang Fu; Xiangcou Zheng; Cong Zhang (Tunnelling and Underground Space Technology, 2024)

Organic matter composition and stability in estuarine wetlands depending on soil salinity - Lele Wu; Zhaoliang Song; Yuntao Wu; Shaopan Xia; Yakov Kuzyakov; Iain P. Hartley; Yunying Fang; Changxun Yu; Yidong Wang; Ji Chen; Laodong Guo; Zimin Li; et al. (Science of The Total Environment, 2024)

Coordination-regulated epitaxial growth for 2D/3D perovskite vertical alignment heterostructure - Guoxiang Zhao; Yuan Chen; Shan Cong; Lutao Li; Chen Wang; Xinyu Du; Ruirui Liu; Jing Lu; Yu Liu; Gaoyuan Chen; Sihan Zhang; Liya Zhang; et al. (Science Bulletin, 2024)

Contribution to energy conservation and quality improvement of frozen pork via contact/contactless immersion freezing in NaCl solution - Yu Zhou; Xia Yu; Ran Xiao; Li-fang Zou; Qing-fei Du; Fei Ma; Cong-gui Chen (Meat Science, 2024)

Mn-MOF derived N-doped MnOx@carbon heterogeneous catalysts for Vis-light, S2O82, HSO5, Vis/S2O82, and Vis/HSO5-induced degradation of metronidazole: Kinetics and mechanistic study - Raza Ullah; Muhammad Rafiq; Alamgir; Adeel Ahmed; Xin Liu; Waqas Haider; Muhammad Fayaz; Qinghua Cao; Bing Yu; Youqing Shen; Hailin Cong (Journal of Environmental Chemical Engineering, 2024)

Effects of Se-enriched yeast on the amelioration of atrazine-induced meat quality degradation - Cong Zhang; Yu Liu; Peilin Wang; Bo Wang; Shanshan Zhang; Zeao Hua; Yanan Li; Xuebing Wang; Xu Yang (Food Chemistry, 2024)

Seismotectonic segmentation controlled by magmatic underplating in the central-southern segment of Tanlu fault zone, eastern China - Yuqi Zhu; Zhouchuan Huang; Cong Ji; Dayong Yu; Ning Mi; Liangshu Wang; Christian Schiffer (Earth and Planetary Science Letters, 2024)

Promoting symbiotic relationship between microalgae and bacteria in wastewater treatment processes: Technic comparison, microbial analysis, and future perspectives - Cong-Cong Tang; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2024)

Amine/vermiculite composite aerogels fabricated by polyethyleneimine-induced vermiculite nanosheet gelation for efficient direct air capture - Shuai Wang; Huilian Sun; Jie Wang; Cong Chen; Lanlan Jiang; Yi Zhang; Yu Liu; Yongchen Song; Zheng Ling (Chemical Engineering Journal, 2024)

Research progress of injectable hydrogels in the treatment of bone tissue diseases - Shengjie Zhang; Xiaohua Li; Chunxiao Li; Hailin Cong; Bing Yu (Chemical Engineering Journal, 2024)

Efficient window layer modification enabling the remarkable FF and efficiency improvement of kesterite solar cell - Dongliang Ding; Yali Sun; Wenbo Li; Yuzhou Sun; Ridong Cong; Zhongrong Wang; Chao Gao; Wei Yu (Chemical Engineering Journal, 2024)

Silicon promotes biomass accumulation in Phragmites australis under waterlogged conditions in coastal wetland - Yuntao Wu; Xiaodong Zhang; Jiayang Lin; Xia Wang; Shaobo Sun; Qian Hao; Lele Wu; Jingyun Zhou; Shaopan Xia; Xiangbing Ran; Yidong Wang; Jiahuan Tang; et al. (Plant and Soil, 2024)

Linking plant nitrogen use efficiency with single traits, ecological strategies and phylogeny in a temperate steppe - Cong Ding; Simon Pierce; Guo-Jiao Yang; Yan-Yu Hu; Zhi-Wei Zhang; Xiao-Tao Lü (Plant and Soil, 2024)

Probing microscale crystallization phenomena: Transforming waste slags into riches - Cong Liang; Zheng-Da Yang; Yu Tan; Bin Ding (Waste Management, 2024)

PRRSV NSP1α degrades TRIM25 through proteasome system to inhibit host antiviral immune response - Yuhang Zheng; Dandan Jiang; Chao Sui; Xiangju Wu; Yue Hu; Changhee Lee; Xiaoyan Cong; Juntong Li; Yu Lu; Zhao Wang; Yijun Du; Jing Qi; et al. (Veterinary Microbiology, 2024)

Assessment and optimization of maximum magnitude forecasting models for induced seismicity in enhanced geothermal systems: The Gonghe EGS project in Qinghai, China - Xinxin Yin; Changsheng Jiang; Fengling Yin; Hongyu Zhai; Yu Zheng; Haidong Wu; Xue Niu; Yan Zhang; Cong Jiang; Jingwei Li (Tectonophysics, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Dissolved oxygen fluctuation alters dissolved organic carbon stability and can accumulate resistant fraction - Yu-Qing Li; Fu-Tao Fang; Cong Zeng; Zhuo-Yi Zhu (Marine Chemistry, 2024)

A down-regulated cytochrome P450 in Neoseiulus barkeri Hughes (Acari: Phytoseiidae) can dechlorinate and hydroxylate chlorpyrifos without producing chlorpyrifos-oxon - Shi-Jiang Yu; Li Wang; Li-Li Ding; Qi Pan; Si-Chen Li; Liu Liu; Lin Cong; Chun Ran (Journal of Hazardous Materials, 2024)

Lipidomics and metabolomics reveal the molecular mechanisms underlying the effect of thermal treatment on composition and oxidative stability of walnut oil - Jing-Jing Zhang; Xiao Xu; Qin Zeng; Cong Li; Bo-Nan Xi; Yu Shu; Tianchen Ma; Hengtao Dong; Yehua Shen (Food Research International, 2024)

Alkali-driven Donnan dialysis for efficient ammonia recovery from wastewater: Performance, mechanism and optimization - Zhinan Dai; Yuanyuan Yu; Wenjie Hao; Cong Chen; Maoqin Ao; Jingmei Yao; Chun Yang; Heng Liang; Chuanbo Guo; Le Han (Chemical Engineering Journal, 2024)

Analysis of Fracture Network Formation Mechanisms and Main Controlling Factors of Methane Explosion Fracturing in Deep Shale Reservoir - Yu Wang; Cheng Zhai; Ting Liu; Xu Yu; Jizhao Xu; Yong Sun; Yuzhou Cong; Wei Tang; Yangfeng Zheng; Ning Luo (Rock Mechanics and Rock Engineering, 2024)

Overexpression of the MiAGL1 gene from mango promoted flowering in transgenic Arabidopsis - Xue-mei Zeng; Xin-hua He; Wen-jing Mo; Hai-xia Yu; Ting-ting Lu; Li-ming Xia; Yi-li Zhang; Jia-wei Zhu; Cong Luo (Journal of Plant Biochemistry and Biotechnology, 2024)

Fibroblast growth factor receptor 4 deficiency in macrophages aggravates experimental colitis by promoting M1-polarization - Luyao Shen; Cong Wang; Ran Ren; Xudong Liu; Dongqin Zhou; Yu Chen; Yu Zhou; Juan Lei; Yang Xiao; Nan Zhang; Huakan Zhao; Yongsheng Li (Inflammation Research, 2024)

Performance evaluation of vegetation concrete with carbonaceous mudstone aggregates in slope protection under wet-dry conditions - Ling Zeng; Jin-Tao Luo; Zi-Ru Yang; Hui-Cong Yu; Wei Wen; Qian-Feng Gao; Hong-Ri Zhang (Bulletin of Engineering Geology and the Environment, 2024)

Synergistic mechanism and toxicity reduction potential in medium-pressure UV/chlorine/TiO2 system for metronidazole removal - Yu-qiong Gao; Xiang-mei Zhong; Xue-ting Ren; Fu-xiang Tian; Nai-yun Gao; Cong Li (Journal of Water Process Engineering, 2024)

Efficient photocatalytic degradation with a lattice-matched α-Bi2O3/Co3O4 Z-scheme heterojunction: An integrated experimental and DFT study - Xiaoqing Wang; Cong Du; Yue Yu; Weiyi Li; Tuo Li; Siyuan Wang; Shanjun Mao; Yongjiang Wang; Junzi Zhao; Chunhua Xiong (Journal of Water Process Engineering, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Organic blue carbon sequestration in vegetated coastal wetlands: Processes and influencing factors - Qian Hao; Zhaoliang Song; Xiaodong Zhang; Ding He; Laodong Guo; Lukas van Zwieten; Changxun Yu; Yidong Wang; Weiqi Wang; Yunying Fang; Yin Fang; Cong-Qiang Liu; et al. (Earth-Science Reviews, 2024)

Risk Factors for Preoperative Cerebral Infarction in Infants with Moyamoya Disease - Qingbao Guo; Songtao Pei; Qian-Nan Wang; Jingjie Li; Cong Han; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; Zhengxing Zou; et al. (Translational Stroke Research, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

The Role of KDM2A and H3K36me2 Demethylation in Modulating MAPK Signaling During Neurodevelopment - Zongyao Ren; Haiyan Tang; Wendiao Zhang; Minghui Guo; Jingjie Cui; Hua Wang; Bin Xie; Jing Yu; Yonghao Chen; Ming Zhang; Cong Han; Tianyao Chu; et al. (Neuroscience Bulletin, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

A highly sensitive and colorimetric fluorescent probe for visualizing hydroxylamine in immune cells - Wei Du; Yang Tian; Yu-An Feng; Xiao-Wei Cong; Rui Tan; Ya-Wen Wang; Yu Peng (Analytica Chimica Acta, 2024)

Identification of undescribed key impurities of homoharringtonine bulk drug - Yang Yu; Jing Wu; Cong-Yong Yue; Tao Zhang; Xiang-Hai Cai (Natural Product Research, 2024)

Genetic association of lipid traits and lipid-related drug targets with normal tension glaucoma: a Mendelian randomization study for predictive preventive and personalized medicine - Tianyi Kang; Yi Zhou; Cong Fan; Yue Zhang; Yu Yang; Jian Jiang (EPMA Journal, 2024)

Investigating the attribution of urban thermal environment changes under background climate and anthropogenic exploitation scenarios - Jiayi Ren; Jun Yang; Wenbo Yu; Nan Cong; Xiangming Xiao; Jianhong (Cecilia) Xia; Xueming Li (Sustainable Cities and Society, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Defense penetration strategy for unmanned surface vehicle based on modified soft actor–critic - Zhao Zhang; Xiao Liang; Cong Chen; Dianyong Liu; Changdong Yu; Wei Li (Ocean Engineering, 2024)

Optimizing terrestrial locomotion of undulating-fin amphibious robots: Asynchronous control and phase-difference optimization - Deliang Yu; Tianyu Che; Huibo Zhang; Chao Li; Cong Wang; Zhaotian Wang (Ocean Engineering, 2024)

Experimental investigation on flame morphology and wall-attached flame temperature of jet flame under the coupled effect of nozzle angle and nozzle-wall spacing - Gaoming Lu; Haiyong Cong; Ziqi Yuan; Zhuyu Shao; Lili Ye; Yubo Bi; Mingshu Bi; Binshan Yu (Fuel, 2024)

Characterization of oxylipins in Antarctic krill oil (Euphausia superba) during storage based on RPLC–MS/MS analysis - Nan Meng; Xincen Wang; Yu Song; Xiaowei Fan; Junpeng Zeng; Tingyu Feng; Peixu Cong; Jie Xu; Changhu Xue (Food Chemistry, 2024)

Effects of hypo-osmotic stress on osmoregulation, antioxidant response, and energy metabolism in sea cucumber Holothuria moebii under desalination environment - Junyang Jiang; Yanna Tang; Zhaozhao Cao; Cong Zhou; Zonghe Yu (Environmental Research, 2024)

Membraneless organelles assembled by AuNPs-enzyme integration in non-photosynthetic bacteria: Achieving high specificity and selectivity for solar hydrogen production - Hui Li; Xiaoxuan Yu; Yaqi Wu; Cong Li; Zhengwei Xu; Wang Liu; Shuheng Chen; Hongcheng Sun; Yan Ge; Zhenhui Qi; Junqiu Liu (Chemical Engineering Journal, 2024)

Pilot-scale field studies on activated microbial remediation of petroleum-contaminated soil - Wu-Juan Sun; Qian Li; Bo-Yun Luo; Rui Sun; Cong-Yu Ke; Si-Chang Wang; Qun-Zheng Zhang; Xun-Li Zhang (Environmental Geochemistry and Health, 2024)

Transforming crystal structures of cobalt molybdate to generate electron-rich sites for electrochemical detection of Pb(II) - Yang-Zhi Liu; Xin Cai; Cong-Cong Huang; Zi-Hao Liu; Yuan-Fan Yang; Yong-Yu Li; Meng Yang; Shi-Hua Chen; Xing-Jiu Huang (Analytica Chimica Acta, 2024)

A polyfunctionalized carbon framework composite for efficient decontamination of Cr(VI) and polycyclic aromatic nitrides from acidic wastewater - Weilong Wu; Han Zhang; Rong Qian; Kunru Yu; Ronghua Li; Kuok Ho Daniel Tang; Xuan Wu; Zhiqiang Guo; Cong Shao; Feixue Yue; Zengqiang Zhang (Environmental Science and Pollution Research, 2024)

Transcriptional and ultrastructural changes of macrophages after african swine fever virus infection - Cong Yuan; Yueyue Duan; Xiangtong Li; Yu Zhang; Liyan Cao; Tao Feng; Junwei Ge; Qi Wang; Haixue Zheng (Veterinary Microbiology, 2024)

Synergistic use of photocatalysis and convergent paired electrolysis for nickel-catalyzed arylation of cyclic alcohols - Zhao-Ran Liu; Xiao-Yu Zhu; Jian-Feng Guo; Cong Ma; Zhiwei Zuo; Tian-Sheng Mei (Science Bulletin, 2024)

The G932C mutation of chitin synthase 1 gene (CHS1) mediates buprofezin resistance as confirmed by CRISPR/Cas9-mediated knock-in approach in the brown planthopper, Nilaparvata lugens - Fan Zhang; Yan-Chao Zhang; Zhi-Tao Yu; Bing Zeng; Hao Sun; Yu-Qiu Xie; Kun Yan Zhu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

A simplified time-frequency fatigue analysis method considering the response characteristics of jacket-type offshore wind turbine - Mengyao Peng; Min Liu; Yu Cong; Shuitao Gu (Ocean Engineering, 2024)

A novel cooperative optimization method of course and speed for wing-diesel hybrid ship based on improved A* algorithm - Cong Wang; Lianzhong Huang; Ranqi Ma; Kai Wang; Jinlu Sheng; Zhang Ruan; Yu Hua; Rui Zhang (Ocean Engineering, 2024)

First record of the latest Devonian ostracods from Xainza region, Tibet, China: implications on palaeoenvironment and palaeobiogeography - Jun-Jun Song; Wen Guo; Yu-Cong Sun; Juan Ma; Jia-Yuan Huang; Yi-Chun Zhang; Wen-Kun Qie (Palaeoworld, 2024)

Pickering extremulsion rich in lipophilic phytochemicals: Preparation, characterization and application - Xu Han; Cong-Jia Duan; Zi-Fei Wei; Jian Xu; Cheng-Dong Nie; Yuan-Hang Chang; Bo-wen Zhai; Yu-Jie Fu (Journal of Food Engineering, 2024)

Temperature effects on plasmalogen profile and quality characteristics in Pacific oyster (Crassostrea gigas) during depuration - Yu Song; Lili Hao; Xincen Wang; Xiaoxu Wang; Peixu Cong; Zhaojie Li; Changhu Xue; Jie Xu (Food Research International, 2024)

Electron-beam generated X-ray irradiation could retard the senescence of postharvest Hericium erinaceus via regulating reactive oxygen metabolism - Yuanyuan Zhong; Yuan Cui; Xinyang Wang; Junzhao Cong; Jiangtao Yu; Shengkun Yan; Junqing Bai; Huaide Xu; Mei Li (Food Bioscience, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Biochar derived from alkali-treated sludge residue regulates anaerobic digestion: Enhancement performance and potential mechanisms - Wen Hu; Hong-Yu Jin; Xiang-Yu Gao; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhihua Li; Zhang-Wei He (Environmental Research, 2024)

Electronic structure and microenvironment modulation of Pd@UiO-66 enhances direct CO esterification to dimethyl carbonate - Yu-Ping Xu; Wen-Fa Chen; Ming-Sheng Wang; Bin-Wen Liu; Shuai-Shuai Hu; Zhong-Ning Xu; Guo-Cong Guo (Chemical Engineering Journal, 2024)

Unlocking the potential of high-voltage aqueous rechargeable batteries: Achievements and perspectives - Feng Yu; Lide Li; Le Pang; Songjun Yang; He Liu; Cong Guo; Weizhai Bao; Jingfa Li; Guozhen Zhang; Faxing Wang; Hongxia Wang (Chemical Engineering Journal, 2024)

Marinobacter albus sp. nov., Isolated from Sand Sediment in a Coastal Intertidal Zone - Tai-Hang Deng; Yu Zhang; Wen-Wu Zhang; Yue Su; Jia-Wei Gao; Jun-Jie Ying; Lin Xu; Xiao-Ming Xia; Cong Sun (Current Microbiology, 2024)

Spatiotemporal evolution of surface urban heat islands: Concerns regarding summer heat wave periods - Jiayi Ren; Jun Yang; Wenbo Yu; Nan Cong; Xiangming Xiao; Jianhong Xia; Xueming Li (Journal of Geographical Sciences, 2024)

Isolation and identification of Pseudomonas tolaasii causing brown rot on Morchella sextelata in Guizhou Province, China - Zhenghui Liu; Yunlong Cong; Frederick Leo Sossah; Yongzhong Lu; Jichuan Kang; Yu Li (Crop Protection, 2024)

Experimental study on the performance of synergistic ventilation system combining shaft with mechanical ventilation in extra-long road tunnels - Bin Zhu; Haiyong Cong; Binshan Yu; Zhuyu Shao; Lili Ye; Yubo Bi; Yiping Zeng (Tunnelling and Underground Space Technology, 2024)

Spatiotemporal variations, sources, and atmospheric transformation potential of volatile organic compounds in an industrial zone based on high-resolution measurements in three plants - Jin-Long Mai; Xing-Cong Cai; De-Yao Luo; Yuan Zeng; Yu-Feng Guan; Wei Gao; She-Jun Chen (Science of The Total Environment, 2024)

Potential of exogenous melatonin administration to mitigate heat stress induce pathophysiology of chicken - Guanghu Zhou; Jingjing Zhang; Shuang Liu; Sainan Dong; Yimei Cong; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2024)

The FAK/occludin/ZO-1 complex is critical for cadmium-induced testicular damage by disruption of the integrity of the blood-testis barrier in chickens - Xiao-Wei Li; Sheng Li; Yu Yang; Milton Talukder; Xiang-Wen Xu; Chen-Xi Li; Cong Zhang; Xue-Nan Li; Jin-Long Li (Journal of Hazardous Materials, 2024)

Catalytic hydroconversion of residue from methanolysis of XilinGol League No. 6 Lignite: Cracking mechanism of C-O bond and structural features of liquid coal derivative - Sheng Li; Xiao-Yu Zhang; Zhi-Min Zong; Zhi-Hao Ma; Jian-Feng Shan; Xing-Shun Cong; Mei-Ling Xu; Li Li; Xian-Yong Wei (Fuel, 2024)

Fate of contaminants of emerging concern in two wastewater treatment plants after retrofitting tertiary treatment for reduction of nitrogen discharge - Tianyuan Chen; Qiaoting Zeng; Meixian Cao; Lanping Zhang; Bob Adyari; Cong Ma; Kai Wang; Deti Gao; Anyi Hu; Qian Sun; Chang-Ping Yu (Environmental Research, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

Sensitivities of energy use reduction in subtropical high-rise office buildings: A Hong Kong case - Cong Yu; Wei Pan; Yefei Bai (Energy and Buildings, 2024)

Interpolation of non-stationary geo-data using Kriging with sparse representation of covariance function - Cong Miao; Yu Wang (Computers and Geotechnics, 2024)

A novel ZIF-8@cellulose composite monolithic carbon via a facile template-free strategy for selective and efficient CO2 adsorption - Yu Shu; Longfei Qiao; Jialong Geng; Cong Li; Bang Chen; Qidong Wang; Hiroshi Uyama; Yehua Shen (Chemical Engineering Journal, 2024)

Synergistic therapy for melanoma via bioactive compounds derived metal-phenolic networks - Zhenghao Zhou; Cong Li; Shuai Cui; Shian Sun; Shaowei Zhu; Qing Yu; Ning Ding; Hao Hong; Dongzhi Yang (Chemical Engineering Journal, 2024)

Cross-Talking Pathways of Rapidly Accelerated Fibrosarcoma-1 (RAF-1) in Alzheimer’s Disease - Hong Hong; Lujiao Yu; Wenqiang Cong; Kexin Kang; Yazhu Gao; Qing Guan; Xin Meng; Haiyan Zhang; Zhike Zhou (Molecular Neurobiology, 2024)

Taxonomic status of hares ( Lepus spp.) in Xinjiang, China (Lagomorpha: Leporidae): An integrative approach - Wen‐Juan Shan; Zu‐Rui Li; Hui‐Ying Dai; Peng‐Cheng Dong; Yu‐Cong Zhang (Zoologica Scripta, 2024)
The taxonomic status and interspecies relationships of hares (genus Lepus ) in Xinjiang, China, remain ambiguous owing to extremely similar external morphologies, introgressive hybridization between species and a lack of molecular genetic records. In this study, a total of 154 hare specimens were used to clarify their taxonomic status. Based on multiple lines of evidence, including observations and comparisons of external morphological characteristics, skull morphometrics and genome‐wide single nucleotide polymorphism (SNP) datasets, four hare species were recognised. Lepus yarkandensis and Lepus timidus , which have obvious morphological characteristics, were identified as two distinct species, as previously reported. Combining the integrated morphological and molecular datasets with the relevant literature, we proposed suggestions on the classification of the more controversial hares. Due to molecular and morphological similarities, hares in northern and central Xinjiang were divided into two subspecies of Lepus tolai , namely, Lepus tolai lehmanni and Lepus tolai centrasiaticus . Despite similar external morphological characters, hares in the southwest Pamir Plateau and its surroundings can be distinguished from L. tolai by differences in skull morphology and genetic divergence and were, therefore, considered a subspecies of Lepus tibetanus , Lepus tibetanus pamirensis . Furthermore, we found that hybridization and introgression occurred between sympatric or parapatric hares, especially between L. yarkandensis and L. tibetanus pamirensis , L. yarkandensis and L. tolai centrasiaticus , and L. tolai lehmanni and L. timidus .

Metabolomics revealed more deleterious toxicity induced by the combined exposure of ammonia and nitrite on Ruditapes philippinarum compared to single exposure - Ming Cong; Zhaoshun Li; Yu Che; Yuanmei Li; Wenwen Tian; Jiasen Lv; Xiyan Sun (Marine Environmental Research, 2024)

Pilot–scale vertical continuous–flow reactors applied to treat rural domestic wastewater at low temperature via aerobic granular sludge - Shibo Cong; Ge Yu; Shuai Xia; Haiyang Yu; Yang Sun; Yu Gao; Yuzhi Liu; Donglei Zou (Journal of Water Process Engineering, 2024)

Different responses of marine microalgae Phaeodactylum tricornutum upon exposures to WAF and CEWAF of crude oil: A case study coupled with stable isotopic signatures - Yadi Lou; Ying Wang; Shiyue Li; Fuwei Yu; Xing Liu; Yi Cong; Zhaochuan Li; Fei Jin; Mingxing Zhang; Ziwei Yao; Juying Wang (Journal of Hazardous Materials, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

An efficient process for preparing regenerated magnets by dynamic recovery of Nd-Fe-B sintered magnet sludge - Liying Cong; Haibo Xu; Qingmei Lu; Lichao Yu; Quangui Zhou; Qiong Wu; Ming Yue (Journal of Environmental Chemical Engineering, 2024)

Liquid immiscibility acting on the formation of the Miaoya carbonatite-syenite complex in the South Qinling Belt, Central China - Yu-hong Xia; Shao-cong Lai; Hang Yang; Yu Zhu; Jiang-feng Qin; Ren-zhi Zhu; Min Liu; Fang-yi Zhang; Zhe-hao Zhong (Journal of Asian Earth Sciences, 2024)

Exploring debris flow deposit morphology in river valleys: Insights from physical modeling experiments - Cong-Jiang Li; Yu-Xiang Hu; Gang Fan; Qing-Yang Zhu; Da-Rui Liu; Jia-Wen Zhou (Engineering Geology, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Hornblendites as a record of differentiation, metasomatism and magma fertility in arc crust - Ren-Zhi Zhu; Daniel J. Smith; Fangyue Wang; Jiang-Feng Qin; Chao Zhang; Shaowei Zhao; Min Liu; Fangyi Zhang; Yu Zhu; Shao-Cong Lai (Chemical Geology, 2024)

Identification of GmPT proteins and investigation of their expressions in response to abiotic stress in soybean - Xiaolan Yang; Qing Hu; Yunfeng Zhao; Yanhang Chen; Cong Li; Jin He; Zhen-Yu Wang (Planta, 2024)

Soil bacteria mediate organic carbon stability during alpine wetland biogeomorphic succession in the arid region of Central Asia - Yang Hu; Mengfei Cong; Mo Chen; Maidinuer Abulaizi; Guangling Yu; Zailei Yang; Xinping Zhu; Hongtao Jia (Plant and Soil, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Molecular characterization and functional analysis of peroxiredoxin 1 (Prx1) from roughskin sculpin (Trachidermus fasciatus) - Yingying Liu; Haiyan Cong; Caihong Bi; Haidong Zha; Shanshan Yu; Lihua Zhao; Qian Zhu (Fish Physiology and Biochemistry, 2024)

Grazing exclusion jeopardizes plant biodiversity effect but enhances dryness effect on multifunctionality in arid grasslands - Lingfei Yu; Wenjuan Sun; Haiyang Zhang; Nan Cong; Yuan Chen; Jinjiao Hu; Xin Jing (Agriculture, Ecosystems & Environment, 2024)

Physiological and transcriptome analysis of acclimatory response to cold stress in marine red alga Pyropia yezoensis - Li-Hong Ma; Lin Tian; Yu-Qing Wang; Cong-Ying Xie; Guo-Ying Du (Algae, 2024)
Red macroalga Pyropia yezoensis is a high valuable cultivated marine crop. Its acclimation to cold stress is especially important for long cultivation period across winter in coasts of warm temperate zone in East Asia. In this study, the response of P. yezoensis thalli to low temperature was analyzed on physiology and transcriptome level, to explore its acclimation mechanism to cold stress. The results showed that the practical photosynthesis activity (indicated by ΦPSII and qP) was depressed and pigment allophycocyanin content was decreased during the cold stress of 48 h. However, the Fv/Fm and non-photochemical quenching increased significantly after 24 h, and the average growth rate of thalli also rebounded from 24 to 48 h, indicating a certain extent of acclimation to cold stress. On transcriptionally, the low temperature promoted the expression of differentially expressed genes (DEGs) related to carbohydrate metabolism and energy metabolism, while genes related to photosynthetic system were depressed. The increased expression of DEGs involved in ribosomal biogenesis and lipid metabolism which could accelerate protein synthesis and enhance the degree of fatty acid unsaturation, might help P. yezoensis thallus cells to cope with cold stress. Further co-expression network analysis revealed differential expression trends along with stress time, and corresponding hub genes play important roles in the systemic acquired acclimation to cold stress. This study provides basic mechanisms of P. yezoensis acclimation to cold temperature and may aid in exploration of functional genes for genetic breeding of economic macroalgae.

Damaging effects of earth fissures on high-speed railway bridges: Insights from physical experiments and numerical simulations - Cong Liu; Zhaoyue Yu; Jiewei Zhan; Ming Wu; Yuemin Sun; Jianbing Peng (Transportation Geotechnics, 2024)

Mechanisms of LPS–induced epithelial mesenchymal transition in bEECs - Mingkun Sun; Pengjie Song; Yu Zhao; Bowen Li; Ping Wang; Zhipeng Cong; Song Hua (Theriogenology, 2024)

Petrological and mineralogical constraints on the formation of Neoproterozoic calc-alkaline continental crust: The example of the Luding Intrusive complex, western Yangtze Block, South China - Yu Zhu; Shao-cong Lai; Hervé Rezeau; Ren-Zhi Zhu; Min Liu; Jiang-Feng Qin; Shao-wei Zhao; Fang-yi Zhang; Hang Yang (Lithos, 2024)

Antimicrobial resistance characteristics and phylogenetic relationships of pleuromutilin-resistant Enterococcus isolates from different environmental samples along a laying hen production chain - Cong Lin; Yuxuan Feng; Xianjun Xie; Haoyu Zhang; Jie Wu; Yixiao Zhu; Jing Yu; Jingyi Feng; Wen Su; Shanming Lai; Anyun Zhang (Journal of Environmental Sciences, 2024)

Characterization and metabolism pathway of volatile compounds in walnut oil obtained from various ripening stages via HS-GC-IMS and HS-SPME-GC–MS - Bo-Nan Xi; Jing-Jing Zhang; Xiao Xu; Cong Li; Yu Shu; Yu Zhang; Xuanming Shi; Yehua Shen (Food Chemistry, 2024)

Photon-phonon coupling cold sterilization technology for milk preservation - Xiaodong Wang; Jingqiang Yu; Haixia Wu; Leiying Wu; Wuyunga Borjihan; Cong Wang; Munkhjargal Burenjargal; Alideertu Dong (Food Control, 2024)

Effects of irrigation and nitrogen levels on yield and water-nitrogen-radiation use efficiency of drip-fertigated cotton in south Xinjiang of China - Zhentao Bai; Cong Xie; Jiang Yu; Wenqiang Bai; Shengzhao Pei; Yunxia Li; Zhijun Li; Fucang Zhang; Junliang Fan; Feihu Yin (Field Crops Research, 2024)

Synergistic binding mechanisms of co-contaminants in soil profiles: Influence of iron-bearing minerals and microbial communities - Fu-Sheng Sun; Miao-Miao Wang; Xiang-Yang Zhao; Qiao-Yun Huang; Cong-Qiang Liu; Guang-Hui Yu (Environmental Pollution, 2024)

Identification of the domestication gene GmCYP82C4 underlying the major quantitative trait locus for the seed weight in soybean - Yang Li; Wenqian Zhao; Jiajun Tang; Xiuli Yue; Jinbao Gu; Biyao Zhao; Cong Li; Yanhang Chen; Jianbo Yuan; Yan Lin; Yan Li; Fanjiang Kong; et al. (Theoretical and Applied Genetics, 2024)

Elevating sensing capability via dual-atom catalysts boosted luminol cathodic electrochemiluminescence - Yan-Chen Kong; Dan-Ling Wang; Jing-Jing Zhang; Yu-Xin Yang; Cong-Hui Xu; Rida Javed; Hongbin Zhao; Daixin Ye; Wei Zhao (Analytica Chimica Acta, 2024)

Significant accrual of soil organic carbon through long‐term rice cultivation in paddy fields in China - Xiaomin Yang; Zhaoliang Song; Lukas Van Zwieten; Laodong Guo; Ji Chen; Zhongkui Luo; Yidong Wang; Yu Luo; Zhengang Wang; Weiqi Wang; Jingxu Wang; Yu Wang; et al. (Global Change Biology, 2024)
Paddy fields serve as significant reservoirs of soil organic carbon (SOC) and their potential for terrestrial carbon (C) sequestration is closely associated with changes in SOC pools. However, there has been a dearth of comprehensive studies quantifying changes in SOC pools following extended periods of rice cultivation across a broad geographical scale. Using 104 rice paddy sampling sites that have been in continuous cultivation since the 1980s across China, we studied the changes in topsoil (0–20 cm) labile organic C (LOC I), semi‐labile organic C (LOC II), recalcitrant organic C (ROC), and total SOC. We found a substantial increase in both the content (48%) and density (39%) of total SOC within China's paddy fields between the 1980s to the 2010s. Intriguingly, the rate of increase in content and density of ROC exceeded that of LOC (I and II). Using a structural equation model, we revealed that changes in the content and density of total SOC were mainly driven by corresponding shifts in ROC, which are influenced both directly and indirectly by climatic and soil physicochemical factors; in particular temperature, precipitation, phosphorous (P) and clay content. We also showed that the δ 13 C LOC were greater than δ 13 C ROC , independent of the rice cropping region, and that there was a significant positive correlation between δ 13 C SOC and δ 13 C straw . The δ 13 C LOC and δ 13 C SOC showed significantly negative correlation with soil total Si, suggesting that soil Si plays a part in the allocation of C into different SOC pools, and its turnover or stabilization. Our study underscores that the global C sequestration of the paddy fields mainly stems from the substantial increase in ROC pool.

Association of multiple blood metals and systemic atherosclerosis: A cross-sectional study in the CAD population - Yapei Sun; Qi Mao; Denglu Zhou; Jiacheng Tian; Hang Du; Qin Yu; Jianhua Zhao; Weixia Duan; Cong Liu; Yu Duan; Jie Zhou; Tian Zhang; et al. (Chemosphere, 2024)

Short-term exposure to ozone may trigger the onset of Kawasaki disease: An individual-level, case-crossover study in East China - Yixiang Zhu; Renjie Chen; Cong Liu; Yue Niu; Xia Meng; Su Shi; Kexin Yu; Guoying Huang; Liping Xie; Siyuan Lin; Min Huang; Meirong Huang; et al. (Chemosphere, 2024)

Preparation of high-purity SiO2 by S-HGMS coupled with mixed-acid leaching: A case study on hematite tailings from Ansteel, China - Cong Li; Xiaofeng Yang; Yongkui Li; Yu Chen; Xiaodong Pan; Yongping Xie; Xingyu Liu; Suqin Li (Waste Management, 2024)

Settlement prediction of immersed tunnel considering time-dependent foundation modulus - Shu-Yu He; Cong Tang; Wan-Huan Zhou (Tunnelling and Underground Space Technology, 2024)

Climate and industrial pollution determine the seasonal and spatial mercury variations in the China's Weihe River - Xinyu Zhang; Huhu Kang; Liangju Zhao; Junming Guo; Yu Zhang; Cong Xie; Xiying Dong; Shichang Kang; Xiaohong Liu (Science of The Total Environment, 2024)

Quantitative single-virus tracking for revealing the dynamics of SARS-CoV-2 fusion with plasma membrane - Hao-Yang Liu; Yusi Hu; Cong Yu; Zhi-Gang Wang; Shu-Lin Liu; Dai-Wen Pang (Science Bulletin, 2024)

Modular ocean trace elements sampling for the international GEOTRACES studies – Evidence from analysis of dissolved Fe and Pb - J. Zhang; Z.T. Ni; J.L. Ren; F. Yu; X.Y. Diao; Y. Wang; S.J. Zhang; H. Su; S.L. Cong; Z.J. Lu; S. Jiang; J. Ou; et al. (Progress in Oceanography, 2024)

Vertical baffled reactor promoting aerobic sludge concentration for effective remediating unstable–load domestic wastewater: Performance, microbial properties and mechanism - Shibo Cong; Yang Sun; Yanhong Dong; Guangxu Xiao; Donglei Zou; Yu Yan (Journal of Water Process Engineering, 2024)

Improving enzyme accessibility in the aqueous enzymatic extraction process by microwave-induced porous cell walls to increase oil body and protein yields - Xin Guo; Bi-cong Wu; Yun Jiang; Yu Zhang; Bo Jiao; Qiang Wang (Food Hydrocolloids, 2024)

Research on fatigue damage mitigation of offshore wind turbines by a bi-directional PSTMD under stochastic wind-wave actions - Zhenbo Lei; Gang Liu; Yu Cong; Wei Tang (Engineering Structures, 2024)

Sense and Shoot: Multifunctional CaO2-loaded Cu-MOF nanosheets for integrated fluorescence detection and fenton-like degradation of tetracycline - Yuxin Wang; Yishuang Li; Cong Wang; Xiaoxiao Yu; Guosong Lai; Xin Li (Chemical Engineering Journal, 2024)

Triboelectric negative air ion generators for efficient membrane fouling control - Yi Dai; Kang Yu; Huan Li; Hongyue Zhu; Jiao Xie; Dengpan Nie; Tao Liu; Bin Luo; Cong Gao; Yingchun Luo; Yiyi Wu; Shuangxi Nie (Chemical Engineering Journal, 2024)

Revealing the roles of biochar derived from iron-rich fermented sludge residue in anaerobic digestion - Hong-Yu Jin; Zhang-Wei He; Yong-Xiang Ren; Zheng-Shuo Zou; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Zhihua Li; Aijie Wang (Chemical Engineering Journal, 2024)

Rare earth elements in sediments of the Pearl River Estuary, China: distribution, influencing factors, and multi-index assessment - Fang Chen; Yang-Guang Gu; Sheng-Zhong Ma; Yan-Mei Wang; Shao-Hua Yu; Yang Zhou; Cong Wu; Zhi-Yuan Peng (Journal of Soils and Sediments, 2024)

A systematic review and meta-analysis of the efficacy of ketamine and esketamine on suicidal ideation in treatment-resistant depression - Ya-Ting Wang; Xiao-Le Wang; Lan Lei; Zhen-Yu Guo; Fei-Fei Kan; Die Hu; Cong Gai; Yi Zhang (European Journal of Clinical Pharmacology, 2024)

CS/CoFe2O4 nanocomposite as a high-effective and steady chainmail catalyst for tetracycline degradation with peroxymonosulfate activation: performance and mechanism - Weiwei Yu; Yueqi Li; Minghui Shu; Cong Liu; Yue Liang; Yufeng Mao; JiangLin Tan; Yang Liu; Ting Ai (Environmental Geochemistry and Health, 2024)

Hydrogeochemistry and indicators of flowback and produced water from wells that are hydraulically fractured with recycled wastewater: A case study of the Changning gas field in the Sichuan Basin - Dan Liu; Wei Xiong; Xiaowei Zhang; Wei Guo; Wanting Li; Jinliang Gao; Lixia Kang; Yuyang Liu; Zhaoyuan Shao; Lin Zhang; Cong Yu; Fengrong Liao; et al. (Applied Geochemistry, 2024)

Isolation and Cultivation of Carotenoid-Producing Strains from Tidal Flat Sediment and Proposal of Croceibacterium aestuarii sp. nov., a Novel Carotenoid-Producing Species in the Family Erythrobacteraceae - Xiao-Yan Sun; Han Dong; Yu Zhang; Jia-Wei Gao; Peng Zhou; Cong Sun; Lin Xu (Journal of Marine Science and Engineering, 2024)
Carotenoids are extensively used in drugs, cosmetics, nutrients, and foods, owing to their antioxidant and anti-inflammatory characteristics. Diverse marine heterotrophic prokaryotes can accumulate carotenoids and become promising alternatives for the advancement of carotenoids production. In this research, 55 strains were isolated and cultivated from tidal flat sediment in Zhoushan and classified into the phyla Pseudomonadota (n = 24), Bacillota (n = 18), Bacteroidota (n = 9), and Actinomycetota (n = 4). Nine of them accumulated carotenoids, and most of them belonged to the families Flavobacteriaceae (n = 4) and Erythrobacteraceae (n = 4). Among those carotenoid-producing strains, one strain, designated as D39T, was proposed as one novel species belonging to the genus Croceibacterium through polyphasic taxonomy approaches. Genomic annotations and carotenoid compound determinations revealed that strain D39T encoded crtEBIYZG genes and mainly accumulated zeaxanthin as major carotenoids. Furthermore, carotenoid biosynthesis pathway in the majority of Croceibacterium strains were identical with that in the strain D39T, implying that Croceibacterium members can be sources of producing zeaxanthin. This study enhances knowledge of microbial biodiversity in tidal flats, proposes a novel carotenoid-producing Croceibacterium species, and elucidates carotenoid biosynthesis pathway in the genus Croceibacterium, which contribute to enriching marine carotenoid-producing strains and promoting a comprehensive insight into genomic contents of them.

Efficient Bayesian model updating for settlement prediction of the immersed tunnel of HZMB - Shu-Yu He; Sin-Chi Kuok; Cong Tang; Wan-Huan Zhou (Transportation Geotechnics, 2024)

Regulation of Hippo-YAP/CTGF signaling by combining an HDAC inhibitor and 5-fluorouracil in gastric cancer cells - Yanling Wu; Cong Shan Li; Ruo Yu Meng; Hua Jin; Ok Hee Chai; Soo Mi Kim (Toxicology and Applied Pharmacology, 2024)

Mass-immigration shapes the antibiotic resistome of wastewater treatment plants - Lanping Zhang; Bob Adyari; Liyuan Hou; Xiaoyong Yang; Mahmoud Gad; Yuwen Wang; Cong Ma; Qian Sun; Qiang Tang; Yifeng Zhang; Chang-Ping Yu; Anyi Hu (Science of The Total Environment, 2024)

Quantitative relationships of FAM50B and PTCHD3 methylation with reduced intelligence quotients in school aged children exposed to lead: Evidence from epidemiological and in vitro studies - Cong Wan; Huimin Ma; Jiahong Liu; Fei Liu; Jing Liu; Guanghui Dong; Xiaowen Zeng; Daochuan Li; Zhiqiang Yu; Xinming Wang; Jun Li; Gan Zhang (Science of The Total Environment, 2024)

A slow-release fertilizer containing cyhalofop-butyl reduces N2O emissions by slowly releasing nitrogen and down-regulating the relative abundance of nirK - Zewang Zhang; Gonglei Chen; Xiangyang Yu; Dong Liang; Cong Xu; Cheng Ji; Lei Wang; Hongbo Ma; Jidong Wang (Science of The Total Environment, 2024)

Contrasting effects of intensified dry-season drought and extended dry-season length on soil greenhouse gas emissions in a subtropical forest - Cong Wang; Guoliang Xiao; Yu Guan; Yong Li; Dan Chen; Weijun Shen (Science of The Total Environment, 2024)

Selaginellin derivatives from Selaginella tamariscina and evaluation for anti-breast cancer activity - Jing Wen; Dong-Mei Sha; Xiao-Yong He; Yu-Han Tian; Shuai-Cong Ni; Bin He; Yuan Liu; Xin-Jia Yan (Phytochemistry, 2024)

UV-LED cocatalytic Fe3+/peroxymonosulfate process for the degradation of sulfamethoxypyridazine: Performance, mechanism and DBP formation during postchlorination - Yu-qiong Gao; Qian Zeng; Ke-xuan Li; Ju-xiang Chen; Xiao-jun Deng; Tao Wu; Cong Li (Journal of Water Process Engineering, 2024)

A novel low sampling rate and cost-efficient active sampler for medium/long-term monitoring of gaseous pollutants - Zhiyuan Wang; Tao Yu; Jin Ye; Lei Tian; Bencheng Lin; Wenjun Leng; Cong Liu (Journal of Hazardous Materials, 2024)

Design of bifunctional ultrathin MnO2 nanofilm with laccase-like activity for sensing environmental pollutants containing phenol groups - Sheng-Tao Wu; Hui-Qi Su; Qian-Xiang Xiao; Zhi-Yu Qiu; Gang-Qiang Huang; Man-Ni He; Yi Ge; Cong-Hui Wang; Ying-Wu Lin (Journal of Hazardous Materials, 2024)

Biomethane production enhancement from waste activated sludge with recycled magnetic biochar: Insights into the recycled strategies and mechanisms - Hong-Yu Jin; Yong-Xiang Ren; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Zhihua Li; Aijie Wang; Zhang-Wei He (Journal of Cleaner Production, 2024)

Preparation of antibacterial antiviral nanofiber and its application in durable and self-cleaning personal protective equipment - Xiaohua Li; Shuaibing Guo; Shengjie Zhang; Chunxiao Li; Bing Yu; Hailin Cong; Youqing Shen (Chemical Engineering Journal, 2024)

A review of chitosan in gene therapy: Developments and challenges - Liang Dong; Yanan Li; Hailin Cong; Bing Yu; Youqing Shen (Carbohydrate Polymers, 2024)

Determination of uptake rates of volatile organic compounds by 24-hour passive sampling and their application in enclosed ship cabin environments - Tao Yu; Yan Wang; Longfei Chen; Wenjun Leng; Yue Shi; Bencheng Lin; Juntao Zhao; Zhiyuan Wang; Jinhan Mo; Cong Liu (Building and Environment, 2024)

A systematic review of drying in aquatic products - Junpeng Zeng; Yu Song; Peixu Cong; Yunrui Cao; Jie Xu; Changhu Xue (Reviews in Aquaculture, 2024)
Drying is an essential method for the process and storage of aquatic products. With the removal of water, the occurrence of oxidation, hydrolysis and browning reaction also accompanies it. This article reviews the applications of emerging drying methods in aquatic products, emphasising high‐quality drying. In addition, it summarises the effects of the drying process on the quality of aquatic products, including appearance, nutritional components, flavour and microorganisms. Especially, non‐destructively monitoring technologies are introduced and discussed, including near‐infrared spectroscopy, Raman spectroscopy, hyperspectral imaging, low‐field nuclear magnetic resonance and computer vision system, which are applied to detect and predict the quality of aquatic products. A comprehensive review of recent advances in the research of the drying process of aquatic products is presented, and some perspectives are made for future research.

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

ZIC2 accelerates growth and stemness in gastric cancer through the Wnt/β-catenin pathway - Ying Yu; Chao Tan; Li Ding; Zhen Zhu; Gong Zhang; Cong Long (Tissue and Cell, 2023)

Corrigendum to “Cardamine violifolia as a potential Hg hyperaccumulator and the cellular responses” [Sci. Total Environ., Volume 863(2023), 160940] - Liwei Cui; Xue Tian; Hongxin Xie; Xin Cong; Lihong Cui; Han Wu; Jianxu Wang; Bai Li; Jiating Zhao; Yanshan Cui; Xinbin Feng; Yu-Feng Li (Science of The Total Environment, 2023)

Characterising personal, household, and community PM2.5 exposure in one urban and two rural communities in China - Ka Hung Chan; Xi Xia; Cong Liu; Haidong Kan; Aiden Doherty; Steve Hung Lam Yim; Neil Wright; Christiana Kartsonaki; Xiaoming Yang; Rebecca Stevens; Xiaoyu Chang; Dianjianyi Sun; et al. (Science of The Total Environment, 2023)

Fusion dsRNA in targeting salivary protein genes enhance the RNAi-based aphid control - Li Yang; Cong-Yan Qin; Yang Chen; Zi-Guo Wang; Ruo-Yu Chen; Jinzhi Niu; Jin-Jun Wang (Pesticide Biochemistry and Physiology, 2023)

Complete genome sequence of carotenoid-producing Aestuariibaculum lutulentum L182T isolated from the tidal sediment - Wen-Jia Liu; Jia-Wei Gao; Yu Zhang; Cong Sun; Lin Xu (Marine Genomics, 2023)

Coupling UV-radiation with immobilized bacteria for the removal of 17β-estradiol and 17 α-ethynylestradiol - Dan Qin; Claude Kiki; Cong Ma; Qian Sun; Chang-Ping Yu (Journal of Water Process Engineering, 2023)

Efficient heterogeneous activation of peroxymonosulfate by manganese-doped LaCoO3 perovskites for metronidazole degradation: A mechanistic study and reaction pathways - Muhammad Rafiq; Adeel Ahmed; Muhammad Usman; Raza Ullah; Fengyuan Gao; Muhammad Mateen; Bing Yu; Youqing Shen; Hailin Cong (Journal of Environmental Chemical Engineering, 2023)

Effects of pomelo sponge fermented by Monascus ruber on cholesterol metabolism and intestinal microbiota in high-fat diet mice - Yu-Zhen Li; Jie-Yan Shi; Hui Wu; Ka-Hing Wong; Peter C.K. Cheung; Xu-Cong Lv; Qiong-Qiong Yang; Bo-Bo Zhang (Food Bioscience, 2023)

Production of biochar from squeezed liquid of fruit and vegetable waste: Impacts on soil N2O emission and microbial community - Xiaoxuan Liu; Cancan Jiang; Yu Qin; Cong Wang; Jinglin Wang; Xiaoxu Zheng; Mairemu Maihaiti; Xupo Zhang; Shuanglong Ma; Shengjun Xu; Xuliang Zhuang (Environmental Research, 2023)

Silver-induced adsorption optimization of adjacent Co tetrahedral sites for enhanced oxygen reduction/evolution reaction - Can-Wen Yu; Cong-Yi Du; Ting Ouyang; Xi-Ting Zhang; Zhao-Qing Liu (Chemical Engineering Journal, 2023)

Elucidation of the neutralizing antibody evasion of emergent SARS-CoV-2 Omicron sub-lineages using structural analysis - Cong Sun; Yuan-Tao Liu; Yin-Feng Kang; Chu Xie; Shu-Xin Li; Yu-Tong Lu; Mu-Sheng Zeng (Science China Life Sciences, 2023)

Peripheral BDNF Regulates Somatosensory–Sympathetic Coupling in Brachial Plexus Avulsion-Induced Neuropathic Pain - Hang Xian; Huan Guo; Yuan-Ying Liu; Jian-Lei Zhang; Wen-Chao Hu; Ming-Jun Yu; Rui Zhao; Rou-Gang Xie; Hang Zhang; Rui Cong (Neuroscience Bulletin, 2023)

Constructing and Validating a Network of Potential Olfactory Sheathing Cell Transplants Regulating Spinal Cord Injury Progression - Yan Zhang; Yu-shen Yang; Wei-can Chen; Cong-mei Wang; He-fan He (Molecular Neurobiology, 2023)

Parerythrobacter aestuarii sp. nov., Isolated from Seawater in the Tidal Region of Taizhou - Han Dong; Ren-Zhuang Han; Yu Zhang; Maripat Xamxidin; Peng Zhou; Cong Sun; Wu Qu; Lin Xu (Current Microbiology, 2023)

White matter alterations in mild cognitive impairment revealed by meta-analysis of diffusion tensor imaging using tract-based spatial statistics - Longfei Li; Wei Yang; Yu Wan; Hailong Shen; Ting Wang; Liangliang Ping; Chuanxin Liu; Min Chen; Hao Yu; Shushu Jin; Yuqi Cheng; Xiufeng Xu; et al. (Brain Imaging and Behavior, 2023)

Numerical study on a semi-mechanistic wall boiling model based on dry-patch mechanism for CHF prediction in vertical tube and fuel assembly - Xiang Zhang; Genglei Xia; Minjun Peng; Chunyan He; Tenglong Cong; Hao Yu (Annals of Nuclear Energy, 2023)

Applying sheet iron to enhance the treatment efficiency of digested effluent with continuous flow and the corresponding mechanism - Cong Ding; Li-bin Chen; Li-ping Yu; Ru Wang; Lin-jiang Yuan; Lan Wang; Liang-wei Deng (Chemosphere, 2023)

Adverse effects of thiamethoxam on the behavior, biochemical responses, hepatopancreas health, transcriptome and intestinal flora of juvenile Chinese mitten crab (Eriocheir sinensis) - Yiwen Yang; Cong Zhang; Xiaodan Wang; Qiuran Yu; Long He; Xinyu Cai; Erchao Li; Chuanjie Qin; Jianguang Qin; Liqiao Chen (Chemosphere, 2023)

Identification and localization of grape diseased leaf images captured by UAV based on CNN - Weihan Li; Xiao Yu; Cong Chen; Qi Gong (Computers and Electronics in Agriculture, 2023)

Derivation of nonstationary rainfall intensity-duration-frequency curves considering the impacts of climate change and urbanization - Lei Yan; Dongyang Lu; Lihua Xiong; Hongfeng Wang; Qinghua Luan; Cong Jiang; Bin Xiong; Wentao Xu; Pengtao Yan; Qingwen Lei; Chong-Yu Xu (Urban Climate, 2023)

Toxicity of leachate from smoked cigarette butts to terrestrial animals: A case study on the earthworm Eisenia fetida - Yu Xi; Leiyu Diao; Ziyi Wang; Zi Jin; Yilin Wang; Wenhua Liu; Dongsheng Wen; Hongxin Li; Cong Sun; Jiqi Lu (Science of The Total Environment, 2023)

Petrogenesis of Neoproterozoic high-K intrusion in the southwestern Yangtze Block, South China: Implication for the recycled subducted-sediment in the mantle source - Xiu-wei Jiang; Shao-cong Lai; Yu Zhu; Jiang-feng Qin; Ren-zhi Zhu; Min Liu; Hang Yang; Zhen Yang; Wen-bin Xue (Precambrian Research, 2023)

Reverse genetic study reveals the molecular targets of chordotonal organ TRPV channel modulators - Yu-Xuan Peng; Zhao-Yu Liu; Pin-Xuan Lin; Shao-Cong Su; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2023)

Numerical simulation of the interaction between waves and pile breakwater with horizontal slotted plates - Jingmao Peng; Ke Li; Shuitao Gu; Yu Cong (Ocean Engineering, 2023)

Enhanced denitrification of the AO-MBBR system used for expressway service area sewage treatment: A new perspective on decentralized wastewater treatment - Xin Xing; Xin Yuan; Yu Zhang; Cong Men; Zhuowei Zhang; Xiaoying Zheng; Dong Ni; Huatian Xi; Jiane Zuo (Journal of Environmental Management, 2023)

Insights into the in vitro digestibility of pork myofibrillar protein with different ionic polysaccharides from the perspective of gel characteristics - Xia Yu; Xi-xi Wang; Li-fang Zou; Ke-zhou Cai; Jing-zhi Pan; Cong-gui Chen (Food Chemistry, 2023)

Systemic subchronic toxicity and comparison of four selenium nutritional supplements by 90-day oral exposure in Sprague-Dawley rats - Lu Yu; Yanmei Li; Wen Qu; Yanhua Zheng; Xuejiao Chen; Shaohua Fu; Jingjing Qu; Jie Tian; Shuiyuan Cheng; Xin Cong; Bolin Fan; Chunhong Wang (Food and Chemical Toxicology, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Experimental and numerical study of PEN FRP-strengthened circular RC columns under lateral cyclic loading with high axial compression ratio - Yu-Lei Bai; Shang-Cong Bai; Shi-Jie Mei; Jun-Feng Jia (Engineering Structures, 2023)

Insights into the surface Structure-Sensitive photocatalytic oxidation of gaseous toluene on Pd/TiO2 catalysts - Cong Wu; Qinglong Liu; Yu Zhan; Wei Tan; Xiaoqian Wei; Qing Tong; Haiqin Wan; Lin Dong (Chemical Engineering Journal, 2023)

Novel supramolecular deep eutectic solvent pretreatment for obtaining fluorescent lignin and promoting biomass pyrolytic saccharification - Zhiwen Jia; Shiyang Wang; Haipeng Yu; Wanyu Li; Jiamin Ye; Yihao Hu; Cong Liu; Zijian Ye; Yan Sun; Xiwei Xu (Bioresource Technology, 2023)

Bi0·5Na0·5TiO3/ZnO Z-scheme heterojunction for piezo-photocatalytic water remediation: Mechanical energy harvesting and energy band configuration - Peng Wang; Wanqian Cai; Fangyuan Yu; Ping Zhou; Mei Lin; Cong Lin; Tengfei Lin; Min Gao; Chunlin Zhao; Xiangqi Li; Xiao Wu (Chemosphere, 2023)

The evolution of insecticide resistance in the white backed planthopper Sogatella furcifera (Horvath) of China in the period 2014–2022 - Ya-Ting Liu; Xin-Yu Song; Bin Zeng; Wen-Jing Zhang; Xing-Yu Chen; Ze-Rui Feng; Hua-Yang Yu; Cong-Fen Gao; Shun-Fan Wu (Crop Protection, 2023)

A bottom-up approach for community load prediction based on multi-agent model - Zuoxiang Yu; Cong Song; Yanfeng Liu; Dengjia Wang; Bojia Li (Sustainable Cities and Society, 2023)

Insights into the roles and mechanisms of a green-prepared magnetic biochar in anaerobic digestion of waste activated sludge - Hong-Yu Jin; Lei Yang; Yong-Xiang Ren; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Zhihua Li; Aijie Wang; Zhang-Wei He (Science of The Total Environment, 2023)

Reduced graphene oxide supported CoFe2O4 composites with enhanced peroxymonosulfate activation for the removal of sulfamethoxazole: Collaboration of radical and non-radical pathways - Adeel Ahmed; Muhammad Usman; Zhijian Ji; Muhammad Rafiq; Raza Ullah; Bing Yu; Youqing Shen; Hailin Cong (Journal of Environmental Chemical Engineering, 2023)

Neoproterozoic tectonic transition from subduction to back-arc extension along the western Yangtze Block, South China: Petrological evidence of Nb-enriched basalts and arc-type intrusive rocks - Yu Zhu; Shao-cong Lai; Wan-li Xie; Jiang-feng Qin; Ren-zhi Zhu; Shao-wei Zhao; Min Liu; Fang-yi Zhang; Ze-zhong Zhang; Hang Yang (Gondwana Research, 2023)

Quantitative characterization of water transport and wetting patterns in coal using LF-NMR and FTIR techniques - Yuliang Cai; Cheng Zhai; Xu Yu; Yong Sun; Jizhao Xu; Yangfeng Zheng; Yuzhou Cong; Yujie Li; Aikun Chen; Hexiang Xu; Shuai Wang; Xizhuo Wu (Fuel, 2023)

Corrigendum to “Ca2+ plays an antiviral role by increasing p53 expression to achieve protection against spring viraemia of carp virus infection” [Fish Shellfish Immunol. 102 (2020) 449–459/455] - Long-Feng Lu; Xiao-Yu Zhou; Can Zhang; Zhuo-Cong Li; Dan-Dan Chen; Yong-An Zhang; Shun Li (Fish & Shellfish Immunology, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Grazing and reclamation-induced microbiome alterations drive organic carbon stability within soil aggregates in alpine steppes - Yang Hu; Guangling Yu; Jianqin Zhou; Kaihui Li; Mo Chen; Maidinuer Abulaizi; Mengfei Cong; Zailei Yang; Xinping Zhu; Hongtao Jia (CATENA, 2023)

A tradeoff between denitrification and nitrate leaching into the subsoil in nitrate-rich vegetable soils treated by reductive soil disinfestation - Hui-Min Zhang; Yu Liu; Ying-Hua Zhang; Yong Li; Zhao-Xiong Chen; Xin Sun; Hang Jing; Jing Wang; Ahmed S. Elrys; Mao-Heng Zhang; Zu-Cong Cai; Yi Cheng (Agriculture, Ecosystems & Environment, 2023)

Data‐driven estimation of nitric oxide emissions from global soils based on dominant vegetation covers - Xingshuai Tian; Yulong Yin; Kai He; Ruonan Qiu; Jiahui Cong; Zihan Wang; Huitong Yu; Zhong Chen; Yiyan Chu; Hao Ying; Zhenling Cui (Global Change Biology, 2023)
Soils are a major source of global nitric oxide (NO) emissions. However, estimates of soil NO emissions have large uncertainties due to limited observations and multifactorial impacts. Here, we mapped global soil NO emissions, integrating 1356 in‐situ NO observations from globally distributed sites with high‐resolution climate, soil, and management practice data. We then calculated global and national total NO budgets and revealed the contributions of cropland, grassland, and forest to global soil NO emissions at the national level. The results showed that soil NO emissions were explained mainly by N input, water input and soil pH. Total above‐soil NO emissions of the three vegetation cover types were 9.4 Tg N year −1 in 2014, including 5.9 Tg N year −1 (1.04, 95% confidence interval [95% CI]: 0.09–1.99 kg N ha −1 year −1 ) emitted from forest, 1.7 Tg N year −1 (0.68, 95% CI: 0.10–1.26 kg N ha −1 year −1 ) from grassland, and 1.8 Tg N year −1 (0.98, 95% CI: 0.42–1.53 kg N ha −1 year −1 ) from cropland. Soil NO emissions in approximately 57% of 213 countries surveyed were dominated by forests. Our results provide updated inventories of global and national soil NO emissions based on robust data‐driven models. These estimates are critical to guiding the mitigation of soil NO emissions and can be used in combination with biogeochemical models.

Bisphenol A decreases the developmental toxicity and histopathological alterations caused by polystyrene nanoplastics in developing marine medaka Oryzias melastigma - Fuwei Yu; Fei Jin; Yi Cong; Yadi Lou; Zhaochuan Li; Ruijing Li; Baojun Ding; Ying Wang; Jingwen Chen; Juying Wang (Chemosphere, 2023)

Identification and contribution of potential sources to atmospheric lead pollution in a typical megacity: Insights from isotope analysis and the Bayesian mixing model - Wen-Jing Dai; Xiao-Dong Li; Yu-Cong Fu; Shi-Yuan Ding; Qin-Kai Li; Zhi-Qi Zhao (Science of The Total Environment, 2023)

Parallel paired electrolysis-enabled asymmetric catalysis: simultaneous synthesis of aldehydes/aryl bromides and chiral alcohols - Bing Sun; Zhen-Hua Wang; Yun-Zhao Wang; Yu-Cheng Gu; Cong Ma; Tian-Sheng Mei (Science Bulletin, 2023)

Emissions of formaldehyde and nitrogen dioxide from liquefied petroleum gas combustion - Jin Ye; Siming Shi; Tao Yu; Cong Liu; Jingguang Li; Zhen Ding; Zhijiong Huang; Hua Qian (Process Safety and Environmental Protection, 2023)

Diatom evidence for late Holocene environmental change in a permafrost peatland in the northern Greater Khingan Mountains, Northeast China - Dongxue Han; Yang Sun; Zicheng Yu; Ming Jiang; Jinxin Cong; Chuanyu Gao; Guoping Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Loss of OsARF18 function confers glufosinate resistance in rice - Jin-Qiu Xia; Da-Yu He; Qin-Yu Liang; Zheng-Yi Zhang; Jie Wu; Zi-Sheng Zhang; Jing Zhang; Lin Wang; Cong-He Zhang; Ping-Xia Zhao; Cheng-Bin Xiang (Molecular Plant, 2023)

Computer-aided discovery of a novel thermophilic laccase for low-density polyethylene degradation - Yan Zhang; Thea Jess Plesner; Yi Ouyang; Yu-Cong Zheng; Etienne Bouhier; Emilie Ingemann Berentzen; Mingliang Zhang; Pengfei Zhou; Wolfgang Zimmermann; Gregers Rom Andersen; Bekir Engin Eser; Zheng Guo (Journal of Hazardous Materials, 2023)

Simultaneous and rapid screening of live and dead E. coli O157:H7 with three signal outputs: An all-in-one biosensor using phage-apoferritin@CuO2 signal tags on MXenes-modified electrode platform - Shu Xiao; Cong Cao; Tinghong Ming; Yuting Cao; Zhenzhong Yu; Ning Gan (Journal of Hazardous Materials, 2023)

Soil moisture dominates the interannual variability in alpine ecosystem productivity by regulating maximum photosynthetic capacity across the Qinghai-Tibetan Plateau - Tao Zhang; Yuanyuan Tang; Mingjie Xu; Guang Zhao; Nan Cong; Zhoutao Zheng; Juntao Zhu; Ben Niu; Zhi Chen; Yangjian Zhang; Ning Chen; Yongtao He; et al. (Global and Planetary Change, 2023)

A review of anorexia induced by T-2 toxin - Ting-Yu Huang; Wen-Xi Song; You-Shuang Wang; Yu Liu; Feng-Juan Chen; Yun-He Chen; Yi-Bao Jiang; Cong Zhang; Xu Yang (Food and Chemical Toxicology, 2023)

Adsorption-enhanced photocatalytic waterborne virus inactivation by graphite carbon nitride conjugated with covalent organic frameworks - Lu Zhang; Tianhao Xi; Dongyang Zhu; Hongchen Shen; Weiheng Su; Pingfeng Yu; Cong Lyu (Chemical Engineering Journal, 2023)

A novel robust phosphate-functionalized metal–organic framework for deep desulfurization at wide temperature - Cong Yu; Peixin Zhang; Qi Ding; Lifeng Yang; Xian Suo; Xili Cui; Huabin Xing (Chemical Engineering Journal, 2023)

Neuroprotective effect of salidroside on hippocampal neurons in diabetic mice via PI3K/Akt/GSK-3β signaling pathway - Xue-Hua Wang; Zhong-Fu Zuo; Lu Meng; Qi Yang; Pan Lv; Li-Pan Zhao; Xiao-Bai Wang; Yu-Fei Wang; Ying Huang; Cong Fu; Wen-Qiang Liu; Xue-Zheng Liu; et al. (Psychopharmacology, 2023)

Agricultural ditches are hotspots of greenhouse gas emissions controlled by nutrient input - Wenxin Wu; Xueqi Niu; Zhifeng Yan; Siyue Li; Sophie A. Comer-Warner; Hanqin Tian; Si-Liang Li; Jianwen Zou; Guirui Yu; Cong-Qiang Liu (Water Research, 2023)

Organic carbon preservation in wetlands: Iron oxide protection vs. thermodynamic limitation - Fu-Sheng Sun; Chao Ma; Guang-Hui Yu; Yakov Kuzyakov; Yun-Chao Lang; Ping-Qing Fu; Li-Jun Guo; Hui Henry Teng; Cong-Qiang Liu (Water Research, 2023)

Transcription factor ELK1 regulates the expression of histone 3 lysine 9 to affect developmental potential of porcine preimplantation embryos - Yuanshen Zhao; Yanhui Zhai; Cong Fu; Lijing Shi; Xiangjie Kong; Qi Li; Hao Yu; Xinglan An; Sheng Zhang; Ziyi Li (Theriogenology, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Design of biomass-based N, S co-doped porous carbon via a straightforward post-treatment strategy for enhanced CO2 capture performance - Meng Cao; Yu Shu; Qiuhong Bai; Cong Li; Bang Chen; Yehua Shen; Hiroshi Uyama (Science of The Total Environment, 2023)

Inhibition of ecdysone receptor (DcEcR) and ultraspiracle (DcUSP) expression in Diaphorina citri increased susceptibility to pesticides - Cong Zhang; Bin Wan; Meng-Ru Jin; Xi Wang; Yu-Jing Wei; Ling Zhong; Bin Xia (Pesticide Biochemistry and Physiology, 2023)

Efficient photocatalytic simultaneous removal of organic and heavy metal complex pollutants under visible light by crystal-facet-mediated TiO2/Ti3C2-BiOBr nanocomposites - Xin Chen; Qianwei Liang; Wenjing Gao; Jianyu Liu; Ziyu Zhao; Meng Yu; Cong Jiang; Jianqiang Hu (Journal of Water Process Engineering, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

Detection of walnut oil adulterated with high-linoleic acid vegetable oils using triacylglycerol pseudotargeted method based on SFC-QTOF-MS - Jing-Jing Zhang; Yan Gao; Mei-Ling Zhao; Xiao Xu; Bo-Nan Xi; Li-Ke Lin; Jing-Yi Zheng; Bang Chen; Yu Shu; Cong Li; Yehua Shen (Food Chemistry, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Effects of self-produced lactic fermentation (SPLF) on GHG and VSC emissions during swine slurry storage - Qunxin Cong; Yue Wang; Yu Zhang; Fubin Yin; Wanqin Zhang; Tiantian Cao; Hongmin Dong (Environmental Research, 2023)

T-2 toxin metabolism and its hepatotoxicity: New insights on the molecular mechanism and detoxification - Wenxi Song; Youshuang Wang; Tingyu Huang; Yu Liu; Fengjuan Chen; Yunhe Chen; Yibao Jiang; Cong Zhang; Xu Yang (Environmental Pollution, 2023)

Enlocking the high Zn2+-storage of conversion-type Te cathode by regulating the surface binding-interaction with graphene - Cong Guo; Shangjun Yi; Rui Si; Yixiao Wang; He Liu; Feng Yu; Jingfa Li (Chemical Engineering Journal, 2023)

Source analysis of metals in the tea plant using linear correlation analysis combined with a lead-strontium isotope tracer - Yan Cong; Rui-lian Yu; Yu Yan; Bo-sen Weng; Gong-ren Hu; Jing-wei Sun; Jian-yong Cui; YanYan; Yao-yi Huang (CATENA, 2023)

Pore Structure and Damage Evaluation of Hot Dry Rocks in Enhanced Geothermal System by Combining Electrical Resistivity, Ultrasonic Waves and Nuclear Magnetic Resonance - Yong Sun; Cheng Zhai; Xu Yu; Jizhao Xu; Yuzhou Cong; Yangfeng Zheng; Wei Tang; Yujie Li (Natural Resources Research, 2023)

Real-time recombinase-aided amplification assay for rapid amplification of the IS1081 gene of Mycobacterium tuberculosis - Yuanyuan Liu; Weicong Ren; Zhongtan Xue; Yuedong Miao; Wei Wang; Xuxia Zhang; Cong Yao; Yuanyuan Shang; Shanshan Li; Fengling Mi; Yu Pang (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Magnetic nanoparticle-assisted colonization of synthetic bacteria on plant roots for improved phytoremediation of heavy metals - Cong Shi; Zirun Zhao; Nali Zhu; Qilin Yu (Chemosphere, 2023)

Analysis of influencing factors of the projectile entering the water through the ice hole - Xinyu Hu; Yingjie Wei; Cong Wang; Jiarui Wang; Delei Yu; Qian Yang; Yulin Wang (Ocean Engineering, 2023)

Upregulation of mitochondrial calcium uniporter contributes to paraquat-induced neuropathology linked to Parkinson’s disease via imbalanced OPA1 processing - Weixia Duan; Cong Liu; Jie Zhou; Qin Yu; Yu Duan; Tian Zhang; Yuanyuan Li; Guanyan Fu; Yapei Sun; Jiacheng Tian; Zhiqin Xia; Yingli Yang; et al. (Journal of Hazardous Materials, 2023)

Enhanced viability of probiotics encapsulated within synthetic/natural biopolymers by the addition of gum arabic via electrohydrodynamic processing - Jiage Ma; Tianzhu Li; Qingyun Wang; Cong Xu; Wei Yu; Hongliang Yu; Wan Wang; Zhibiao Feng; Lijun Chen; Juncai Hou; Zhanmei Jiang (Food Chemistry, 2023)

Constructing a three-dimensional creep model for rocks and soils based on memory-dependent derivatives: A theoretical and experimental study - Liming Zhang; Deng Zhang; Zaiquan Wang; Yu Cong; Xiaoshan Wang (Computers and Geotechnics, 2023)

MiR-370-3p aggravates blood–brain barrier injury and neuron apoptosis by targeting SMURF1 to activate the TLR4/MyD88/NF-κB signaling in sepsis-associated encephalopathy - Neng Wang; Dan Zhong; Jie Lin; Mei Ye; Yu Chen; Lili Wang; Mei Chen; Cong Luo (Molecular & Cellular Toxicology, 2023)

Understanding traffic bottlenecks of long freeway tunnels based on a novel location-dependent lighting-related car-following model - Shanchuan Yu; Cong Zhao; Lang Song; Yishun Li; Yuchuan Du (Tunnelling and Underground Space Technology, 2023)

Protective effects of electroacupuncture on polycystic ovary syndrome in rats: Down-regulating Alas2 to inhibit apoptosis, oxidative stress, and mitochondrial dysfunction in ovarian granulosa cells - Jing Cong; Mubai Li; Yu Wang; Hongli Ma; Xinming Yang; Jingshu Gao; Long Wang; Xiaoke Wu (Tissue and Cell, 2023)

Middle–Late Ordovician brachiopods from Ningnan, southern Sichuan Province, Southwest China: Implications for macroevolution and palaeogeography - Yong Wang; Ren-Bin Zhan; Xiao-Cong Luan; Yu-Chen Zhang; Xin Wei (Palaeoworld, 2023)

Darriwilian–Sandbian (Middle–Late Ordovician) shallow warm-water deposits in the Upper Yangtze region, South China: A case study from the Qiaojia area, northeastern Yunnan Province - Xiao-Cong Luan; Xiao-Le Zhang; Qi-Jian Li; Yong Wang; Yu-Nong Cui; Ren-Bin Zhan (Palaeoworld, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

BOD/COD ratio as a probing index in the O/H/O process for coking wastewater treatment - Gengrui Wei; Tuo Wei; Zemin Li; Cong Wei; Qiaoping Kong; Xianghong Guan; Guanglei Qiu; Yun Hu; Chaohai Wei; Shuang Zhu; Yu Liu; Sergei Preis (Chemical Engineering Journal, 2023)

Ag-modification argyrodite electrolytes enable high-performance for all-solid-state lithium metal batteries - Zhongkai Wu; Chuang Yu; Chaochao Wei; Ziling Jiang; Cong Liao; Shuai Chen; Shaoqing Chen; Linfeng Peng; Shijie Cheng; Jia Xie (Chemical Engineering Journal, 2023)

Inhibition of Toll-Like Receptor 4 Signaling Pathway Accelerates the Repair of Avascular Necrosis of Femoral Epiphysis through Regulating Macrophage Polarization in Perthes Disease - Ronghui Yu; Cong Ma; Guoyong Li; Jianyun Xu; Dan Feng; Xia Lan (Tissue Engineering and Regenerative Medicine, 2023)

Microstructure Evolution of Bituminous Coal Modified by High-Pressure CO2 Foam Fracturing Fluid with Different Treatment Times - Yangfeng Zheng; Cheng Zhai; Aikun Chen; Yong Sun; Yuzhou Cong; Wei Tang; Jizhao Xu; Xu Yu; Xinyu Zhu; Yujie Li (Natural Resources Research, 2023)

Dinotefuran resistance in Nilaparvata lugens: resistance monitoring, inheritance, resistance mechanism and fitness costs - Yan-Chao Zhang; Zhi-Tao Yu; Yang Gao; Wen-Nan Ye; Yu-Xuan Peng; Shuai Zhang; Cong-Fen Gao (Journal of Pest Science, 2023)

LncRNA SLC25A21-AS1 increases the chemosensitivity and inhibits the progression of ovarian cancer by upregulating the expression of KCNK4 - Ke Huang; Xiyi Chen; Zhe Geng; Xueyou Xiong; Yu Cong; Xinxing Pan; Siyu Liu; Lili Ge; Juan Xu; Xuemei Jia (Functional & Integrative Genomics, 2023)

Different cold tolerances among three strains of large yellow croaker: related to antioxidant defense and energy metabolism - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Hui Zhang; Yu-Cong Huang; Wei-Guang Zou (Fish Physiology and Biochemistry, 2023)

Portable smartphone-assisted ratiometric fluorescence sensor for visual detection of glucose - Xiaohui Zhang; Bo Sun; Yunyi Zhang; Qingfeng Zhang; Mahmood Hassan Akhtar; Ming Li; Yuwei Gu; Cong Yu (Analytica Chimica Acta, 2023)

Field measures of strengthen plant-microbial remediation of PAHs-FQs compound pollution - Lei Zhao; Zhenzhen Han; Mengying Zhou; Cong Lyu; Yu Li (Environmental Science and Pollution Research, 2023)

Preparation of high-quality alkylated gasoline with low alkane-to-alkene ratio catalyzed by polyether-based Brønsted-Lewis acidic deep eutectic solvent - Ying-Bin Jiang; Feng-Li Yu; Bing Yuan; Cong-Xia Xie; Shi-Tao Yu (Fuel, 2023)

Conversion of lignite-derived volatiles into aromatics over Zn@MCM-41 and ZSM-5 tandem catalysts with a high stability - Xiao-Yan Zhao; Xue-Yu Ren; Yan-Jun Wang; Jing-Pei Cao; Zi-Meng He; Nai-Yu Yao; Hong-Cun Bai; Hou-Luo Cong (Fuel, 2023)

Deoxynivalenol induces testicular ferroptosis by regulating the Nrf2/System Xc−/GPX4 axis - Xu Yang; Tingyu Huang; Yunhe Chen; Fengjuan Chen; Yu Liu; Youshuang Wang; Wenxi Song; Juntao Zhang; Yibao Jiang; Fangyu Wang; Cong Zhang (Food and Chemical Toxicology, 2023)

Soil nitrogen transformation in different land use and implications for karst soil nitrogen loss controlling - Zhong-Jun Wang; Fu-Jun Yue; Li-Li Xue; Yu-Chun Wang; Cai-Qing Qin; Jie Zeng; Hu Ding; Yu-Cong Fu; Si-Liang Li (CATENA, 2023)

Resveratrol-induced SIRT1 activation inhibits glycolysis-fueled angiogenesis under rheumatoid arthritis conditions independent of HIF-1α - Tian-Tian Jiang; Cong-Lan Ji; Li-Jun Yu; Meng-Ke Song; Yan Li; Qiang Liao; Tuo Wei; Opeyemi Joshua Olatunji; Jian Zuo; Jun Han (Inflammation Research, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Single-atom boosted electrochemiluminescence via phosphorus doping of Fe–N/P–C catalysts - Yu-Xin Yang; Qian-Nan He; Cong-Hui Xu; Rida Javed; Hongbin Zhao; Daixin Ye; Wei Zhao (Analytica Chimica Acta, 2023)

Low-temperature phenol-degrading microbial agent: construction and mechanism - Yu Yang; Yu Zhang; Cong Liu; Zhiqiang Su; Ruizhi Zhao; Jiti Zhou (Archives of Microbiology, 2023)

Aestuariibaculum lutulentum sp. nov., a marine bacterium isolated from coastal sediment in Beihai - Jia-Wei Gao; Dong-Yan He; Wen-Wu Zhang; Yu-Ruo Wang; Yue Su; Jun-Jie Ying; Zhi-Cheng Wu; Wu Qu; Lin Xu; Cong Sun (Archives of Microbiology, 2023)

Evaluation of the Added Value of Probabilistic Nowcasting Ensemble Forecasts on Regional Ensemble Forecasts - Lu Yang; Cong-Lan Cheng; Yu Xia; Min Chen; Ming-Xuan Chen; Han-Bin Zhang; Xiang-Yu Huang (Advances in Atmospheric Sciences, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

On the extinction depth of freezing-induced groundwater migration - Xiao-Wei Jiang; Hong-Yu Xie; Shemin Ge; Han Tang; Shu-Cong Tan; Xu-Sheng Wang; Li Wan; Yijian Zeng (Journal of Hydrology, 2023)

Prediction of zebrafish embryonic developmental toxicity by integrating omics with adverse outcome pathway - Xiao Gou; Cong Ma; Huimin Ji; Lu Yan; Pingping Wang; Zhihao Wang; Yishan Lin; Nivedita Chatterjee; Hongxia Yu; Xiaowei Zhang (Journal of Hazardous Materials, 2023)

Fe(II)-mediated transformation of schwertmannite associated with calcium from acid mine drainage treatment - Cong Fan; Chuling Guo; Wei Chen; Guining Lu; Yu Shen; Zhi Dang (Journal of Environmental Sciences, 2023)

Immunization effect of recombinant Lactobacillus casei displaying Aeromonas veronii Aha1 with an LTB adjuvant in carp - Xue Jiao; Dong-Xing Zhang; Chong Chen; Ling-cong Kong; Xiao-Yu Hu; Xiao-Feng Shan; Ai-Dong Qian (Fish & Shellfish Immunology, 2023)

Oral vaccination with recombinant Lactobacillus casei with surface displayed OmpK fused to CTB as an adjuvant against Vibrio mimicus infection in Carassius auratus - Hong-Jin Li; Bin-Tong Yang; Yu-Feng Sun; Tong Zhao; Zhi-Peng Hao; Wei Gu; Meng-Xia Sun; Wei Cong; Yuan-Huan Kang (Fish & Shellfish Immunology, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Risk assessment and landslide prevention design using numerical modelling — A case study in Qingliu, China - Cong-jiang Li; Yu-xiang Hu; Nan Jiang; Hai-bo Li; Jia-wen Zhou (Journal of Mountain Science, 2023)

A Storage-Saving Quadtree-Based Multibeam Bathymetry Map Representation Method - Zheng Cong; Teng Ma; Ye Li; Mingxiao Yuan; Yu Ling; Haohan Du; Chi Qi; Ziyuan Li; Shuo Xu; Qiang Zhang (Journal of Marine Science and Engineering, 2023)
With the rapid advancement of the simultaneous localization and mapping (SLAM) technology, the collaboration of several autonomous underwater vehicles (AUVs) in large-scale seafloor imaging has become a trending topic. Electromagnetic waves are difficult to transfer underwater, the only viable method of communication is acoustic transmission, but its bandwidth is limited. Therefore, how to compress and process multibeam bathymetry maps so that AUVs can acquire maps gathered by other AUVs has become an important topic of study. This study presents a representation approach for multibeam bathymetry maps based on a quadtree structure. In comparison to the girding approach, the sparse pseudo-input Gaussian processes (SPGPs) method, and the octree-based method, the quadtree-based method suggested in this study preserves precision while compressing storage space. Experiments utilizing field data validate the performance of the proposed technique, and the method’s ability to compress storage space towards an AUV cooperative SLAM’s scenario.

The mechanism of rh-endostatin-induced cardiotoxicity and its protection by dihydromyricetin[in vivo/in vitro, C57BL/6 mice, AC16 and hiPSC-CMs] - Xiaoran Guan; Wuquan Li; Yong Wang; Qun Zhao; Xinru Yu; Jing Jiang; Weihua Bian; Cong Xu; Yeying Sun; Chunxiang Zhang (Toxicology Letters, 2023)

Cardamine violifolia as a potential Hg hyperaccumulator and the cellular responses - Liwei Cui; Xue Tian; Hongxin Xie; Xin Cong; Lihong Cui; Han Wu; Jianxu Wang; Bai Li; Jiating Zhao; Yanshan Cui; Xinbin Feng; Yu-Feng Li (Science of The Total Environment, 2023)

Enhancement of organics and nutrient removal and microbial mechanism in vertical flow constructed wetland under a static magnetic field - Cong Li; Likui Feng; Jianjun Lian; Xiaoting Yu; Chunzhen Fan; Zhen Hu; Haiming Wu (Journal of Environmental Management, 2023)

Purification performance from bypass ecological treatment systems treating WWTPs effluents and improvement of water quality in receiving rivers: A case study in southern China - Xiaoxu Zheng; Shengjun Xu; Yeliang Bi; Gong Cheng; Shuanglong Ma; Hao Zhang; Cancan Jiang; Cong Wang; Ping Lyu; Yu Qin; Xuliang Zhuang (Journal of Environmental Management, 2023)

Sulfide-driven nitrous oxide recovery during the mixotrophic denitrification process - Cong Yu; Sen Qiao; Jiti Zhou (Journal of Environmental Sciences, 2023)

l-Tartaric acid tailored polyamide thin-film composite membrane with enhanced performance for salt and molecular removal - Yuhua Xiong; Xingtao Zuo; Jiajie He; Juan Xiong; Cong Ma; Zhongbing Chen; Yun Zhou; Shuili Yu (Desalination, 2023)

Aerobic glycolysis in colon cancer is repressed by naringin via the HIF1A pathway - Guangtao Pan; Ping Zhang; Aiying Chen; Yu Deng; Zhen Zhang; Han Lu; Aoxun Zhu; Cong Zhou; Yanran Wu; Sen Li (Journal of Zhejiang University-SCIENCE B, 2023)

Prediction and significance of intra-platform shoals distribution of Changxing formation in Gaoshiti area of Sichuan Basin - Dong Wang; Hong Liu; Tong Yu; Minglong Li; Lei Tan; Kun Zhang; Chao Geng; Cong Chen (Carbonates and Evaporites, 2023)

Integrating oculomics with genomics reveals imaging biomarkers for preventive and personalized prediction of arterial aneurysms - Yu Huang; Cong Li; Danli Shi; Huan Wang; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Yijun Hu; Shulin Tang; Shunming Liu; Songyuan Luo; et al. (EPMA Journal, 2023)
Objective Arterial aneurysms are life-threatening but usually asymptomatic before requiring hospitalization. Oculomics of retinal vascular features (RVFs) extracted from retinal fundus images can reflect systemic vascular properties and therefore were hypothesized to provide valuable information on detecting the risk of aneurysms. By integrating oculomics with genomics, this study aimed to (i) identify predictive RVFs as imaging biomarkers for aneurysms and (ii) evaluate the value of these RVFs in supporting early detection of aneurysms in the context of predictive, preventive and personalized medicine (PPPM). Methods This study involved 51,597 UK Biobank participants who had retinal images available to extract oculomics of RVFs. Phenome-wide association analyses (PheWASs) were conducted to identify RVFs associated with the genetic risks of the main types of aneurysms, including abdominal aortic aneurysm (AAA), thoracic aneurysm (TAA), intracranial aneurysm (ICA) and Marfan syndrome (MFS). An aneurysm-RVF model was then developed to predict future aneurysms. The performance of the model was assessed in both derivation and validation cohorts and was compared with other models employing clinical risk factors. An RVF risk score was derived from our aneurysm-RVF model to identify patients with an increased risk of aneurysms. Results PheWAS identified a total of 32 RVFs that were significantly associated with the genetic risks of aneurysms. Of these, the number of vessels in the optic disc (‘ntreeA’) was associated with both AAA ( β = −0.36, P = 6.75e−10) and ICA ( β = −0.11, P = 5.51e−06). In addition, the mean angles between each artery branch (‘curveangle_mean_a’) were commonly associated with 4 MFS genes ( FBN1 : β = −0.10, P = 1.63e−12; COL16A1 : β = −0.07, P = 3.14e−09; LOC105373592 : β = −0.06, P = 1.89e−05; C8orf81/LOC441376 : β = 0.07, P = 1.02e−05). The developed aneurysm-RVF model showed good discrimination ability in predicting the risks of aneurysms. In the derivation cohort, the C -index of the aneurysm-RVF model was 0.809 [95% CI: 0.780–0.838], which was similar to the clinical risk model (0.806 [0.778–0.834]) but higher than the baseline model (0.739 [0.733–0.746]). Similar performance was observed in the validation cohort, with a C -index of 0.798 (0.727–0.869) for the aneurysm-RVF model, 0.795 (0.718–0.871) for the clinical risk model and 0.719 (0.620–0.816) for the baseline model. An aneurysm risk score was derived from the aneurysm-RVF model for each study participant. The individuals in the upper tertile of the aneurysm risk score had a significantly higher risk of aneurysm compared to those in the lower tertile (hazard ratio = 17.8 [6.5–48.8], P = 1.02e−05). Conclusion We identified a significant association between certain RVFs and the risk of aneurysms and revealed the impressive capability of using RVFs to predict the future risk of aneurysms by a PPPM approach. Our finds have great potential to support not only the predictive diagnosis of aneurysms but also a preventive and more personalized screening plan which may benefit both patients and the healthcare system. Graphical abstract

RNA-seq analysis reveals the effect of the metamorphic cue (juvenile oysters) on the Rapana venosa larvae - Mei-Jie Yang; Ying Shi; Zhi-Shu Lin; Pu Shi; Zhi Hu; Cong Zhou; Peng-Peng Hu; Zheng-Lin Yu; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
As a vital developmental event, metamorphosis controls the population dynamics of most marine invertebrates and affects the breeding of economic shellfish. Rapana venosa is an economically important species in China, but artificial aquaculture has hampered its metamorphosis process. Previous studies have found that juvenile oysters can effectively induce the metamorphosis of R. venosa , but the specific induction mechanism is not clear. Here, we investigated the mechanism underlying the response of R. venosa to juvenile oysters through the RNA-seq analysis. In this study, the gene set responses to metamorphosis cues (juvenile oysters) in R. venosa were identified, and GO and KEGG enrichment analyses were further performed on these gene sets. The results showed that the expression of the prototype of the class of immediate early genes, the transcription factor AP-1, was rapidly and significantly increased, and the molecular chaperone of NOS, HSP90, exhibited lower expression in the M12 group than in the control group. In contrast, the expression of inhibitors of apoptosis (IAPs) was significantly increased upon exposure to juvenile oysters. Additionally, the Wnt signaling pathway and MAPK signaling pathway were enriched in the trend analysis. These pathways may also play critical regulatory roles in the response to juvenile oysters. Taken together, the results show that competent larvae rapidly respond to the inducing effects of oysters via some immediate early genes, such as the transcription factor AP-1, which may further regulate downstream pathways such as the MAPK signaling pathway to cause subsequent changes, including a decrease in HSP90 and an increase in IAPs. These changes together may regulate the metamorphosis of R. venosa . This study provides further evidence that juvenile oysters are the metamorphosis cues of R. venosa , which may enhance our understanding of the metamorphosis mechanism in this marine invertebrate.

Ghrelin Inhibits ACL Derived Fibroblasts Pyroptosis and Promotes Migration Through Regulating NF-κB p65/NLRP3 Signaling - Xu Zhu; Juan Wu; Shao-Wei Zheng; Gang Liu; Yu-Cong Zou (International Journal of Peptide Research and Therapeutics, 2023)

Fouling-free membrane stripping for ammonia recovery from real biogas slurry - Cong Chen; Zhinan Dai; Yifan Li; Qin Zeng; Yang Yu; Xin Wang; Changyong Zhang; Le Han (Water Research, 2023)

Recovery and recycling core of phosphogypsum: Characteristic hazardous elements risk assessment and analysis - Chao-Qiang Wang; Ze-Yuan Wang; De-Ming Huang; Qi-Cong Huang; Yu Chen; Huan Zhang; Zhong-He Shui (Process Safety and Environmental Protection, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Hyperforin: A natural lead compound with multiple pharmacological activities - Xin-Xin Li; Yu Yan; Jia Zhang; Kang Ding; Cong-Yuan Xia; Xue-Ge Pan; Yan-Jing Shi; Jie-Kun Xu; Jun He; Wei-Ku Zhang (Phytochemistry, 2023)

Risks of applying mobilising agents for remediation of arsenic-contaminated soils: Effects of dithionite–EDTA and citric acid on arsenic fractionation, leachability, oral bioavailability/bioaccessibility and speciation - Xiao-Chen Chen; Cong-Cong Yao; Ao Wang; Zeng-Di Zhang; Long-Zhao Chen; Jian-Yu Zhang; Xian-Hua Liu; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Ecological risk under the dual threat of heavy metals and antibiotic resistant Escherichia coli in swine-farming wastewater in Shandong Province, China - Cong Liu; Chenglian Feng; Yuanpeng Duan; Peng Wang; Chong Peng; Zixuan Li; Lanping Yu; Mengda Liu; Fangkun Wang (Environmental Pollution, 2023)

Effect of ionic radius and valence state of alkali and alkaline earth metals on promoting the catalytic performance of La2O3 catalysts for glycerol carbonate production - Jialin Yu; Ke Wang; Shibo Shao; Wei Li; Shangfeng Du; Xianfeng Chen; Cong Chao; Xianfeng Fan (Chemical Engineering Journal, 2023)

Eco-friendly recyclable high performance ramie yarn reinforced polyimine vitrimer composites - Pandeng Li; Cheng Hao; Huihui Wang; Tian He; Tong Shu; Cong Li; Longjiang Yu; Ning Yan (Chemical Engineering Journal, 2023)

A novel ternary deep eutectic solvent pretreatment for the efficient separation and conversion of high-quality gutta-percha, value-added lignin and monosaccharide from Eucommia ulmoides seed shells - Cong-Jia Duan; Xu Han; Yuan-Hang Chang; Jian Xu; Gan-Lu Yue; Ying Zhang; Yu-Jie Fu (Bioresource Technology, 2023)

Litter accumulation retards the positive effects of nitrogen inputs on plant carbon sequestration in grassland - Yu Ning; Xiao-Sa Liang; Cong Ding; Zhi-Wei Zhang; Yan-Yu Hu; Guo-Jiao Yang; Xiao-Tao Lü (Plant and Soil, 2023)

Melatonin Alleviates the Oxygen–Glucose Deprivation/Reperfusion-Induced Pyroptosis of HEI-OC1 Cells and Cochlear Hair Cells via MT-1,2/Nrf2 (NFE2L2)/ROS/NLRP3 Pathway - Yu Zheng; Na Gao; Weixun Zhang; Rui Ma; Fanglu Chi; Zhen Gao; Ning Cong (Molecular Neurobiology, 2023)

Characterization of water retention behavior of cracked compacted lateritic soil exposed to wet-dry cycles - Qian-Feng Gao; Hui-Cong Yu; Ling Zeng; Yu-Xin Huang (Bulletin of Engineering Geology and the Environment, 2023)

Porewater dissolved inorganic carbon released due to artificial sediment scouring in the Yellow River - Xing-yu Huang; Dong Zhang; Fu-shun Wang; Zhi-qi Zhao; Ai-chun Chen; Jun-wen Zhang; Cong Zhang; Li Wu; Yu-hong Li; Bing-juan Ma; Qi-yan Feng (Applied Geochemistry, 2023)

A new air cleaning technology to synergistically reduce odor and bioaerosol emissions from livestock houses - Tiantian Cao; Yunhao Zheng; Hongmin Dong; Shunli Wang; Yu Zhang; Qunxin Cong (Agriculture, Ecosystems & Environment, 2023)

An expectation–maximization algorithm for estimating proportions of deletions among bacterial populations with application to study antibiotic resistance gene transfer in Enterococcus faecalis - Yu Zhang; Cong Zhang; Wenwen Huo; Xinlei Wang; Michael Zhang; Kelli Palmer; Min Chen (Marine Life Science & Technology, 2023)

Efficient removal of uranium(VI) from aqueous solution by a novel phosphate-modified biochar supporting zero-valent iron composite - Ziwei Tang; Zhongran Dai; Mi Gong; Hong Chen; Xiayu Zhou; Yating Wang; Cong Jiang; Wanying Yu; Le Li (Environmental Science and Pollution Research, 2023)

Microbial functional communities and the antibiotic resistome profile in a high-selenium ecosystem - Yanmei Sun; Jia Guo; Fu Wei; Xiaohui Chen; Meng Li; Chao Li; Size Xia; Guangming Zhang; Wencai You; Xin Cong; Tian Yu; Shiwei Wang (Chemosphere, 2023)

Combining metal and sulfate isotopes measurements to identify different anthropogenic impacts on dissolved heavy metals levels in river water - Cong Zhang; Dong Zhang; Hui-zhen Duan; Zhi-qi Zhao; Jun-wen Zhang; Xing-yu Huang; Bing-juan Ma; De-shun Zheng (Chemosphere, 2023)

Description of a moderately acidotolerant and aerotolerant anaerobic bacterium Acidilutibacter cellobiosedens gen. nov., sp. nov. within the family Acidilutibacteraceae fam. nov., and proposal of Sporanaerobacteraceae fam. nov. and Tepidimicrobiaceae fam. nov. - Hui Fan; Jiang Li; Weidong Wu; Rui Chen; Min Yang; Yinggang Zhang; Lulu Cong; Lirong Dai; Yu Deng; Lei Cheng; Shichun Ma (Systematic and Applied Microbiology, 2023)

Eukaryotic plankton community assembly and influencing factors between continental shelf and slope sites in the northern South China Sea - Tangcheng Li; Guilin Liu; Huatao Yuan; Jianwei Chen; Xin Lin; Hongfei Li; Liying Yu; Cong Wang; Ling Li; Yunyun Zhuang; Lin Senjie (Environmental Research, 2023)

Inter-building effect on building energy consumption in high-density city contexts - Cong Yu; Wei Pan (Energy and Buildings, 2023)

Durable antibacterial and temperature regulated core-spun yarns for textile health and comfort applications - Wei Fan; Yao Zhang; Yanli Sun; Shujuan Wang; Cong Zhang; Xichen Yu; Weiting Wang; Kai Dong (Chemical Engineering Journal, 2023)

Controlling sp3 defect density of carbon-based catalysts by defining a limiting space - Qianjie Xie; Wenfang Si; Zheng Wang; Yu Shu; Cong Li; Yehua Shen; Hiroshi Uyama (Chemical Engineering Journal, 2023)

A chitosan derivative-crosslinked hydrogel with controllable release of polydeoxyribonucleotides for wound treatment - Yanzhen Sun; Xiaodong Jing; Yang Liu; Bing Yu; Hao Hu; Hailin Cong; Youqing Shen (Carbohydrate Polymers, 2023)

Dynamic properties of polycrystalline ice subjected to cyclic triaxial loading - Yanyang Yu; Enlong Liu; Bingtang Song; Yu Su; Cong Chen; Shijia Tang (Cold Regions Science and Technology, 2023)

Probability distribution characteristics of summer extreme precipitation in Xinjiang, China during 1970–2021 - Ailiyaer Aihaiti; Yu Wang; Mamtimin Ali; Lianhua Zhu; Junjian Liu; Hailiang Zhang; Jiacheng Gao; Cong Wen; Meiqi Song (Theoretical and Applied Climatology, 2023)
Based on the daily precipitation data of 96 stations in Xinjiang, China, from 1970 to 2021, the trend of summer extreme precipitation indices and their regional characteristics are analyzed. The generalized extreme value (GEV) model is used to investigate the probability distribution characteristics of summer extreme precipitation indices in northern, southern, and eastern Xinjiang. The results show that (1) The summer maximum 1-day precipitation (RX1day) and maximum 5-day precipitation (RX5day) of most stations in Xinjiang showed an increasing trend, while the summer consecutive dry days (CDD) showed a decreasing trend. (2) The climatology (mean intensity) of RX1day, RX5day, and CDD at most stations in northern Xinjiang were more than 10 mm, more than 15 mm, and less than 25 days, respectively, while those at most stations in southern and eastern Xinjiang were less than 10 mm, less than 15 mm, and more than 25 days. The regional averaged climatology and inter-annual variability of RX1day/RX5day (CDD) in southern and eastern Xinjiang were smaller (larger) than that in northern Xinjiang. (3) The 20-year return level (RL20) of RX1day, RX5day, and CDD at stations in northern Xinjiang were 19.38–56.57 mm, 28.05–70.91 mm, and 22.51–51.05 days, respectively. The RL20 of RX1day, RX5day, and CDD at stations in southern Xinjiang were 21.31–46.07 mm, 23.99–72.89 mm, and 14.94–89.80 days, respectively. The RL20 of RX1day, RX5day, and CDD at stations in eastern Xinjiang were 8.89–36.36 mm, 10.13–50.66 mm, and 26.75–92.00 days, respectively. Compared with northern Xinjiang, there were lesser RX1day and RX5day events, with weaker intensity and smaller variability in southern and eastern Xinjiang. And the CDD events were opposite.

Functional Characterization of Apple MdTGA2.1 in Arabidopsis with Reduced SA Sensitivity and Increased Stress Tolerance - Yi Tian; Cai-Xia Zhang; Chen-Yu Zhu; Xiu-Hong An; Pei-Hua Cong (Journal of Plant Growth Regulation, 2023)

Near-infrared spectroscopy method for rapid proximate quantitative analysis of nutrient composition in Pacific oyster Crassostrea gigas - Zhe Li; Haigang Qi; Ying Yu; Cong Liu; Rihao Cong; Li Li; Guofan Zhang (Journal of Oceanology and Limnology, 2023)

Retraction Note: Knockdown of long non‑coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA‑15a and repressing ROCK1 expression - Xia Li; Sheng‑Wu Wang; Xi‑Ling LI; Feng‑Yuan Yu; Hai‑Ming Cong (Inflammation Research, 2023)

Have China’s drylands become wetting in the past 50 years? - Yu Zhang; Yangjian Zhang; Liang Cheng; Nan Cong; Zhoutao Zheng; Ke Huang; Jianshuang Zhang; Yixuan Zhu; Jie Gao; Yihan Sun (Journal of Geographical Sciences, 2023)

A novel aggregation-induced emission probe-linked phage sorbent assay for virulent bacteria strain imaging and on-site detection - Jiahui Teng; Cong Cao; Zhenzhong Yu; Hongzhen Xie; Fubang Liu; Chong Xu; Yuting Cao; Ning Gan (Analytica Chimica Acta, 2023)

From multiple cropping frequency to multiple cropping system: A new perspective for the characterization of cropland use intensity - Ge Shen; Qiangyi Yu; Qingbo Zhou; Cong Wang; Wenbin Wu (Agricultural Systems, 2023)

Cryo-EM structures reveal the dynamic transformation of human alpha-2-macroglobulin working as a protease inhibitor - Xiaoxing Huang; Youwang Wang; Cong Yu; Hui Zhang; Qiang Ru; Xinxin Li; Kai Song; Min Zhou; Ping Zhu (Science China Life Sciences, 2022)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

Insight into the impacts and mechanisms of ketone stress on the antibiotic resistance in Escherichia coli - Zhenping Tang; Yu Zhang; Shasha Xiao; Yuanyuan Gao; Yi Duan; Boyang Liu; Cong Xiong; Zhengqing Yang; Yueyue Wu; Shuai Zhou (Environmental Science and Pollution Research, 2022)

Research on the Hydrodynamic Performance of a Horizontal-Axis Tidal Current Turbine with Symmetrical Airfoil Blades Based on Swept-Back Models - Yu-Ting Yan; Shi-Ming Xu; Cong Liu; Xiao Zhang; Jian-Mei Chen; Xue-Ming Zhang; Yong-Jun Dong (Journal of Marine Science and Engineering, 2022)
For the design of a horizontal-axis tidal current turbine with adaptive variable-pitch blades, both numerical simulations and physical model experiments were used to study the hydrodynamic performance of symmetrical airfoil blades based on backward swept models. According to the lift–drag ratio of symmetrical airfoils, variable airfoil sections were selected for each part of the blade in the spanwise direction. Then, three kinds of blades were designed by using different swept-back models from wind turbines. A rotation model with a multi-reference frame was employed to conduct a three-dimensional steady numerical simulation of the turbine model based on the CFD method. The axial thrust and energy-capturing efficiency under different tip speed ratios, as well as the corresponding starting torque under different flow rates, were analyzed. The simulation results indicate that model 2 has optimal start-up performance, and model 3 has the largest power coefficient. The thrust coefficient of model 1 is the smallest. In all, model 2 has better comprehensive performance. The experiments of model 2 show that it has suitable hydrodynamic performance to capture bidirectional energy via passively variable pitch. This research provides an important solution for the design and optimization of horizontal-axis turbines to harvest bidirectional tidal current energy.

NAD+-capped RNAs are widespread in rice (Oryza sativa) and spatiotemporally modulated during development - Haijiao Dong; Xufeng Wang; Cong Tan; Lei Gao; Jie Cui; Lin Liu; Beixin Mo; Yongzhong Xing; Yu Yu; Xuemei Chen (Science China Life Sciences, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Storage, patterns and influencing factors for soil organic carbon in coastal wetlands of China - Shaopan Xia; Zhaoliang Song; Lukas Van Zwieten; Laodong Guo; Changxun Yu; Weiqi Wang; Qiang Li; Iain P. Hartley; Yuanhe Yang; Hongyan Liu; Yidong Wang; Xiangbin Ran; et al. (Global Change Biology, 2022)
Soil organic carbon (SOC) in coastal wetlands, also known as “blue C,” is an essential component of the global C cycles. To gain a detailed insight into blue C storage and controlling factors, we studied 142 sites across ca. 5000 km of coastal wetlands, covering temperate, subtropical, and tropical climates in China. The wetlands represented six vegetation types ( Phragmites australis , mixed of P. australis and Suaeda , single Suaeda , Spartina alterniflora , mangrove [ Kandelia obovata and Avicennia marina ], tidal flat) and three vegetation types invaded by S. alterniflora ( P. australis , K. obovata , A. marina ). Our results revealed large spatial heterogeneity in SOC density of the top 1‐m ranging 40–200 Mg C ha −1 , with higher values in mid‐latitude regions (25–30° N) compared with those in both low‐ (20°N) and high‐latitude (38–40°N) regions. Vegetation type influenced SOC density, with P. australis and S. alterniflora having the largest SOC density, followed by mangrove, mixed P. australis and Suaeda , single Suaeda and tidal flat. SOC density increased by 6.25 Mg ha −1 following S. alterniflora invasion into P. australis community but decreased by 28.56 and 8.17 Mg ha −1 following invasion into K. obovata and A. marina communities. Based on field measurements and published literature, we calculated a total inventory of 57 × 10 6 Mg C in the top 1‐m soil across China's coastal wetlands. Edaphic variables controlled SOC content, with soil chemical properties explaining the largest variance in SOC content. Climate did not control SOC content but had a strong interactive effect with edaphic variables. Plant biomass and quality traits were a minor contributor in regulating SOC content, highlighting the importance of quantity and quality of OC inputs and the balance between production and degradation within the coastal wetlands. These findings provide new insights into blue C stabilization mechanisms and sequestration capacity in coastal wetlands.

Dissecting the role of cell signaling versus CD8+ T cell modulation in propranolol antitumor activity - Wei Li; Jielin Wan; Cuiyu Chen; Chengfang Zhou; Ping Liao; Qian Hu; Jiali Hu; Yang Wang; Yu Zhang; Cong Peng; Yuanfei Huang; Weihua Huang; et al. (Journal of Molecular Medicine, 2022)

Estimation of Active Earth Pressure for Limited Width of Soil Using Nonlinear Failure Criterion - Lu Cong; Xuan-yu Yang; Bi-chang Zhang; Wei Xiong (Geotechnical and Geological Engineering, 2022)

Adipose Mesenchymal Stem Cell-Derived Exosomes Promote Wound Healing Through the WNT/β-catenin Signaling Pathway in Dermal Fibroblasts - Cong Li; Yu An; Yu Sun; Fan Yang; Quanchen Xu; Zhiguo Wang (Stem Cell Reviews and Reports, 2022)
The differentiation, migration, and proliferation of skin fibroblasts are identified as key factors in cutaneous wound healing. Adipose-derived mesenchymal stem cells (ADMSCs) and their exosomes (ADMSC-Exos) have been considered as potential therapeutic tools for tissue regeneration; however, the underlying mechanisms on cutaneous wound healing are still not well understood. In this study, we successfully obtained ADMSC-Exos and found ADMSC-Exos significantly promoted the migration and proliferation of fibroblasts in a dose-dependent manner in vitro. The expression levels of COL-I and COL-III in fibroblasts treated with ADMSC-Exos were significantly increased, while the expression level of α-SMA was decreased. In addition, the enhanced protein expression of WNT2b and β-catenin confirmed the activation of the WNT/β-catenin signaling pathway and the WNT/β-catenin inhibitor (XAV939) reversed the promoting effect of ADMSC-Exos on wound healing and the β-catenin expression. Taken together, our study partially elucidates the mechanism of ADMSC-Exos in wound healing, illustrating the potential of ADMSC-Exos as a new therapeutic approach to promote skin wound healing. Graphical Abstract

Inhibition of visfatin alleviates sepsis-induced intestinal damage by inhibiting Hippo signaling pathway - Zhong-Shen Kuang; Yu-Xin Leng; Ning Yang; Zheng-Qian Li; Ya-Nan Zong; Deng-Yang Han; Yue Li; Jin-Dan He; Xing-Ning Mi; Zhu-Kai Cong; Xi Zhu; Chang-Yi Wu; et al. (Inflammation Research, 2022)
Background The aim of this study is to investigate role of Visfatin, one of the pro-inflammatory adipokines, in sepsis-induced intestinal injury and to clarify the potential mechanism. Methods C57BL/6 mice underwent cecal ligation and puncture (CLP) surgery to establish sepsis model in vivo. Intestinal epithelial cells were stimulated with LPS to mimic sepsis-induced intestinal injury in vitro. FK866 (the inhibitor of Visfatin) with or without XMU-MP-1 (the inhibitor of Hippo signaling) was applied for treatment. The expression levels of Visfatin, NF-κB and Hippo signaling pathways-related proteins were detected by western blot or immunohistochemistry. The intestinal cell apoptosis and intestinal injury were investigated by TUNEL staining and H&E staining, respectively. ELISA was used to determine the production of inflammatory cytokines. Results The expression of Visfatin increased in CLP mice. FK866 reduced intestinal pathological injury, inflammatory cytokines production, and intestinal cell apoptosis in sepsis mice. Meanwhile, FK866 affected NF-κB and Hippo signaling pathways. Additionally, the effects of FK866 on inflammatory response, apoptosis, Hippo signaling and NF-κB signaling were partly abolished by XMU-MP-1, the inhibitor of Hippo signaling. In vitro experiments also revealed that FK866 exhibited a protective role against LPS-induced inflammatory response and apoptosis in intestinal cells, as well as regulating NF-κB and Hippo signaling, whereas addition of XMU-MP-1 weakened the protective effects of FK866. Conclusion In short, this study demonstrated that inhibition of Visfatin might alleviate sepsis-induced intestinal injury through Hippo signaling pathway, supporting a further research on Visfatin as a therapeutic target.

Provenance and Palaeogeomorphology study of the southwestern North China Craton during Middle-Late Triassic and its geological implication - Cong Tan; Zhuang Ruan; Bingsong Yu; Zhixin Li; Ce Liu; Lei Zhao; Jianzhong Li; Peng Jia (International Geology Review, 2022)

Cis-element amplified polymorphism (CEAP), a novel promoter- and gene-targeted molecular marker of plants - Meiyan Chen; Xinhua He; Xing Huang; Tingting Lu; Yili Zhang; Jiawei Zhu; Haixia Yu; Cong Luo (Physiology and Molecular Biology of Plants, 2022)

Enhanced Extracellular Matrix Degradation in Growth Plate Contributes to Manganese Deficiency-Induced Tibial Dyschondroplasia in Broiler Chicks - Peng-Fei Dong; Cong Jin; Cai-Yu Lian; Lin Wang; Zhen-Yong Wang (Biological Trace Element Research, 2022)

Research on the layout optimization and utilization of floor gas extraction roadway: a case study in Shoushan No.1 Coal Mine, China - Xiong Ding; Cheng Zhai; Jizhao Xu; Xu Yu; Yong Sun; Yuzhou Cong; Yangfeng Zheng; Wei Tang (Arabian Journal of Geosciences, 2022)

Effects of vegetation restoration on soil carbon dynamics in Karst and non-karst regions in Southwest China: a synthesis of multi-source data - Xiao-Cong Zhu; Ming-Guo Ma; Ryunosuke Tateno; Xin-Hua He; Wei-Yu Shi (Plant and Soil, 2022)

Rational design and fabrication of monophasic bioceramic microspheres with enhanced mechanical and biological performances in reconstruction of segmental bone defect - Yu Cong; Zhong Liang; Ni Jianping; Hu Wenyue; Ghamor-Amegavi Edem Prince; Xiangfeng Zhang (Medical & Biological Engineering & Computing, 2022)

A20 attenuates pyroptosis and apoptosis in nucleus pulposus cells via promoting mitophagy and stabilizing mitochondrial dynamics - Xin Peng; Cong Zhang; Zhi-Min Zhou; Kun Wang; Jia-Wei Gao; Zhan-Yang Qian; Jun-Ping Bao; Hang-Yu Ji; V. L. F. Cabral; Xiao-Tao Wu (Inflammation Research, 2022)

Therapeutic Effects of Sodium Para-Aminosalicylic Acid on Cognitive Deficits and Activated ERK1/2-p90RSK/NF-κB Inflammatory Pathway in Pb-Exposed Rats - Li-li Lu; Yu-wen Zhang; Zhao-cong Li; Yuan-yuan Fang; Lei-lei Wang; Yue-song Zhao; Shao-jun Li; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Effects of dietary protein concentration on growth and anti-oxidant capacity of coho salmon Oncorhynchus kisutch (Walbaum, 1792) alevins - Cong-mei Xu; Hai-rui Yu; Qin Zhang; Ling-yao Li; Jing-jing Fan; Meng-jie Guo; Fang-hui Li; Xiang-yi Qiu; Ling-ling Shan (Aquaculture International, 2022)

Massive Heat Shock Protein 70 Genes Expansion and Transcriptional Signatures Uncover Hard Clam Adaptations to Heat and Hypoxia - Zhi Hu; Hao Song; Jie Feng; Cong Zhou; Mei-Jie Yang; Pu Shi; Zheng-Lin Yu; Yong-Ren Li; Yong-Jun Guo; Hai-Zhou Li; Tao Zhang (Frontiers in Marine Science, 2022)
Heat shock protein 70 (HSP70) members participate in a wide range of housekeeping and stress-related activities in eukaryotic cells. In marine ecosystems, bivalves encounter abiotic stresses, including high temperatures and low dissolved oxygen. Here, 133 MmHSP70 genes were identified through combined methods including Blastp, HMM and manual filtration, based on the whole Mercenaria mercenaria genome. The MmHSP70 genes were unevenly distributed, and 41 genes (33.08%) were located on Chr 7. Phylogenetic analyses indicated that the MmHSP70 gene family mainly consisted of two clusters and the Hspa12 subfamily underwent lineage-specific expansion. A high-density collinear gene block was observed between M. mercenaria Chr 7 and Cyclina sinensis Chr 14. Tandem duplication MmHSP70 gene pairs experienced different levels of purifying selection, which could be an important source of sequence and functional constraints. MmHSP70 genes showed tissue-specific and stress-specific expression. Most tandem duplication HSP70 gene pairs had high expression under hypoxia stress. HSP70 B2 tandem duplication gene pairs showed significantly increased expression under heat plus severe hypoxia stress. This study provided a comprehensive understanding of the MmHSP70 gene family in the M. mercenaria and laid a significant foundation for further studies on the functional characteristics of MmHSP70 genes during exposure to heat and hypoxia stress.

Mechanical properties distribution of lime-fly ash solidified oil contaminated soil in a coastal environment - Min Li; Cong Ma; Zhao Ming Sun; Xin Yu Yao (European Journal of Environmental and Civil Engineering, 2022)

Study on the seepage control of ultra-deep in situ test wells in deep overburden of riverbeds - Ting Yu; Bing-nan Jiang; Shun-bin He; Wen-ming Peng; Cong-yong Ran (Arabian Journal of Geosciences, 2022)

Differences in responses of ammonia volatilization and greenhouse gas emissions to straw return and paddy-upland rotations - Yu Liu; Kunkun Wang; Shipeng Liao; Tao Ren; Xiaokun Li; Rihuan Cong; Jianwei Lu (Environmental Science and Pollution Research, 2022)

Comparison of the Intestinal Bacteria Between Black Seabass Centropristis striata Reared in Recirculating Aquaculture System and Net Pen - Cong Yu; Chen Zhang; Abba Salisu; Yan Wang (Current Microbiology, 2022)

Dynamic evolution mechanism and subsequent reactivated ancient landslide analyses of the “6.17” Danba sequential disasters - Nan Jiang; Hai-bo Li; Yu-xiang Hu; Jie-yuan Zhang; Wei Dai; Cong-jiang Li; Jia-wen Zhou (Bulletin of Engineering Geology and the Environment, 2022)

Association of Sandstone-Type Uranium Mineralization in the Northern China with Tectonic Movements and Hydrocarbons - Yin Chen; Peisen Miao; Jianguo Li; Ruoshi Jin; Hualei Zhao; Lulu Chen; Cong Wang; Haoyu Yu; Xiaoru Zhang (Journal of Earth Science, 2022)

Application of ADSCs and their Exosomes in Scar Prevention - Cong Li; Shuqiang Wei; Quanchen Xu; Yu Sun; Xuchao Ning; Zhiguo Wang (Stem Cell Reviews and Reports, 2022)
Scar is a common way of healing after tissue injury. The poor scar healing will not only cause dysfunction of tissues and organs but also affect the appearance of the patients’ body surface, which causes the pressure of life and spirit to the patients. However, the formation of scar tissue is an extremely complex process and its mechanism is not fully understood. At present, there is no treatment method to eliminate scars completely. Fibroblasts are the most abundant cells in the dermis, which have the ability to synthesize and remodel extracellular matrix (ECM). Myofibroblasts actively participate in the wound healing process and influence the outcome. Therefore, both of them play important roles in wound healing and scar formation. Adipose tissue-derived stem cells (ADSCs) are pluripotent stem cells that can act on target cells by paracrine. Adipose tissue stem cell-derived exosomes (ADSC-Exos) are important secretory substances of ADSCs. They are nanomembrane vesicles that can transport a variety of cellular components and fuse with target cells. In this review, we will discuss the effects of ADSCs and ADSC-Exos on the behavior of fibroblasts and myofibroblasts during wound healing and scarring stage in combination with recent studies. Graphical Abstract

The adaptation mechanism based on an integrated vulnerability assessment of potato production to climate change in Inner Mongolia, China - Na Huang; Jialin Wang; Yu Song; Yuying Pan; Guolin Han; Ziyuan Zhang; Shangqian Ma; Guofeng Sun; Cong Liu; Zhihua Pan (Mitigation and Adaptation Strategies for Global Change, 2022)

The impact of Typhoon Lekima (2019) on East China: a postevent survey in Wenzhou City and Taizhou City - Cong Zhou; Peiyan Chen; Shifang Yang; Feng Zheng; Hui Yu; Jie Tang; Yi Lu; Guoming Chen; Xiaoqing Lu; Xiping Zhang; Jing Sun (Frontiers of Earth Science, 2022)

Damage and Failure of Hot Dry Rock under Cyclic Liquid Nitrogen Cold Shock Treatment: A Non-destructive Ultrasonic Test Method - Yong Sun; Cheng Zhai; Jizhao Xu; Xu Yu; Yuzhou Cong; Yangfeng Zheng; Wei Tang; Yujie Li (Natural Resources Research, 2022)

Expression and localization of amelotin, laminin γ2 and odontogenesis-associated phosphoprotein (ODAPH) on the basal lamina and junctional epithelium - Cong Li; Yan Gao; Zhenzhen Xu; Yuan Tian; Haiyu Mu; Cuicui Yu; Yuguang Gao; Li Zhang (Journal of Molecular Histology, 2022)

Pre-inoculation with Bradyrhizobium japonicum confers NaCl tolerance by improving nitrogen status and ion homeostasis in wild soybean (Glycine soja L.) seedlings - Ying Wang; Cong Cheng; Ziyi Du; Bingjun Yu (Acta Physiologiae Plantarum, 2022)

Position Correction and Trajectory Optimization of Underwater Long-Distance Navigation Inspired by Sea Turtle Migration - Ziyuan Li; Huapeng Yu; Ye Li; Tongsheng Shen; Chongyang Wang; Zheng Cong (Journal of Marine Science and Engineering, 2022)
Accumulating evidence suggests that migrating animals store navigational “maps” in their brains, decoding location information from geomagnetic information based on their perception of the magnetic field. Inspired by this phenomenon, a novel geomagnetic inversion navigation framework was proposed to address the error constraint of a long-distance inertial navigation system. In the first part of the framework, the current paper proposed a geomagnetic bi-coordinate inversion localization approach which enables an autonomous underwater vehicle (AUV) to estimate its current position from geomagnetic information like migrating animals. This paper suggests that the combination of geomagnetic total intensity (F) and geomagnetic inclination (I) can determine a unique geographical location, and that there is a non-unique mapping relationship between the geomagnetic parameters and the geographical coordination (longitude and latitude). Then the cumulative error of the inertial navigation system is corrected, according to the roughly estimated position information. In the second part of the framework, a cantilever beam model is proposed to realize the optimal correction of the INS historical trajectory. Finally, the correctness of the geomagnetic bi-coordinate inversion localization model we proposed was verified by outdoor physical experiments. In addition, we also completed a geomagnetic/inertial navigation integrated long-distance semi-physical test based on the real navigation information of the AUV. The results show that the geomagnetic inversion navigation framework proposed in this paper can constrain long-distance inertial navigation errors and improve the navigation accuracy by 73.28% compared with the pure inertial navigation mode. This implies that the geomagnetic inversion localization will play a key role in long-distance AUV navigation correction.

Isolation and partial characterization of a novel bacteriocin from Pseudomonas azotoformans with antimicrobial activity against Pasterella multocida - Yu Wang; Shuang Lei; Inam Muhammad; Yu Jia; Cheng-guang He; Yi-Ming Wang; Yun-Hang Gao; Ling-Cong Kong; Hong-Xia Ma (Archives of Microbiology, 2022)

Mechanical Properties of Limestone After High-Temperature Treatment Under Triaxial Cyclic Loading and Unloading Conditions - Qing-bin Meng; Jiang-Feng Liu; Hai Pu; Li-yuan Yu; Jiang-yu Wu; Cong-kai Wang (Rock Mechanics and Rock Engineering, 2021)

c-Abl Tyrosine Kinase-Mediated Neuronal Apoptosis in Subarachnoid Hemorrhage by Modulating the LRP-1-Dependent Akt/GSK3β Survival Pathway - Cong Yan; Hongwei Yu; Yao Liu; Pei Wu; Chunlei Wang; Hongbo Zhao; Kongbin Yang; Qi Shao; Yingqiang Zhong; Wenyang Zhao; Jingwei Li; Nan Liu; et al. (Journal of Molecular Neuroscience, 2021)

Early Palaeozoic alkaline trachytes in the North Daba Mountains, South Qinling Belt: petrogenesis and geological implications - Hang Yang; Shao-Cong Lai; Jiang-Feng Qin; Ren-Zhi Zhu; Shao-Wei Zhao; Yu Zhu; Fang-Yi Zhang; Ze-Zhong Zhang; Xing-Ying Wang (International Geology Review, 2021)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

Lipin1 Alleviates Autophagy Disorder in Sciatic Nerve and Improves Diabetic Peripheral Neuropathy - Meijian Wang; Min Xie; Shuyan Yu; Pan Shang; Cong Zhang; Xiaolin Han; Cuiqin Fan; Li Chen; Xianghua Zhuang; Shihong Chen (Molecular Neurobiology, 2021)

Time-resolved Fluorescence Immunoassay (TRFIA) for the Simultaneous Detection of MMP-9 and Lp-PLA2 in Serum - Hong-yan Ma; Qian Mao; Yan-bin Zhu; Chun-li Cong; Shi-yu Zheng; Qi Zhang; Cui-cui Chen; Lai-qing Li (Journal of Fluorescence, 2021)

An atlas of bacterial secondary metabolite biosynthesis gene clusters - Bin Wei; Ao‐Qi Du; Zhen‐Yi Zhou; Cong Lai; Wen‐Chao Yu; Jin‐Biao Yu; Yan‐Lei Yu; Jian‐Wei Chen; Hua‐Wei Zhang; Xue‐Wei Xu; Hong Wang (Environmental Microbiology, 2021)
Summary Bacterial secondary metabolites are rich sources of novel drug leads. The diversity of secondary metabolite biosynthetic gene clusters (BGCs) in genome‐sequenced bacteria, which will provide crucial information for the efficient discovery of novel natural products, has not been systematically investigated. Here, the distribution and genetic diversity of BGCs in 10 121 prokaryotic genomes (across 68 phyla) were obtained from their PRISM4 outputs using a custom python script. A total of 18 043 BGCs are detected from 5743 genomes with non‐ribosomal peptide synthetases (25.4%) and polyketides (15.9%) as the dominant classes of BGCs. Bacterial strains harbouring the largest number of BGCs are revealed and BGC count in strains of some genera vary greatly, suggesting the necessity of individually evaluating the secondary metabolism potential. Additional analysis against 102 strains of discovered bacterial genera with abundant amounts of BGCs confirms that Kutzneria , Kibdelosporangium , Moorea , Saccharothrix , Cystobacter , Archangium , Actinosynnema , Kitasatospora , and Nocardia , may also be important sources of natural products and worthy of priority investigation. Comparative analysis of BGCs within these genera indicates the great diversity and novelty of the BGCs. This study presents an atlas of bacterial secondary metabolite BGCs that provides a lot of key information for the targeted discovery of novel natural products.

Numerical estimation of landslide-generated waves at Kaiding Slopes, Houziyan Reservoir, China, using a coupled DEM-SPH method - Yu-xiang Hu; Yong-guo Zhu; Hai-bo Li; Cong-jiang Li; Jia-wen Zhou (Landslides, 2021)

The role of telomere dysfunction in genomic instability and age-related diseases - Lu Xu; Kexiong Zhang; Yu-Sheng Cong (Genome Instability & Disease, 2021)

Geochemical characteristics of the lower Cambrian Qiongzhusi Formation in Huize area, east Yunnan: implications for paleo-ocean environment and the origin of black rock series - Yong Cheng; Weiqing Liu; Wei Wu; Yu Zhang; Guo Tang; Cong Liu; Qi Nie; Yiming Wen; Ping Lu; Chuanyu Zhang (Arabian Journal of Geosciences, 2021)

Complete genome analysis of the newly isolated Shigella sonnei phage vB_SsoM_Z31 - Bingdong Wei; Cong Cong; Lichun Zhang; Lin Zheng; Long Chen; Wei Yu; Yongping Xu (Archives of Virology, 2021)

In situ cosmogenic 10Be, 26Al, and 21Ne dating in sediments from the Guizhou Plateau, southwest China - Ye Yang; Yu Liu; Yan Ma; Sheng Xu; Cong-Qiang Liu; Shi-Jie Wang; Finlay M. Stuart; Derek Fabel (Science China Earth Sciences, 2021)

Activity of eugenol derivatives against Fusarium graminearum Q1 strain and screening of isoeugenol mixtures - Wen Cui; Kai-Yue Du; Yu-Xuan Ling; Cong-Jun Yang (Journal of Plant Pathology, 2021)

Effect of first-stage aeration on treatment of domestic sewage in different hybrid constructed wetlands - Fei-Long Yan; Yi Wang; Wen-Huai Wang; Heng Zhang; Yu-Cong Zheng; Xiao-Mei Kou; Shi-Zhang Wu; Tian Shao (Environmental Science and Pollution Research, 2021)

Safety evaluation and ibuprofen removal via an Alternanthera philoxeroides-based biochar - Yuan-da Du; Xin-qian Zhang; Li Shu; Yu Feng; Cui Lv; Hong-qiang Liu; Fei Xu; Qian Wang; Cong-cong Zhao; Qiang Kong (Environmental Science and Pollution Research, 2021)

The Characteristic of Critical Genes in Neuroendocrine System and Their Regulation on Food Habit Transition and Metamorphosis of Veined Rapa Whelk Rapana venosa (Valenciennes, 1846) - Mei-Jie Yang; Jie Feng; Hao Song; Zheng-Lin Yu; Pu Shi; Jian Liang; Zhi Hu; Cong Zhou; Xiao-Lin Wang; Tao Zhang (Frontiers in Marine Science, 2021)
Metamorphosis is a critical developmental event in mollusks, and neuroendocrine system plays an essential role in this process. Rapana venosa is an economically important shellfish in China, but the artificial technology of R. venosa aquaculture is limited by metamorphosis. As a carnivorous gastropod, food habit transition makes the mechanism of R. venosa metamorphosis more complex. To investigate the changes in the neuroendocrine system and to reveal its role in regulating the food habit transition and metamorphosis of R. venosa , we cloned the cDNA sequences encoding 5-hydroxytryptamine receptor ( Rv-5HTR ), nitric oxide synthetase ( Rv-NOS ) and cholecystokinin receptor ( Rv-CCKR ), and investigated their expression by quantitative real-time PCR analysis, and explore the spatio-temporal changes of 5-HT protein expression using Immunohistochemical (IHC) analysis. The expression of the three geens was significantly increased in the early intramembrane veliger stage, which indicates that the three genes are related to the development of digestive system. Additionally, expression of the three genes was decreased after metamorphosis, while Rv-NOS and Rv-CCKR were increasingly expressed in competent larvae, which may help the larvae find suitable environments and promote digestive system development for metamorphosis, and the result of 5-HT IHC analysis also reflects the development of neuroendocrine system. Furthermore, results show that CCK can effect the expression of digestive enzyme, NOS and 5-HT receptor. Finally, based on the present results, we hypothesized that CCK and CCK receptor may be critical regulatory factors of food habit transition and metamorphosis. These results might provide information on the development of neuroendocrine system of R. venosa , and new insight into the regulation of the food habit transition and metamorphosis of gastropods.

Numerical Study on Interaction between Submarine Landslides and a Monopile Using CFD Techniques - Ru-Yu Li; Jin-Jian Chen; Chen-Cong Liao (Journal of Marine Science and Engineering, 2021)
Offshore installations with pile foundations in shallow water are vulnerable to submarine landslides, which cause serious damage to engineering facilities, loss of life, and loss of money. Due to a shortage of real observation data and the difficulty of reproduction, we lack insight into the interaction behavior between submarine landslides and monopiles. This study capitalized on ANSYS Fluent 20.0 to develop a three-dimensional biphasic (water and slurry) numerical model. This CFD model was used to analyze the interaction between a monopile and submarine landslides at different flow heights. The velocities of submarine landslides were from low to high values. Two modes of interactional forces acting on the monopile are proposed, which are (i) interaction force with peak value and (ii) interaction force without peak value. The influence of flow height and velocity on interaction forces was investigated. Results show that the effect of the flow heights on the interaction force is significant at low velocity stage, while the peak force representing a hazard level of the pile was non-negligible under high flow velocity and low flow height conditions, which should be considered in a future study. The related mechanisms are revealed with a hybrid model considering different components of the force.

Preferential capture of phosphate by an Enteromorpha prolifera–based biopolymer encapsulating hydrous zirconium oxide nanoparticles - Qian-Qian Zhong; Li Shen; Ya-Qin Zhao; Yu-Cui Hao; Li-Cong Meng; Yan-Juan Liu; Xing Xu; Ya-Nan Shang; Bao-Yu Gao; Qin-Yan Yue (Environmental Science and Pollution Research, 2021)

De novo hydroponics system efficiency for the cuttings of alfalfa (Medicago sativa L.) - Zhili Zhao; Wenyu Zhang; Yang Liu; Shuai Li; Wu Yao; Xiaohui Sun; Siyu Li; Lichao Ma; Juan Sun; Qingchuan Yang; Yongxiang Li; Guofeng Yang; et al. (Physiology and Molecular Biology of Plants, 2021)
The legume plant alfalfa ( Medicago sativa L.) is a widely cultivated perennial forage due to its high protein content, palatability, and strong adaptability to diverse agro-ecological zones. Alfalfa is a self-incompatible cross-pollinated autotetraploid species with tetrasomic inheritance. Therefore, maintaining excellent traits through seed reproduction is a prime challenge in alfalfa. However, the cutting propagation technology could enable consistent multiplication of quality plants that are genetically identical to the parent plant. The current study aimed to develop a simple, cost-effective, reproducible, and efficient hydroponic cutting method to preserve alfalfa plants and for molecular research. In this study, alfalfa landrace ‘Wudi’ was grown in hydroponics for 30 days and used as source material for cuttings. The top, middle and bottom sections of its stem were used as cuttings. The rooting rate, root length, and stem height of the different stem sections were compared to determine the best segment for alfalfa propagation in four nutrient treatments (H M , H M + 1/500H, H M + 1/1000H and d H M + 1/2000H). After 21 days of culture, the rooting rates of all the three stem types under four cutting nutrient solutions were above 78%. The rooting rate of the middle and bottom parts in H M + 1/1000 H and H M + 1/2000 H nutrient solutions reached more than 93%, with a higher health survey score (> 4.70). In conclusion, this study developed a de novo cutting propagation method that can be used to conserve and propagate germplasm in breeding programs and research. This method is a new report on the cutting propagation of alfalfa by hydroponics, which could supplement the existing cutting propagation methods.

Application Overview of Membrane Separation Technology in Coal Mine Water Resources Treatment in Western China - Fan Wang; Yu Wang; Cong Jing (Mine Water and the Environment, 2021)

Wastewater analysis reveals urban, suburban, and rural spatial patterns of illicit drug use in Dalian, China - Zi-Xiang Cong; Xue-Ting Shao; Si-Yu Liu; Wei Pei; De-Gao Wang (Environmental Science and Pollution Research, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

Seasonal Variations in Total Lipid and Fatty Acid Composition of Haliotis discus Hannai from Three Different Production Zones - Lipin Chen; Qi Wang; Xiaohan Cong; Fanqianhui Yu; Yong Xue; Qingjuan Tang; Changhu Xue; Yanqing Liu; Zhaojie Li (Journal of Aquatic Food Product Technology, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

Investigation on the dust migration behavior and safety zone in the fully mechanized mining face - Xin-xiao Lu; Cheng-yan Wang; Yun Xing; Cong Shen; Guo-yu Shi (Environmental Science and Pollution Research, 2021)

Algorithm of Berthing and Maneuvering for Catamaran Unmanned Surface Vehicle Based on Ship Maneuverability - Gongxing Wu; Mingyuan Zhao; Yu Cong; ZhiWen Hu; Guofu Li (Journal of Marine Science and Engineering, 2021)
In the complex port environment, ship berthing manipulation is one of the most difficult operations. In this study, an algorithm of berthing and maneuvering was designed for a catamaran unmanned surface vehicle (USV), which is used for port patrol and protection. Considering the influence of wind, waves, and currents, the mathematical model of the maneuvering movement for the twin-hull and twin-propeller USV was established. Based on the Visual Studio development platform, the USV’s berthing manipulation simulation software was designed. Through the turning simulation experiment of the catamaran USV under different differential rotation speeds of the twin propellers, the relationship between the ship’s turning radius and the propeller speed difference was obtained. A simulation experiment of decelerating and stopping ships at different speeds was carried out, which can provide a reference for speed control when berthing. A berthing maneuvering algorithm based on ship maneuverability was proposed. USV’s berthing algorithm includes three stages: approach process, turning process, and berthing process. In the approach process, the appropriate approach speed was select according to the rotation angle. In the turning process, the right and left propeller speed differences were select. In the berthing process, the berthing speed was controlled according to the berthing distance. In the port environment, a berthing simulation experiment for catamaran USV was carried out. The simulation results show that based on the berthing and maneuvering algorithm, the efficiency and safety of catamaran USV berthing can be improved.

An Integrated Dynamic Model and Optimized Fuzzy Controller for Path Tracking of Deep-Sea Mining Vehicle - Yu Dai; Cong Xue; Qiao Su (Journal of Marine Science and Engineering, 2021)
The capability of path tracking largely determines the operational efficiency of deep-sea mining vehicles. In this paper, the relationships of vehicle–sediment mechanical interaction were obtained by sinkage and shear tests. Then, an overset grid method was used to establish the computational fluid dynamics (CFD) model of the vehicle, and the spatial hydrodynamic distribution was calculated in different motion states. Based on the above research, a multi-body dynamic (MBD) model of the mining vehicle was developed, which considered the spatial hydrodynamic effects and the mechanical interaction between vehicle and sediment. In addition, a path-tracking controller based on fuzzy logic control was proposed. A genetic algorithm optimized the fuzzy rules through co-simulation between the controller and the MBD model. Finally, the co-simulation results of the vehicle which moved along the expected path indicated that the performance of the optimized fuzzy controller was preferable to the original fuzzy controller.

Preparation, Characterization, and In Vitro Pharmacodynamics and Pharmacokinetics Evaluation of PEGylated Urolithin A Liposomes - Shengfu Yi; Cong Zhang; Junjie Hu; Yan Meng; Liang Chen; Huifan Yu; Shan Li; Guihong Wang; Guohua Zheng; Zhenpeng Qiu (AAPS PharmSciTech, 2021)

Investigation on disc cutter behaviors in cutting rocks of different strengths and reverse estimation of rock strengths from experimental cutting forces - Yu-cong Pan; Quan-sheng Liu; Jian-ping Liu; Xiao-xuan Kong; Xing-xin Peng; Qi Liu (European Journal of Environmental and Civil Engineering, 2021)

Tuberculosis relapse is more common than reinfection in Beijing, China - Yi Liu; Xu Xia Zhang; Jia Jia Yu; Chen Liang; Qing Xing; Cong Yao; Chuan You Li (Infectious Diseases, 2020)

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

Genome-wide analysis of chloride channel-encoding gene family members and identification of CLC genes that respond to Cl−/salt stress in upland cotton - Xun Liu; Boyi Pi; Jianwei Pu; Cong Cheng; Jiajia Fang; Bingjun Yu (Molecular Biology Reports, 2020)

Non-coding RNAS and colorectal cancer liver metastasis - Xiao-Yu Zhou; Bing Luo; Ze-Kun Jiang; Ying-Kang Xie; Feng-Cong Wu; Jiong-Qiang Huang; Jing-Song Chen (Molecular and Cellular Biochemistry, 2020)

SUMOylation of Pdia3 exacerbates proinsulin misfolding and ER stress in pancreatic beta cells - Na Li; Xi Luo; Qilin Yu; Ping Yang; Zhishui Chen; Xinqiang Wang; Jipin Jiang; Jing Xu; Quan Gong; Decio L. Eizirik; Zhiguang Zhou; Jiajun Zhao; et al. (Journal of Molecular Medicine, 2020)

A C‐type lectin with antibacterial activity in weather loach, Misgurnus anguillicaudatus - Xiao‐Wen Zhang; Cong‐Hui Yang; Hong‐Quan Zhang; Xin‐Tong Pan; Ze‐Yu Jin; Hong‐Wei Zhang; Xiao‐Hua Xia (Journal of Fish Diseases, 2020)
C‐type lectins are carbohydrate‐binding proteins that play important roles in immunity by serving as pattern recognition receptors. In the present study, a novel nattectin‐like C‐type lectin was obtained from the weather loach, Misgurnus anguillicaudatus , designated as MaCTL. MaCTL encodes a peptide with 165 amino acids, with a signal peptide and a single C‐type lectin domain (CTLD), containing a galactose‐specific QPD motif and a conserved Ca 2+ ‐binding site. Transcripts of MaCTL were significantly upregulated after immune challenge with its pathogen A. hydrophila . In vitro assays with recombinant MaCTL protein revealed that it exhibited hemagglutinating and bacterial agglutinating activities, in a Ca 2+ ‐dependent manner. MaCTL was found to bind to a wide range of bacteria, as well as bind to bacterial polysaccharides LPS and PGN. Moreover, MaCTL displayed antimicrobial activity by inhibiting the growth of bacteria. These results collectively suggest that MaCTL is involved in the antibacterial defence of weather loach.

Effects of ferric and manganese precursors on catalytic activity of Fe-Mn/TiO2 catalysts for selective reduction of NO with ammonia at low temperature - Huan Du; Zhitao Han; Qimeng Wang; Yu Gao; Cong Gao; Jingming Dong; Xinxiang Pan (Environmental Science and Pollution Research, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Water sources of major plant species along a strong climatic gradient in the inland Heihe River Basin - Liangju Zhao; Cong Xie; Xiaohong Liu; Ninglian Wang; Zhang Yu; Xiying Dong; Lixin Wang (Plant and Soil, 2020)

Overexpression of the mango MiCO gene delayed flowering time in transgenic Arabidopsis - Yuan Liu; Cong Luo; Xiu-Juan Zhang; Xin-Xi Lu; Hai-Xia Yu; Xiao-Jie Xie; Zhi-Yi Fan; Xiao Mo; Xin-Hua He (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Exploring slope spatial heterogeneity by nitrogen transfer and arbuscular mycorrhizal community - Yanyan Yu; Lu Zhao; Min Cui; Yutong Xiao; Cong Wang; Yuan Miao; Zhijie Chen; Yanhong Cao; Junqiang Zheng; Shijie Han (Journal of Soils and Sediments, 2020)

Sodium Para-aminosalicylic Acid Reverses Changes of Glutamate Turnover in Manganese-Exposed Rats - Zhao-Cong Li; Fang Wang; Shao-Jun Li; Lin Zhao; Jun-Yan Li; Yue Deng; Xiao-Juan Zhu; Yu-Wen Zhang; Dong-Jie Peng; Yue-Ming Jiang (Biological Trace Element Research, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

1H NMR Quantification of DHA and EPA in Fish Oil - Jinxiao Lv; Cong Wang; Xiuli Zhang; Zhihua Lv; Mingming Yu (Journal of Ocean University of China, 2020)

Aggregation behavior of juvenile Neptunea cumingii and effects on seed production - Zhenglin Yu; Zhi Hu; Hao Song; Tao Xu; Meijie Yang; Cong Zhou; Tao Zhang (Journal of Oceanology and Limnology, 2020)

RETRACTED ARTICLE: Knockdown of long non-coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA-15a and repressing ROCK1 expression - Xia Li; Sheng-Wu Wang; Xi-Ling LI; Feng-Yuan Yu; Hai-Ming Cong (Inflammation Research, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Prenatal di-(2-ethylhexyl) phthalate maternal exposure impairs the spatial memory of adult mouse offspring in a phase- and gender-dependent manner - Ling-Li Zhao; Ru Shen; Cong-Cong Sun; Shan-Yu Zhang; Bo Wang; Mei-Fang Sun; De-Xiang Xu (Environmental Science and Pollution Research, 2020)

Lipid/Hyaluronic Acid–Coated Doxorubicin-Fe3O4 as a Dual-Targeting Nanoparticle for Enhanced Cancer Therapy - Jinying Liang; Xue Yang; Danmeng Liu; Mei Cong; Yu Song; Suping Bai (AAPS PharmSciTech, 2020)

Correction to: On the Applicability of the Expected Waiting Time Method in Nonstationary Flood Design - Lei Yan; Lihua Xiong; Qinghua Luan; Cong Jiang; Kunxia Yu; Chong-Yu Xu (Water Resources Management, 2020)

Correction to: Emodin alleviated pulmonary inflammation in rats with LPS-induced acute lung injury through inhibiting the mTOR/HIF-1α/VEGF signaling pathway - Xiaoqian Li; Cong Shan; Zhonghua Wu; Hongji Yu; Aidong Yang; Bo Tan (Inflammation Research, 2020)

A novel putative betapartitivirus isolated from the plant-pathogenic fungus Rhizoctonia solani - Yi Chen; Jia En Su; Xi Yun Qin; Zhi Yong Fan; Xiao Hai Zhang; Qing Yu; Zhen Yuan Xia; Cong Ming Zou; Gao Kun Zhao; Zhong Long Lin (Archives of Virology, 2020)

On the Applicability of the Expected Waiting Time Method in Nonstationary Flood Design - Lei Yan; Lihua Xiong; Qinghua Luan; Cong Jiang; Kunxia Yu; Chong-Yu Xu (Water Resources Management, 2020)

Correction to: EPAC Negatively Regulates Myelination via Controlling Proliferation of Oligodendrocyte Precursor Cells - Zheng-Zheng Gao; Ying-Cong Li; Chong-Yu Shao; Jian Xiao; Ying Shen; Liang Zhou (Neuroscience Bulletin, 2020)

EPAC Negatively Regulates Myelination via Controlling Proliferation of Oligodendrocyte Precursor Cells - Zhen-Zhen Gao; Ying-Cong Li; Chong-Yu Shao; Jian Xiao; Ying Shen; Liang Zhou (Neuroscience Bulletin, 2020)

Doxorubicin sensitizes cancer cells to Smac mimetic via synergistic activation of the CYLD/RIPK1/FADD/caspase-8-dependent apoptosis - Chengkui Yang; Qiao Ran; Yifei Zhou; Shan Liu; Cong Zhao; Xiaoliang Yu; Fang Zhu; Yuting Ji; Qian Du; Tao Yang; Wei Zhang; Sudan He (Apoptosis, 2020)

Emodin alleviated pulmonary inflammation in rats with LPS-induced acute lung injury through inhibiting the mTOR/HIF-1α/VEGF signaling pathway - Xiaoqian Li; Cong Shan; Zhonghua Wu; Hongji Yu; Aidong Yang; Bo Tan (Inflammation Research, 2020)

Physical and micro-structural characteristics of limestone after high temperature exposure - Qing-Bin Meng; Cong-Kai Wang; Jiang-Feng Liu; Ming-Wei Zhang; Meng-Meng Lu; Yu Wu (Bulletin of Engineering Geology and the Environment, 2020)

Coix seed oil prolongs lifespan and enhances stress resistance in Caenorhabditis elegans - Xin-Yan Chen; De-Chun Liao; Ying-Ting Yu; Cong-Min Wei; Ling-Yan Xuan; Shan Li; Hong-Bing Wang (Biogerontology, 2020)

Aprepitant Intravenous Emulsion Based on Ion Pairing/Phospholipid Complex for Improving Physical and Chemical Stability During Thermal Sterilization - Xinyu Zhang; Ying Wei; Zhijun Cao; Ying Xu; Cong Lu; Meiqi Zhao; Jingxin Gou; Tian Yin; Yu Zhang; Haibing He; Yanjiao Wang; Xing Tang (AAPS PharmSciTech, 2020)

Atorvastatin ameliorates depressive behaviors and neuroinflammatory in streptozotocin-induced diabetic mice - Zhang Hai-Na; Yu Xu-Ben; Tang Cong-Rong; Cao Yan-Cheng; Yang Fan; Xu Lei-Mei; Sun Ruo-Lan; Ye-Zi; Wang Ye-Xuan; Liang Jing (Psychopharmacology, 2020)

High-efficient biodegradation of refractory dye by a new bacterial flora DDMY1 under different conditions - X. H. Xie; X. L. Zheng; C. Z. Yu; Q. Y. Zhang; Y. Q. Wang; J. H. Cong; N. Liu; Z. J. He; B. Yang; J. S. Liu (International Journal of Environmental Science and Technology, 2020)

Anaerophilus nitritogenes gen. nov., sp. nov., isolated from salt lake sediment in Xinjiang Province, China - Ran Zhang; Yan Zeng; Tian-Qi Wang; Xin-Mei Wang; Yi-Yu Shi; Jia-Tian Zou; Cong Sun; Gui-Shan Zhang; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Disruption of tight junction structure contributes to secretory dysfunction in IgG4-related sialadenitis - Sai-Nan Min; Li-Ling Wu; Yan-Yan Zhang; Wen-Xuan Zhu; Xin Cong; Guang-Yan Yu (Journal of Molecular Histology, 2020)

Settlement and metamorphosis of Rapana venosa (Gastropoda: Muricidae) with implications for artificial culture - Zhenglin Yu; Meijie Yang; Hao Song; Zhi Hu; Cong Zhou; Xiaolong Wang; Haizhou Li; Tao Zhang (Journal of Oceanology and Limnology, 2020)

Evaluation of the genetic diversity of mango (Mangifera indica L.) seedling germplasm resources and their potential parents with start codon targeted (SCoT) markers - Li Zhou; Xin-Hua He; Hai-Xia Yu; Mei-Yan Chen; Yan Fan; Xiu-Juan Zhang; Zhong-Bing Fang; Cong Luo (Genetic Resources and Crop Evolution, 2020)

Tea Residue Boosts Dye Decolorization and Induces the Evolution of Bacterial Community - Xuehui Xie; Xiulin Zheng; Chengzhi Yu; Qingyun Zhang; Yiqin Wang; Junhao Cong; Na Liu; Zhenjiang He; Bo Yang; Jianshe Liu (Water, Air, & Soil Pollution, 2019)

Association between social health status and depressive symptoms among community-dwelling elderly adults in Zhejiang Province, China - Hong-lei Dai; Zhe-bin Yu; Liu-qing You; Min-hua Fan; Hong-wei Zhu; Dan-jie Jiang; Meng-yin Wu; Shu-juan Lin; Xiao-cong Zhang; Kun Chen (Journal of Zhejiang University-SCIENCE B, 2019)

A structured approach to the analysis of remote sensing images - Donghui Yan; Congcong Li; Na Cong; Le Yu; Peng Gong (International Journal of Remote Sensing, 2019)

Vanadium compounds induced damage of human umbilical vein endothelial cells and the protective effect of berberine - Cong-Cong Hou; Hong-Yu Liang; Yi-Hui Pan; Man Wang; Li-Li Zhao; Yuan Bian; Duan-Yuan Cao; Ding Zhao (BioMetals, 2019)

Liver Targeting Albumin-Coated Silybin-Phospholipid Particles Prepared by Nab™ Technology for Improving Treatment Effect of Acute Liver Damage in Intravenous Administration - Cong Lu; Xin Li; Xue Liang; Xinyu Zhang; Tian Yin; Jingxin Gou; Haibing He; Yu Zhang; Xing Tang (AAPS PharmSciTech, 2019)

Aureibaculum marinum gen. nov., sp. nov., a Novel Bacterium of the Family Flavobacteriaceae Isolated from the Bohai Gulf - Huilin Zhao; Yulong Wu; Cong Zhang; Jiarong Feng; Zheng Xu; Yunfei Ding; Yaxin Gao; Yu Geng; Jie Song; Boqing Li; Xiaofei Ji (Current Microbiology, 2019)

Characterization and complete genome sequence analysis of phage GP4, a novel lytic Bcep22-like podovirus - Ronghuan Wang; Yu Cong; Zhiqiang Mi; Hang Fan; Taoxing Shi; Hui Liu; Yigang Tong (Archives of Virology, 2019)

Algicoccus marinus gen. nov. sp. nov., a marine bacterium isolated from the surface of brown seaweed Laminaria japonica - Jun-Jie Ying; Shun-Li Zhang; Chao-Yu Huang; Lin Xu; Zhe Zhao; Min Wu; Cong Sun (Archives of Microbiology, 2019)

Influence of fungi and bag mesh size on litter decomposition and water quality - Jiexiu Zhai; Ling Cong; Guoxin Yan; Yanan Wu; Jiakai Liu; Yu Wang; Zhenming Zhang; Mingxiang Zhang (Environmental Science and Pollution Research, 2019)

Erratum to: Plant water use strategies in the Shapotou artificial sand-fixed vegetation of the southeastern margin of the Tengger Desert, northwestern China - Liang-ju Zhao; Xiao-gang Wang; Yu-cui Zhang; Cong Xie; Quan-yu Liu; Fei Meng (Journal of Mountain Science, 2019)

High-throughput Luminex xMAP assay for simultaneous detection of antibodies against rabbit hemorrhagic disease virus, Sendai virus and rabbit rotavirus - Miaoli Wu; Lei Ma; Feng Cong; Yujun Zhu; Fengjiao Xu; Yuexiao Lian; Bihong Huang; Li Xiao; Meili Chen; Yu Zhang; Ren Huang; Pengju Guo (Archives of Virology, 2019)

Parametric Study on the Free-Fall Water Entry of a Sphere by Using the RANS Method - Pengyao Yu; Cong Shen; Chunbo Zhen; Haoyun Tang; Tianlin Wang (Journal of Marine Science and Engineering, 2019)
Motivated by the application of water-entry problems in the air-drop deployment of a spherical oceanographic measuring device, the free-fall water entry of a sphere was numerically investigated by using the transient Reynolds-averaged Navier–Stokes (RANS) method. A convergence study was carried out, which accounts for the mesh density and time-step independence. The present model was validated by the comparison of non-dimensional impact force with previous experimental and numerical results. Effects of parameters, such as impact velocity, radius, and mass of the sphere on the impact force and the acceleration of the sphere, are discussed. It is found that the peak value of the non-dimensional impact force is independent of the impact velocity and the radius of the sphere, while it depends on the mass of the sphere. By fitting the relationship between the peak value of the non-dimensional impact force and the non-dimensional mass, simplified formulas for the prediction of peak values of the impact force and the acceleration were achieved, which will be useful in the design of the spherical oceanographic measuring device.

Plant water use strategies in the Shapotou artificial sand-fixed vegetation of the southeastern margin of the Tengger Desert, northwestern China - Liang-ju Zhao; Xiao-gang Wang; Yu-cui Zhang; Cong Xie; Quan-yu Liu; Fei Meng (Journal of Mountain Science, 2019)

Observed characteristics of tidal currents and mean flow in the northern Yellow Sea - Congcong Bi; Xianwen Bao; Yang Ding; Cong Zhang; Yu Wang; Biao Shen; Kai Wan (Journal of Oceanology and Limnology, 2019)

Dry Deposition of Particulate Matter and Ions in Forest at Different Heights - Jiexiu Zhai; Ling Cong; Guoxin Yan; Yanan Wu; Jiakai Liu; Yu Wang; Wenmei Ma; Zhenming Zhang (International Journal of Environmental Research, 2019)

Effects of partial replacement of fish meal by yeast hydrolysate on antioxidant capability, intestinal morphology, and inflammation-related gene expression of juvenile Jian carp (Cyprinus carpio var. Jian) - Xiang-Yang Yuan; Guang-Zhen Jiang; Cong-Cong Wang; Kenneth Prudence Abasubong; Qing Zou; Yu-Yan Zhou; Wen-Bin Liu (Fish Physiology and Biochemistry, 2019)

PPPDE1 promotes hepatocellular carcinoma development by negatively regulate p53 and apoptosis - Xingwang Xie; Xueyan Wang; Weijia Liao; Ran Fei; Nan Wu; Xu Cong; Qian Chen; Lai Wei; Yu Wang; Hongsong Chen (Apoptosis, 2019)

Molecular mechanism of inbreeding effects based on RNA-Seq analysis of the adductor muscle of bay scallop (Argopecten irradians) - Yu Wang; Shoudu Zhang; Guofan Zhang; Rihao Cong; Li Li (Acta Oceanologica Sinica, 2019)

Nemertean taxonomy—Implementing changes in the higher ranks, dismissing Anopla and Enopla - Malin Strand; Jon Norenburg; José E. Alfaya; Fernando Ángel Fernández‐Álvarez; Håkan S Andersson; Sonia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Gregorio Bigatti; Irina Cherneva; Alexey Chernyshev; Brian M. Chung; et al. (Zoologica Scripta, 2019)

Overexpression of two cold-responsive ATAF-like NAC transcription factors from fine-stem stylo (Stylosanthes guianensis var. intermedia) enhances cold tolerance in tobacco plants - Peng-Lin Zhan; Shan-Wen Ke; Pan-Yu Zhang; Cong-Cong Zhou; Bei-Ling Fu; Xiang-Qian Zhang; Tian-Xiu Zhong; Shu Chen; Xin-Ming Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

MiR-92a inhibits fibroblast-like synoviocyte proliferation and migration in rheumatoid arthritis by targeting AKT2 - Fang-Yuan Yu; Cong-Qin Xie; Chang-liang Jiang; Ji-Tong Sun; Hui-Cheng Feng; Chao Li; Xun-Wu Huang (Journal of Biosciences, 2018)

Volumetric comparison of hippocampal subfields extracted from 4-minute accelerated vs. 8-minute high-resolution T2-weighted 3T MRI scans - Shan Cong; Shannon L. Risacher; John D. West; Yu-Chien Wu; Liana G. Apostolova; Eileen Tallman; Maher Rizkalla; Paul Salama; Andrew J. Saykin; Li Shen (Brain Imaging and Behavior, 2018)

Confluentibacter flavum sp. nov., Isolated from the Saline Lake - Yu. Li; Xin-Jun Hou; Xia Shen; Shuai-Bo Han; Zhao Ju; Zhe Zhao; Xiao-Yun Yu; Min Wu; Cong Sun (Current Microbiology, 2018)

Origin of Early Cretaceous Guandian adakitic pluton in central eastern China: partial melting of delaminated lower continental crust triggered by ridge subduction - Ze-Bin Luo; Shuo Xue; Li-Peng Zhang; He Li; Cong-Ying Li; Hong Zhang; Yu-Long Liu; Ming-Xing Ling; Weidong Sun (International Geology Review, 2018)

Aquaporin 5 is degraded by autophagy in diabetic submandibular gland - Yan Huang; Xijin Shi; Qianying Mao; Yan Zhang; Xin Cong; Xueming Zhang; Zhejing Zhang; Liling Wu; Ruolan Xiang; Guangyan Yu (Science China Life Sciences, 2018)

Glucocorticoid receptor activation induces decrease of hippocampal astrocyte number in rats - Yu-Xia Lou; Jing Li; Zhen-Zhen Wang; Cong-Yuan Xia; Nai-Hong Chen (Psychopharmacology, 2018)

Thiosulfate amendment reduces mercury accumulation in rice (Oryza sativa L.) - Yunyun Li; Hailong Li; Yong Yu; Jiating Zhao; Yongjie Wang; Cong Hu; Hong Li; Guo Wang; Yufeng Li; Yuxi Gao (Plant and Soil, 2018)

Over-expression of CCK1 Receptor Reverse Morphine Dependence - Lijing Hao; Di Wen; Hongyan Gou; Feng Yu; Bin Cong; Chunling Ma (International Journal of Peptide Research and Therapeutics, 2018)

Identification of maize brace-root quantitative trait loci in a recombinant inbred line population - Ao Zhang; Zhenhai Cui; Cong Li; Jinhong Luo; Yixin Guan; Lingli Liu; Zhuang Zhang; Lijun Zhang; Yan He; Yanye Ruan; Haiqiu Yu (Euphytica, 2018)

Impacts of future climate change (2030-2059) on debris flow hazard: A case study in the Upper Minjiang River basin, China - Ming Li; Cong-shan Tian; Yu-kuan Wang; Qin Liu; Ya-feng Lu; Wang Shan (Journal of Mountain Science, 2018)

The removal of silver nanoparticle by titanium tetrachloride and modified sodium alginate composite coagulants: floc properties, membrane fouling, and floc recycle - Ziyang Wang; Yan Wang; Cong Yu; Yanxia Zhao; Meixia Fan; Baoyu Gao (Environmental Science and Pollution Research, 2018)

Cicada parasitic moths from China (Lepidoptera: Epipyropidae): morphology, identity, biology, and biogeography - Yunxiang Liu; Zhaofu Yang; Guoyun Zhang; Qingqing Yu; Cong Wei (Systematics and Biodiversity, 2018)

The Mechanism of Hyperalgesia and Anxiety Induced by Remifentanil: Phosphorylation of GluR1 Receptors in the Anterior Cingulate Cortex - Jie Zeng; Sisi Li; Chao Zhang; Guijin Huang; Cong Yu (Journal of Molecular Neuroscience, 2018)

Polyphasic taxonomic characterisation of a novel strain as Pararhizobium haloflavum sp. nov., isolated from soil samples near a sewage treatment tank - Xia Shen; Yu Li; Zhe Zhao; Yi-Fan Han; Wen-Wu Zhang; Xiao-Yun Yu; Chong-Ya Zhang; Cong Sun; Min Wu (Antonie van Leeuwenhoek, 2018)

Degradation of the earthy and musty odorant 2,4,6-tricholoroanisole by persulfate activated with iron of different valences - Kejia Zhang; Xinyan Zhou; Tuqiao Zhang; Lang Yu; Zheming Qian; Wenchao Liao; Cong Li (Environmental Science and Pollution Research, 2018)

Cropland physical disturbance intensity: plot-scale measurement and its application for soil erosion reduction in mountainous areas - Ming Li; Yu-kuan Wang; Pei Xu; Bin Fu; Cong-shan Tian; Shan Wang (Journal of Mountain Science, 2018)

Taxanes from Taxus wallichiana var. mairei cultivated in the southern area of the Yangtze River in China - Bo-Shu Lun; Li-Wei Shao; Yong Wang; Cong-Cong Li; Hua Yu; Chun-Hua Wang; Yan Zhu (Natural Product Research, 2017)

Autophagy induced by bovine viral diarrhea virus infection counteracts apoptosis and innate immune activation - Yulong Zhou; Yachao Ren; Yanlong Cong; Yu Mu; Renfu Yin; Zhuang Ding (Archives of Virology, 2017)

Optimization of Lipid Extraction and Determination of Fatty Acid Compositions in Edible Meats of Freshwater and Marine Shrimps - Li Zhou; Peixuan Li; Yuling Zhao; Shuang Hou; Baolei Cong; Jun Huang; Yu Ding; Xiaoxiong Zeng (Journal of Aquatic Food Product Technology, 2017)

Newcastle disease virus-like particles induce dendritic cell maturation and enhance viral-specific immune response - Jing Qian; Jiaxin Ding; Renfu Yin; Yixue Sun; Cong Xue; Xiaohong Xu; Jianzhong Wang; Chan Ding; Shengqing Yu; Xiufan Liu; Shunlin Hu; Yanlong Cong; et al. (Virus Genes, 2017)

Seasonal variations of organic carbon and nitrogen in the upper basins of Yangtze and Yellow Rivers - Xiang-ying Li; Yong-jian Ding; Tian-ding Han; Jian-zhong Xu; Shi-chang Kang; Qing-bai Wu; Mika Sillanpää; Zhong-bo Yu; Cong-rong Yu (Journal of Mountain Science, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Punicalagin protects bovine endometrial epithelial cells against lipopolysaccharide-induced inflammatory injury - An Lyu; Jia-jia Chen; Hui-chuan Wang; Xiao-hong Yu; Zhi-cong Zhang; Ping Gong; Lin-shu Jiang; Feng-hua Liu (Journal of Zhejiang University-SCIENCE B, 2017)

Decreased interaction between ZO-1 and occludin is involved in alteration of tight junctions in transplanted epiphora submandibular glands - Chong Ding; Xin Cong; Xue-Ming Zhang; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2017)

Novel hemostatic agents based on gelatin-microbial transglutaminase mix - Fang Lv; Xiaonan Cong; Wenshu Tang; Yiming Han; Yu Tang; Yongrui Liu; Liqiang Su; Mingyao Liu; Mingfei Jin; Zhengfang Yi (Science China Life Sciences, 2017)

Therapeutic value of nerve growth factor in promoting neural stem cell survival and differentiation and protecting against neuronal hearing loss - Zhao Han; Cong-Pin Wang; Ning Cong; Yu-Yan Gu; Rui Ma; Fang-Lu Chi (Molecular and Cellular Biochemistry, 2017)

Modeling the effects of the streamflow changes of Xinjiang Basin in future climate scenarios on the hydrodynamic conditions in Lake Poyang, China - Ling-Yan Qi; Jia-Cong Huang; Ren-Hua Yan; Jun-Feng Gao; Shi-Gang Wang; Yu-Yin Guo (Limnology, 2017)

Muscarinic acetylcholine receptor-mediated tight junction opening is involved in epiphora in late phase of submandibular gland transplantation - Ning-Yan Yang; Chong Ding; Jing Li; Yan Zhang; Ruo-Lan Xiang; Li-Ling Wu; Guang-Yan Yu; Xin Cong (Journal of Molecular Histology, 2017)

Development of a bacterial-based negative selection system for rapid screening of active single guide RNAs - Yu Nie; Peiqing Cong; Xiaofeng Liu; Min Wang; Yaosheng Chen; Zuyong He (Biotechnology Letters, 2017)

Isolation, chemical characterization, and immunomodulatory activity of naturally acetylated hemicelluloses from bamboo shavings - Ju-qing Huang; Rui-ting Qi; Mei-rong Pang; Cong Liu; Guang-yu Li; Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

Molecular characterization of HOXC8 gene and methylation status analysis of its exon 1 associated with the length of cashmere fiber in Liaoning cashmere goat - Wen L. Bai; Jiao J. Wang; Rong H. Yin; Yun L. Dang; Ze Y. Wang; Yu B. Zhu; Yu Y. Cong; Liang Deng; Dan Guo; Shi Q. Wang; Shu H. Yang; Hui L. Xue (Genetica, 2017)

Genetic diversity of the genotype VII Newcastle disease virus: identification of a novel VIIj sub-genotype - Cong Xue; Yanlong Cong; Renfu Yin; Yixue Sun; Chan Ding; Shengqing Yu; Xiufan Liu; Shunlin Hu; Jing Qian; Qianliang Yuan; Mingxi Yang; Chunfeng Wang; et al. (Virus Genes, 2017)

Two new compounds from Trollius chinensis Bunge - Ya Jie-Shi; Lin Wei-Sang; Rui Yan; Qiang Zhao; Yang Zhang; Gui Yun-Zhao; Yun Cong-Li; Xue Chen; Chong Yu-Zhang; Hua Qiao; Guo Gang-Zhang (Journal of Natural Medicines, 2017)

Lateral flow strip for visual detection of K-ras mutations based on allele-specific PCR - Cong Wang; Xiaomin Chen; Yuying Wu; Hao Li; Yu Wang; Xiaofu Pan; Tingting Tang; Ziying Liu; Xiaokun Li (Biotechnology Letters, 2016)

Streptomyces xinjiangensis sp. nov., an actinomycete isolated from Lop Nur region - Cong Cheng; Yu-Qian Li; Mipeshwaree Devi Asem; Chun-Yan Lu; Xiao-Han Shi; Xiao Chu; Wan-Qin Zhang; Deng- Di An; Wen-Jun Li (Archives of Microbiology, 2016)

Retrieval of sea surface winds under hurricane conditions from GNSS-R observations - Cheng Jing; Xiaofeng Yang; Wentao Ma; Yang Yu; Di Dong; Ziwei Li; Cong Xu (Acta Oceanologica Sinica, 2016)

Two AMT2-Type Ammonium Transporters from Pyrus betulaefolia Demonstrate Distinct Expression Characteristics - Hui Li; Yu Cong; You-hong Chang; Jing Lin (Plant Molecular Biology Reporter, 2016)

Molecular characterization, expression and methylation status analysis of BMP4 gene in skin tissue of Liaoning cashmere goat during hair follicle cycle - Wen L. Bai; Yun L. Dang; Jiao J. Wang; Rong H. Yin; Ze Y. Wang; Yu B. Zhu; Yu Y. Cong; Hui L. Xue; Liang Deng; Dan Guo; Shi Q. Wang; Shu H. Yang (Genetica, 2016)

Neuroprotective effects of a chromatin modifier on ischemia/reperfusion neurons: implication of its regulation of BCL2 transactivation by ERα signaling - Jun Guo; Tao Zhang; Jia Yu; Hong-Zeng Li; Cong Zhao; Jing Qiu; Bo Zhao; Jie Zhao; Wei Li; Tian-Zhi Zhao (Cell and Tissue Research, 2016)

Enhanced short-cut nitrification in an airlift reactor by CaCO3 attachment on biomass under high bicarbonate condition - Mohammad Ali; Li-Yuan Chai; Hai-Ying Wang; Chong-Jian Tang; Xiao-Bo Min; Xu Yan; Cong Peng; Yu-Xia Song; Ping Zheng (Biodegradation, 2016)

Molecular identification of ‘Candidatus phytoplasma asteris’ related strain (16SrΙ-B) associated with Broussonetia papyrifera in Nanjing, China - Cong-Jin Mei; Qing-Can Wang; Ju-Can Gui; Yan-Ling Ji; Han-Shou Yu (European Journal of Plant Pathology, 2016)

Altererythrobacter estronivorus sp. nov., an Estrogen-Degrading Strain Isolated from Yundang Lagoon of Xiamen City in China - Dan Qin; Cong Ma; Anyi Hu; Fangfang Zhang; Hongbo Hu; Chang-Ping Yu (Current Microbiology, 2016)

bFGF signaling-mediated reprogramming of porcine primordial germ cells - Yu Zhang; Jing Ma; Hai Li; Jiawei Lv; Renyue Wei; Yimei Cong; Zhonghua Liu (Cell and Tissue Research, 2016)

Activation of ETA Receptor by Endothelin-1 Induces Hepatocellular Carcinoma Cell Migration and Invasion via ERK1/2 and AKT Signaling Pathways - Ning Cong; Zhongmin Li; Wenbo Shao; Jinpeng Li; Shui Yu (The Journal of Membrane Biology, 2016)

Involvement of polyphosphate kinase in virulence and stress tolerance of uropathogenic Proteus mirabilis - Liang Peng; Qiao Jiang; Jia-Yun Pan; Cong Deng; Jing-Yi Yu; Xiao-Man Wu; Sheng-He Huang; Xiao-Yan Deng (Medical Microbiology and Immunology, 2016)

Dietary Selenium Status Regulates the Transcriptions of Selenoproteome and Activities of Selenoenzymes in Chicken Kidney at Low or Super-nutritional Levels - Jing-Xiu Xu; Cong Zhang; Chang-Yu Cao; Shi-Yong Zhu; Hui Li; Yan-Chun Sun; Jin-Long Li (Biological Trace Element Research, 2016)

Tectonic evolution of Tarim basin in Cambrian–Ordovician and its implication for reservoir development, NW China - Yu BINGSONG; RUAN ZHUANG; ZHANG CONG; PAN YINGLU; LIN CHANGSONG; WANG LIDONG (Journal of Earth System Science, 2016)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Dual-reporter Imaging and its Potential Application in Tracking Studies - Jie Ding; Chao Wang; Pei-Cheng Li; Zhen Zhao; Cheng Qian; Cong-Xiao Wang; Yu Cai; Gao-Jun Teng (Journal of Fluorescence, 2016)

Detection and identification of ‘Candidatus Phytoplasma ziziphi’ associated with violet orychophragmus yellow dwarf disease in China - Qing-Can Wang; Cong-Jin Mei; Ju-Can Gui; Yan-Ling Ji; Han-Shou Yu (Journal of General Plant Pathology, 2015)

Saccharothrix lopnurensis sp. nov., a filamentous actinomycete isolated from sediment of Lop Nur - Yu-Qian Li; Lan Liu; Cong Cheng; Xiao-Han Shi; Chun-Yan Lu; Zhou-Yan Dong; Nimaichand Salam; Deng-Di An; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Non-Stationary Annual Maximum Flood Frequency Analysis Using the Norming Constants Method to Consider Non-Stationarity in the Annual Daily Flow Series - Lihua Xiong; Tao Du; Chong-Yu Xu; Shenglian Guo; Cong Jiang; Christopher J. Gippel (Water Resources Management, 2015)

Generation and propagation of recombinant mumps viruses exhibiting an additional U residue in the homopolymeric U tract of the F gene-end signal - Christian J. Sauder; Laurie Ngo; Vahan Simonyan; Yu Cong; Cheryl Zhang; Malen Link; Tahir Malik; Steven A. Rubin (Virus Genes, 2015)

Evaluation of the potential effects of soil properties on molybdenum availability in soil and its risk estimation in paddy rice - Wei Jiang; Zhongfang Yang; Tao Yu; Qingye Hou; Cong Zhong; Guodong Zheng; Zhiqiang Yang; Jie Li (Journal of Soils and Sediments, 2015)

Reply to Shaocheng Ji’s discussion on ‘Coesite-bearing eclogite breccia: implication for coseismic ultrahigh-pressure metamorphism and the rate of the process’ by Yang et al. (Contrib. Mineral. Petrol., 2014, 167: 1013) - Jian-Jun Yang; Meng-Xi Huang; Hao-Ran Zhang; Cong Yu (Contributions to Mineralogy and Petrology, 2015)

The negative feedback regulation of microRNA-146a in human periodontal ligament cells after Porphyromonas gingivalis lipopolysaccharide stimulation - Shao-Yun Jiang; Dong Xue; Yu-Feng Xie; Dong-Wang Zhu; Yun-Yun Dong; Cong-Cong Wei; Jia-Yin Deng (Inflammation Research, 2015)

Accurate and Efficient Simulation of Fracture–Matrix Interaction in Shale Gas Reservoirs - Long Cai; Didier-Yu Ding; Cong Wang; Yu-Shu Wu (Transport in Porous Media, 2015)

3D-QSAR and docking study on 3-benzimidazol-2-ylhydroquinolin-2-one derivatives as VEGFR-2 tyrosine kinase inhibitors - Cong-min Kang; Dong-qing Liu; Xin-yu Wang; Ying-jie Dai; Jia-gao Cheng; Ying-tao Lv (Medicinal Chemistry Research, 2015)

Identification of microRNAs and their target genes in Alport syndrome using deep sequencing of iPSCs samples - Wen-biao Chen; Jian-rong Huang; Xiang-qi Yu; Xiao-cong Lin; Yong Dai (Journal of Zhejiang University-SCIENCE B, 2015)

The rice OsAMT1;1 is a proton-independent feedback regulated ammonium transporter - Shunying Yang; Dongli Hao; Yu Cong; Man Jin; Yanhua Su (Plant Cell Reports, 2015)

Molecular cloning and identification of an ammonium transporter gene from pear - Hui Li; Yu Cong; Jing Lin; You Hong Chang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Antidepressant-like effects of ferulic acid: involvement of serotonergic and norepinergic systems - Jianliang Chen; Dan Lin; Chong Zhang; Gaowen Li; Nianping Zhang; Lina Ruan; Qizhi Yan; Jianxin Li; Xuefeng Yu; Xupei Xie; Cong Pang; Liang Cao; et al. (Metabolic Brain Disease, 2015)

Development of a reverse genetics system based on RNA polymerase II for Newcastle disease virus genotype VII - Jianzhong Wang; Chunfeng Wang; Na Feng; Hualei Wang; Xuexing Zheng; Songtao Yang; Yuwei Gao; Xianzhu Xia; Renfu Yin; Xiufan Liu; Shunlin Hu; Chan Ding; et al. (Virus Genes, 2015)

Genetic polymorphism of the 26 short tandem repeat loci in the Chinese Hebei Han population using two commercial forensic kits - Liang Lei; Jie Xu; Qingqing Du; Lihong Fu; Xiaojing Zhang; Feng Yu; Chunling Ma; Bin Cong; Shujin Li (Molecular Biology Reports, 2015)

Isolation and molecular characterization of two novel HMW-GS genes from Chinese wheat (Triticum aestivum L.) landrace Banjiemang - Hui Shao; Tian-hong Liu; Cong-Fu Ran; Li-Qun Li; Jing Yu; Xin Gao; Xue-Jun Li (Genes & Genomics, 2015)

Identification of rice Di19 family reveals OsDi19-4 involved in drought resistance - Lili Wang; Changchun Yu; Cong Chen; Chunlan He; Yingguo Zhu; Wenchao Huang (Plant Cell Reports, 2014)

Annual input fluxes and source identification of trace elements in atmospheric deposition in Shanxi Basin: the largest coal base in China - Cong Zhong; Zhongfang Yang; Wei Jiang; Tao Yu; Qingye Hou; Desheng Li; Jianwu Wang (Environmental Science and Pollution Research, 2014)

Screening and monitoring zearalenone-producing Fusarium species by PCR and zearalenone by monoclonal antibodies in feed from China - Shi-Chun Pei; Yu-Ping Zhen; Jian-Wei Gao; Won-Jong Lee; Hong-Fu Zhang; Cheng Ji; Xuan-Zhe Zhang; Cong Chen (Food Additives & Contaminants Part B-Surveillance, 2014)

Development of three X-linked tetrameric microsatellite markers for forensic purposes - Chunnan Dong; Lihong Fu; Xiaojing Zhang; Chunling Ma; Feng Yu; Shujin Li; Bin Cong (Molecular Biology Reports, 2014)

Generation of CD44 gene-deficient mouse derived induced pluripotent stem cells - Zhenwei Song; Qianqian Ji; Haijing Zhao; Yu Nie; Zuyong He; Yaosheng Chen; Peiqing Cong (In Vitro Cellular & Developmental Biology - Animal, 2014)

Ectopic expression of reprogramming factors enhances the development of cloned porcine embryos - Zhenwei Song; Qianqian Ji; Haijing Zhao; Yu Nie; Zuyong He; Yaosheng Chen; Peiqing Cong (Biotechnology Letters, 2014)

Seasonal changes of the fatty acid composition in the hepatopancreas and vitelline gland of the gastropod Onchidium struma - Xue-Ping Ying; Hans-Uwe Dahms; Xiao-Ying Ni; Cong-Cong Hou; Yu-Jie Zhang; Wan-Xi Yang (Marine Biology Research, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Annual input fluxes of heavy metals in agricultural soil of Hainan Island, China - Wei Jiang; Qingye Hou; Zhongfang Yang; Tao Yu; Cong Zhong; Yi Yang; Yangrong Fu (Environmental Science and Pollution Research, 2014)

6′- O -Caffeoylarbutin inhibits melanogenesis in zebrafish - Min Xu; Qiao-Cong Lao; Ping Zhao; Xiao-Yu Zhu; Hong-Tao Zhu; Xu-Lu Luo; Chong-Ren Yang; Jian-Hui He; Chun-Qi Li; Ying-Jun Zhang (Natural Product Research, 2014)

Effect of miR-205 on 3T3-L1 preadipocyte differentiation through targeting to glycogen synthase kinase 3 beta - Jingwei Yu; Yaosheng Chen; Limei Qin; Luxi Cheng; Guangcai Ren; Peiqing Cong; Delin Mo; Zuyong He (Biotechnology Letters, 2014)

Activation of STAT3 stimulates AHSP expression in K562 cells - Cong Cao; GuoWei Zhao; Wei Yu; XueMin Xie; WenTian Wang; RuiFeng Yang; Xiang Lv; DePei Liu (Science China Life Sciences, 2014)

A systematic proteomic analysis of NaCl-stressed germinating maize seeds - Ling-Bo Meng; Yi-Bo Chen; Tian-Cong Lu; Yue-Feng Wang; Chun-Rong Qian; Yang Yu; Xuan-Liang Ge; Xiao-Hui Li; Bai-Chen Wang (Molecular Biology Reports, 2014)

High seroprevalence of Chlamydia infection in sows in Hunan province, subtropical China - Xiao-Xuan Zhang; Run-Cheng Li; Guo-Hua Liu; Wei Cong; Hui-Qun Song; Xing-Long Yu; Xing-Quan Zhu (Tropical Animal Health and Production, 2014)

Probability-based damage assessment for reinforced concrete bridge columns considering the corrosive and seismic hazards in Taiwan - Chien-Kuo Chiu; Yue-Cong Lyu; Wen-Yu Jean (Natural Hazards, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Stable carbon and hydrogen isotopes of gases from the large tight gas fields in China - JinXing Dai; YunYan Ni; GuoYi Hu; ShiPeng Huang; FengRong Liao; Cong Yu; DeYu Gong; Wei Wu (Science China Earth Sciences, 2014)

Male Accessory Gland Secretions Modulate Female Post-Mating Behavior in the Moth Spodoptera litura - Jin-Feng Yu; Cong Li; Jin Xu; Jian-Hong Liu; Hui Ye (Journal of Insect Behavior, 2014)

Olfactory Cues Used in Host Selection by Frankliniella occidentalis (Thysanoptera: Thripidae) in Relation to Host Suitability - Yu Cao; Junrui Zhi; Chunlei Cong; David C. Margolies (Journal of Insect Behavior, 2014)

Comparison of Hydrolysis Efficiency and Enzyme Adsorption of Three Different Cellulosic Materials in the Presence of Poly(ethylene Glycol) - Min Zhang; Jia Ouyang; Baotian Liu; Heng Yu; Ting Jiang; Cong Cai; Xin Li (BioEnergy Research, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

Novel 2-(E)-substituted benzylidene-6-(N-substituted aminomethyl)cyclohexanones and cyclohexanols as analgesic and anti-inflammatory agents - Dan Liu; Weishe Yu; Jingjing Li; Cong Pang; Linxiang Zhao (Medicinal Chemistry Research, 2013)

Induction of viable gynogenetic progeny using eggs and UV-irradiated sperm from the Chinese tetraploid loach, Misgurnus anguillicaudatus - Ya-Juan Li; Zhuo Yu; Ming-Zhao Zhang; Cong Qian; Syuiti Abe; Katsutoshi Arai (Aquaculture International, 2013)

MiR-143 is not essential for adipose development as revealed by in vivo antisense targeting - Zuyong He; Jingwei Yu; Chunyan Zhou; Guangcai Ren; Peiqing Cong; Delin Mo; Yaosheng Chen; Xiaohong Liu (Biotechnology Letters, 2013)

The SOX gene family: function and regulation in testis determination and male fertility maintenance - Ting Jiang; Cong-Cong Hou; Zhen-Yu She; Wan-Xi Yang (Molecular Biology Reports, 2013)

Isolation and characterization of polymorphic microsatellite markers in the fish Garra orientalis (oriental sucking barb) - Li-Wei Su; Zhi-Zhi Liu; Cong-Tao Wang; Zhen Zeng; Ang-Yu Liu; Wen-Qiao Tang; Jin-Quan Yang (Conservation Genetics Resources, 2013)

Characterization and Expression of a Phytochelatin Synthase Gene in Birch-leaf Pear (Pyrus betulaefolia Bunge) - You Hong Chang; Hui Li; Yu Cong; Jing Lin; Bao Long Sheng (Plant Molecular Biology Reporter, 2012)

Evaluation of a DNA vaccine candidate co-expressing GP3 and GP5 of porcine reproductive and respiratory syndrome virus (PRRSV) with interferon α/γ in immediate and long-lasting protection against HP-PRRSV challenge - Yijun Du; Jing Qi; Yu Lu; Jiaqiang Wu; Dongwan Yoo; Xing Liu; Xiumei Zhang; Jun Li; Wenbo Sun; Xiaoyan Cong; Jianli Shi; Jinbao Wang (Virus Genes, 2012)

Developmental changes in lysophospholipid receptor expression in rodent heart from near-term fetus to adult - Fang Wang; Jianfeng Hou; Bianmei Han; Yu Nie; Xiangfeng Cong; Shengshou Hu; Xi Chen (Molecular Biology Reports, 2012)

Genome sequence determination and analysis of a Chinese virulent strain, LMS, of Gallid herpesvirus type 2 - Yun Cheng; Feng Cong; Yan-ping Zhang; Zhi-jie Li; Na-na Xu; Guang-yu Hou; Chang-jun Liu (Virus Genes, 2012)

A fully human CD19/CD3 bi-specific antibody triggers potent and specific cytotoxicity by unstimulated T lymphocytes against non-Hodgkin’s lymphoma - Yan Zhou; Lan-tu Gou; Bo Mu; Wei-chan Liao; Jing He; Cong Ma; Yu-qin Yao; Jin-liang Yang (Biotechnology Letters, 2012)

Aluminum ammonium sulfate dodecahydrate purified from traditional Chinese medicinal herb Korean monkshood root is a potent matrix metalloproteinase inhibitor - Yehua Shen; Sen Liu; Fenghai Jin; Tianyang Mu; Cong Li; Kun Jiang; Weihua Tian; Dahai Yu; Yingqi Zhang; Xuexun Fang (BioMetals, 2012)

Seasonal variation in population characteristics and management implications for brown rats (Rattus norvegicus) within their native range in Harbin, China - Da-Wei Wang; Lin Cong; Ling-Fen Yue; Bao-Huan Huang; Jian-Xu Zhang; Yu Wang; Ning Li; Xiao-Hui Liu (Journal of Pest Science, 2011)

Changes of paired-pulse evoked responses during the development of epileptic activity in the hippocampus - Zhou-yan Feng; Xiao-jing Zheng; Cong Tian; Yang Wang; Hao-yu Xing (Journal of Zhejiang University-SCIENCE B, 2011)

Differential expression of oncogenic miRNAs in proliferating and senescent human fibroblasts - Miao Wang; Zhaojie Cheng; Tian Tian; Jingwen Chen; Fei Dou; Mingzhou Guo; Yu-Sheng Cong (Molecular and Cellular Biochemistry, 2011)

The mechanisms underlying ICa heterogeneity across murine left ventricle - Lin Xu; Xu-Yong Li; Yu Liu; Hai-Tao Li; Jing Chen; Xiao-Yan Li; Xue-Jun Jiang; Gang Wu; Yan-Hong Tang; Xi Wang; Cong-Xin Huang (Molecular and Cellular Biochemistry, 2011)

The origin of natural tetraploid loach Misgurnus anguillicaudatus (Teleostei: Cobitidae) inferred from meiotic chromosome configurations - Ya-Juan Li; Zhuo Yu; Ming-Zhao Zhang; Cong Qian; Syuiti Abe; Katsutoshi Arai (Genetica, 2011)

Requirement of regulated endocrine-specific protein-18 for development and expression of regulated endocrine-specific protein-18 isoform c in mice - Min Liang; Jian Ling Yang; Min Juan Bian; Jie Liu; Xiao Qi Hong; Yan Cong Wang; Yu Fang Huang; Shu Ping Gu; Mei Yu; Fang Huang; Jian Fei (Molecular Biology Reports, 2011)

Estrogen modulation of peripheral pain signal transduction: involvement of P2X3 receptors - Bei Ma; Li-hua Yu; Juan Fan; Binhai Cong; Ping He; Xin Ni; Geoffrey Burnstock (Purinergic Signalling, 2011)

Antioxidant activities of recombinant amphioxus (Branchiostoma belcheri) apolipoprotein D - Yu Zhang; Yi Cong; Shaohui Wang; Shicui Zhang (Molecular Biology Reports, 2011)

Effects of a Synthetic bFGF Antagonist Peptide on the Proteome of 3T3 Cells Stimulated with bFGF - Xiaoping Wu; Xinglong Jia; Yuhua Ji; Cong Wang; Yonglin Yu; Susu Gao; Quchou Li; Xiaokun Li (International Journal of Peptide Research and Therapeutics, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

Comparative temporal analyses of the Pinus sylvestris L. var. mongolica litv. apical bud proteome from dormancy to growth - Ying-Dong Bi; Zhi-Gang Wei; Zhuo Shen; Tian-Cong Lu; Yu-Xiang Cheng; Bai-Chen Wang; Chuan-Ping Yang (Molecular Biology Reports, 2011)

Methotrexate ameliorates pristane-induced arthritis by decreasing IFN-γ and IL-17A expressions - Wei-kun Hou; Lie-su Meng; Fang Zheng; Yu-rong Wen; Wen-hua Zhu; Cong-shan Jiang; Xiao-jing He; Yan Zhou; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2011)

Genetic analysis of avian paramyxovirus-1 (Newcastle disease virus) isolates obtained from swine populations in China related to commonly utilized commercial vaccine strains - Zhuang Ding; Yan-long Cong; Shuang Chang; Guang-mei Wang; Ze Wang; Quan-peng Zhang; Hao Wu; Yu-zhang Sun (Virus Genes, 2010)

Relation of uric acid levels to aortic root dilatation in hypertensive patients with and without metabolic syndrome - Li-jiang Tang; Jian-jun Jiang; Xiao-feng Chen; Jian-an Wang; Xian-fang Lin; Yu-xi Du; Cong-feng Fang; Zhao-xia Pu (Journal of Zhejiang University-SCIENCE B, 2010)

Functional Identification of a Putative β-Galactosidase Gene in the Special lac Gene Cluster of Lactobacillus acidophilus - Qu Pan; Junmin Zhu; Lina Liu; Yanguang Cong; Fuquan Hu; Jinchuan Li; Xiaoping Yu (Current Microbiology, 2010)

Protein sumoylation sites prediction based on two-stage feature selection - Lin Lu; Xiao-He Shi; Su-Jun Li; Zhi-Qun Xie; Yong-Li Feng; Wen-Cong Lu; Yi-Xue Li; Haipeng Li; Yu-Dong Cai (Molecular Diversity, 2010)

Effects of several immunostimulants on phenoloxidase and hemocytes of the crab Charybdis japonica - Tingjun Fan; Miaomiao Yu; Lingling Yang; Zhenping Shi; Wenjie Sun; Rishan Cong; Xiuxia Yang; Guojian Jiang (Journal of Ocean University of China, 2009)

Slope runoff study in situ using rainfall simulator in mountainous area of North China - Jingjie Yu; Cong Yang; Changming Liu; Xianfang Song; Shanshan Hu; Fadong Li; Changyuan Tang (Journal of Geographical Sciences, 2009)

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)

Prediction of compounds’ biological function (metabolic pathways) based on functional group composition - Yu-Dong Cai; Ziliang Qian; Lin Lu; Kai-Yan Feng; Xin Meng; Bing Niu; Guo-Dong Zhao; Wen-Cong Lu (Molecular Diversity, 2008)

Using AdaBoost for the prediction of subcellular location of prokaryotic and eukaryotic proteins - Bing Niu; Yu-Huan Jin; Kai-Yan Feng; Wen-Cong Lu; Yu-Dong Cai; Guo-Zheng Li (Molecular Diversity, 2008)

The distributions of autumn picoplankton in relation to environmental factors in the reservoirs along the Wujiang River in Guizhou Province, SW China - Baoli Wang; Cong-Qiang Liu; Fushun Wang; Yuanxiu Yu; Lihua Zhang (Hydrobiologia, 2008)

A probiotic treatment containing Lactobacillus, Bifidobacterium and Enterococcus improves IBS symptoms in an open label trial - Yu-jing Fan; Shu-jie Chen; Ying-cong Yu; Jian-min Si; Bin Liu (Journal of Zhejiang University-SCIENCE B, 2006)

Agrobacterium-mediated transformation of the apple rootstock Malus micromalus Makino with the RolC gene - Zhen Zhang; Aijun Sun; Yu Cong; Bingcheng Sheng; Quanhong Yao; Zong-Ming Cheng (In Vitro Cellular & Developmental Biology - Plant, 2006)

Cloning of a novel human NHEDC1 (Na+/H+ exchanger like domain containing 1) gene expressed specifically in testis - Guangming Ye; Cong Chen; Dingding Han; Xiabin Xiong; Yahui Kong; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Zircon Ce4+/Ce3+ ratios and ages for Yulong ore-bearing porphyries in eastern Tibet - Hua-Ying Liang; Ian H. Campbell; Charlotte Allen; Wei-Dong Sun; Cong-Qiang Liu; Heng-Xiang Yu; Ying-Wen Xie; Yu-Qiang Zhang (Mineralium Deposita, 2006)

Construction of a non-antibiotic expression system in a marine cyanobacterium Synechococcus sp. PCC 7002 and its application in production of oral vaccine against enterotoxin of Escherichia coli - Dongyi Xu; Xin Yu; Cong Guo; Jindong Zhao (Journal of Applied Phycology, 2006)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

Characterization of soybean genomic features by analysis of its expressed sequence tags - Ai-Guo Tian; Jun Wang; Peng Cui; Yu-Jun Han; Hao Xu; Li-Juan Cong; Xian-Gang Huang; Xiao-Ling Wang; Yong-Zhi Jiao; Bang-Jun Wang; Yong-Jun Wang; Jin-Song Zhang; et al. (Theoretical and Applied Genetics, 2004)

A novel scale-up method for mammalian cell culture in packed-bed bioreactor - Chunshui Cong; Yu Chang; Jixian Deng; Chengzu Xiao; Zhiguo Su (Biotechnology Letters, 2001)

Transactivation by expression of the hepatitis B virus X protein with an inducible system - Azliyati Azizan; Yu-Sheng Cong; Ken Shain; Shih-Chang Tsai; Ya-Li Yao; Nancy Olashaw; Edward Seto (Molecular Biology Reports, 1998)